Remarks on the Proportions and Dimensions Used in the Design of the Medieval Church of Zsámbék - Fehér, Krisztina; Halmos, Balázs (Periodica Polytechnica Architecture, 2019)
Since the 19th century, the church of Zsámbék was continuously a focus of scholars' interest. The present paper intends to research the church ruins with a new aspect. Using an accurate terrestrial laser scan survey, the geometry of the plan is analysed in order to find proportions among the dimensions. The main goal of the study is to gather information about the design logic of the first masters of the 13th-century Premonstratensian abbey. In addition, our goal was to detect contributions to the 13th-century construction history of the church, that cannot be found in archives of graphic sources. The latest archaeological excavation achieved excellent results concerning several crucial historical points; however, the periodization of the church is still not entirely clarified. From the 19th century, different scholars have proposed various hypotheses about this topic, without consensus.
Number: 2
Keywords: zsámbék

Handlist of Premonstratensian Cartularies - Seale, Yvonne (2019)
Keywords: 📚 premonstratensian (general)

Silence, leadership and service: a medieval Premonstratensian contribution to interreligious dialogue - Hyland, William (Scottish Episcopal Institute Journal, 2019)
Keywords: 📚 premonstratensian (general)

Yvelines. Ancienne abbaye d'Abbecourt à Orgeval : le site réaménagé est dédié à Jean Pruvost - Richardson, Thomas (78Actu, 2019)
Keywords: abbecourt

Kościoły klasztorne norbertanek w średniowiecznej Polsce w świetle reform monastycznych XI i XII w. - Sokołowski, Norbert (Jagiellonian University, 2019)
Theme of this thesis are churches of premonstratensians in medieval Poland shown in light of monastical reforms in 11th and 12th century. The purpose of this thesis is to connect medieval churches of premonstratensians in Poland: in Strzelno and in Kraków-Zwierzyniec with churches, which were built under influence of „Hirsau reform“. Thesis consists of 5 chapters. In the first one author presents in shortened form the beginning of premonstratensians, the female’s branch of this order and history of premonstratensians‘ beginning in Poland. In the second chapter author presents the state of research about churches in Strzelno, their history and description. In the third chapter author presents analogous informations about Saint Salvator‘s church in Kraków-Zwierzyniec. In the fourth chapter author presents the state of research and the history of Saint Augustine and John the Baptist church in Kraków-Zwierzyniec. In the fifth chapter author analyses similarities and differences between churches in Strzelno and Kraków and churches, mainly on german territories, which were built under influence of „Hirsau reform“.
Accepted: 2020-07-28T01:15:44Z
Keywords: 🇵🇱 poland (general)

Sainte Anne - L'histoire et la legende - Lange, Chantal (La gazette de Sedunum: Senots et Blèquencourt, 2019)
Keywords: sainte-anne-de-nouveau-lieu

De geschiedenis van de abdij van Fulco van Berne (en Altforst) nu digitaal in te zien - Deurloo, Peter (De Gelderlander, 2019)
Keywords: berne

Tongland Abbey excavations: recent findings (Kirkcudbright History Society, 2019)
Keywords: tongland

Abdijbibliotheek Van Berne (2019)
Keywords: berne

Das Kloster Elisabethenzell (Spessartprojekt: Die Europäische Kulturlandschaft Spessart, 2019)
Keywords: einsiedel

L’Ordre de Prémontré en Agenais: Prieurés et granges dépendant de l’abbaye Saint-Jean de la Castelle - Abadie, Stéphane (Bulletin de la Société académique d'Agen, 2019)
Keywords: la castelle

La circulation des chanoines prémontrés à travers les Pyrénées (xiie-xve siècle) - Abadie, Stéphane (Monastères et couvents de montagne : circulation, réseaux, influences au Moyen Âge, 2019)
Keywords: 🇫🇷 france (general)

Les abbayes prémontrées de la circarie de Gascogne - Abadie, Stéphane (Actes officiels du 44e colloque du Centre d'Etudes et de Recherches Prémontrées. Circarie de Gascogne. Les prémontrés et la frontière. Pays Basque, 2018, 2019)
Keywords: 🇫🇷 france (general)

Notes sur deux inscriptions tumulaires provenant de l'abbaye d'Arthous - Abadie, Stéphane (Bulletin de la Société de Borda, 2019)
Keywords: arthous

Prémontrés et frontières dans la circarie de Gascogne - Abadie, Stéphane (Actes officiels du 44e colloque du Centre d'Etudes et de Recherches Prémontrées. Circarie de Gascogne. Les prémontrés et la frontière. Pays Basque, 2018, 2019)
Keywords: 🇫🇷 france (general)

San Giorgio in Gratteri. La storia intrigante di un monumento normanno - Agostaro, Francesco (Marsala, 2019)
Keywords: gratteri

Een ambitieus kanunnik grijpt de macht. Joos Bruylant, Grimbergs abdijleven en intriges in de late vijftiende eeuw - Appelmans, Janick (Premonstratenzers en premonstratenzerinnen in Brabant, 2019)
Pages: 71-77
Keywords: grimbergen

Les prémontrés brabançons face aux frontières - Appelmans, Janick (Circarie de Gascogne. Les prémontrés et la frontière. Actes officiels du 44e colloque du Centre d’Études et de Recherches Prémontrées. Pays basque - 2018, 2019)
Keywords: 🇧🇪 belgium (general)

Premonstratenzers en premonstratenzerinnen in Brabant: terugblikken op een kwarteeuw onderzoek - Appelmans, Janick (Premonstratenzers en premonstratenzerinnen in Brabant, 2019)
Pages: 1-12
Keywords: 🇧🇪 belgium (general)

O paradoxo premonstratense após a morte de Norberto de Xanten (1135): vida monástica ou vida canônica? - Araújo, Vinicius Cesar Dreger de (Anais dos Encontros Internacionais de Estudos Medievais, 2019)
Keywords: 📚 premonstratensian (general)

Anselm of Havelberg as 'ecumenist': fiction and history - Avvakumov, Yuri P. (Les récits historiques entre Orient et Occident (XIe-XVe siècle), 2019)
Keywords: 👤 anselm of havelberg

Los premonstratenses: su presencia en España (1143-1835) - Barbastro Gil, Luis (Instituto Alicantino de Cultura, 2019)
Keywords: 🇪🇸 spain (general)

Una presència dels canonges premonstratesos segons el model colonial: Bellpuig d'Artà (1230-1425) - Batle, Josep Amengual i (De Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà, 2019)
Section: De Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà
Keywords: bellpuig de artá

L'abbaye Notre-Dame de l'Assomption de Lahonce - Bioy, François (Actes officiels du 44e colloque du Centre d'Etudes et de Recherches Prémontrées. Circarie de Gascogne. Les prémontrés et la frontière. Pays Basque, 2018, 2019)
Keywords: lahonce

Bergedorf: Prämonstratenser und Prämonstratenserinnen - Bock, Günther (Klosterbuch Schleswig-Holstein und Hamburg : Klöster, Stifte und Konvente von den Anfängen bis zur Reformation, 2019)
Keywords: bergedorf

Durance et sa grange prémontrée d'après quelques documents des XVe, XVIe et XVIIe siècles - Bouillac, Hervé (Revue de l'Agenais, 2019)
Keywords: durance

Die Altarretabel der Marienkriche in Gelnhausen im Kontext der mittelalterlichen Ausstattung. Beobachtungen, Probleme und Fragen - Buchkremer, Michael (Werke, Kontexte, Ensembles, 2019)
Keywords: gelnhausen (marienkirche)

Premonstreit in het Rijksarchief - Carnier, Marc (Premonstratenzers en premonstratenzerinnen in Brabant, 2019)
Pages: 13-18
Keywords: 📚 premonstratensian (general)

De abdij van Averbode: een verhaal van steen en marmer. - Ceukelaire, Marleen de (La pierre comme porteur de messages du chantier de construction et de la vie du bâtiment: actes du XXIe Colloque International de Glyptographie, Amay (Belgique), du 8 au 14 juillet 2018, 2019)
Keywords: averbode

The monasteries of the Canons of Prémontré, c.1180–c.1607 - Clyne, Miriam (Households of God: The Regular Canons and Canonesses of St Augustine and of Prémontré in Medieval Ireland, 2019)
Keywords: 🇮🇪 ireland (general)

La grange de Durance, établissement prémontré du XIIIe s., programme architectural exemplaire - Corvisier, Christian (Revue de l'Agenais, 2019)
Keywords: durance

Adam of Dryburgh - Damian-Grint, Peter (The History of Scottish Theology, Volume I: Celtic Origins to Reformed Orthodoxy, 2019)
Keywords: 👤 adam of dryburgh

Von Prémontré nach Magdeburg. Die Ausbreitung der Prämonstratenser im deutschen Nordosten - Ehlers-Kisseler, Ingrid (Jahrbuch für mitteldeutsche Kirchen- und Ordensgeschichte, 2019)
Keywords: 🇩🇪 germany (general)

L'abbaye de Doue (Haute-Loire), l'exemple d'un établissement de Prémontré en Velay (XIIe-XVe siècles) - Éneau-Brun, Lise (Les monastères de chanoines réguliers en France du XIe au XVIIIe siècle: actes de la sixième journée d'étude du 26 mai 2018 à Saint-Martin-aux-Bois (Oise), 2019)
Keywords: doue

Grafengruft und Luftheizung: zwei aufsehenerregende archäologische Befunde im Kloster Wedinghausen in Arnsberg - Essling-Wintzer, Wolfram (Sauerland, 2019)
Keywords: wedinghausen

Die Grafengruft im Kapitelsaal von Kloster Wedinghausen in Arnsberg - Essling-Wintzer, Wolfram; Strohmann, Dirk (Archäologie in Westfalen-Lippe, 2019)
-
Keywords: wedinghausen

Der Heilige Livinus und die Reform des Prämonstratenserstiftes - Fasbender, Christoph (Analecta Praemonstratensia, 2019)
Keywords: 📚 premonstratensian (general)

Les prémontrés d'Alsace entre deux frontières - Fischer, Marie-Thérèse (Actes officiels du 44e colloque du Centre d'Etudes et de Recherches Prémontrées. Circarie de Gascogne. Les prémontrés et la frontière. Pays Basque, 2018, 2019)
Keywords: 🇫🇷 france (general)

Courte histoire de l'ordre Prémontré - Flaujac, Robert de (Revue de l'Agenais, 2019)
Keywords: 📚 premonstratensian (general)

Torre Abbey, Devon : the archaeology of the Premonstratensian Abbey - Forde, Deirdre (Oxford Archaeology, 2019)
Keywords: torre

Premonstratensian Convent Complex in the Polish Lands: Imbramowice in the Past and Today - Gil-Mastalerczyk, Joanna (IOP Conference Series: Materials Science and Engineering, 2019)
Keywords: imbramowice

Monasterio Santa Cruz de la Zarza - González Pérez, María Luisa (Ayuntamiento de Ribas de Campos, 2019)
Keywords: santa cruz de ribas

Sepulcres, altars i relíquies. Els canonges il.lustrats de Bellpuig de les Avellanes i la recerca històrica - González, Alberto Velasco (De Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà, 2019)
Section: De Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà
Keywords: bellpuig de las avellanes

Gräfin Ermengardis und zwei Wappenscheiben aus der Grafenkapelle des Prämonstratenserklosters Wedinghausen, Arnsberg: Überlegungen zu den jüngsten archäologischen Untersuchungen - Gosmann, Michael (SüdWestfalen Archiv, 2019)
Keywords: wedinghausen

Locuri de adeverire din spațiul transilvan (secolele XIII-XVI). Studiu de caz: conventul premonstratens din Dealul Orăzii - Gross, Lidia (Anuarul Institutului de Istorie »George Bariţiu« - Series HISTORICA - Supliment, 2019)
Publisher: Editura Academiei Române
Keywords: váradhegyfok

Transfer de proprietate și autentificare: moșia Eriu Sâncrai și conventul din Dealul Orăzii în prima jumătate a secolului al XIV-lea - Gross, Lidia (Anuarul Institutului de Istorie »George Bariţiu« - Series HISTORICA, 2019)
Publisher: Editura Academiei Române
Keywords: váradhegyfok

Zur Wasserwirtschaft des prämonstratensischen Chorherrenstifts Broda - Hardt, Matthias (Usus aquarum. Interdiszipinäre Studien zur Nutzung und Bedeutung von Gewässern im Mittelalter, 2019)
Keywords: broda

Frömmigkeit transferieren?: Traditionskerne und Wandel der Prämonstratenser-Domkapitel Brandenburg und Havelberg in den Herausforderungen der Reformation des 16. Jahrhunderts - Heimann, Heinz-Dieter (Analecta Praemonstratensia, 2019)
Keywords: brandenburg:cathedral; havelberg

Barnard Castle, Bowes Castle and Egglestone Abbey - Hislop, Malcolm J.B. (English Heritage, 2019)
Keywords: egglestone

Abbot Jacob Panhausen of Steinfeld’s Praefatio in Regulam Divi Aurelii Augustini Hypponensis Episcopi (1570 Text and Commentary) - Hyland, William (Analecta Praemonstratensia, 2019)
Keywords: steinfeld

Bellpuig ens interpel.la: interrogants en la recerca arqueològica al priorat artanenc - Inglada Grau, Helena (De Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà, 2019)
Section: De Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà
Keywords: bellpuig de artá

De molens van de abdij van Grimbergen - Janssens, H. (Abdijmolens. Natuurkracht ten dienste van norbertijnen en norbertinessen, 2019)
Keywords: grimbergen

De stichting van de Abdij van Averbode vanuit de bewaarde oorkonden (1133-1139) - Janssens, Herman (Premonstratenzers en premonstratenzerinnen in Brabant, 2019)
Pages: 19-37
Keywords: averbode

Molenpatrimonium norbertijnenabdijen BENELUX - Janssens, Herman (Abdijmolens. Natuurkracht ten dienste van norbertijnen en norbertinessen, 2019)
Pages: 55-71
Keywords: 🇧🇪 belgium (general); 🇳🇱 netherlands (general)

Beauport: une abbaye au coeur de l’histoire et des histoires de Bretagne - Jeanneau, Cédric (Quel Moyen Age? La recherche en question, 2019)
Num Pages: 551 Pp.
Keywords: beauport

Les prémontrés de Beauport et la frontière - Jeanneau, Cédric (Actes officiels du 44e colloque du Centre d'Etudes et de Recherches Prémontrées. Circarie de Gascogne. Les prémontrés et la frontière. Pays Basque, 2018, 2019)
Keywords: beauport

Życiowe dokonania Cypriana – zakonnika i biskupa wrocławskiego w latach 1201–1207 - Jerzak, Norbert (Wrocławski Przegląd Teologiczny, 2019)
Keywords: 👤 cyprian of wrocław

Das Kloster Selbold - Keil, Manfred; Peschelt, Rainer; Schuldt, Anita (Mitteilungsblatt. Zentrum für Regionalgeschichte ; Kreisausschuss des Main-Kinzig-Kreises, Amt für Kultur, Sport Ehrenamt und Regionalgeschichte, 2019)
Keywords: selbold

Das Rätsel um den Heiligen Hermann-Josef von Steinfeld - Klinkhammer, Heike; Salwator, Wydawnictwo (Kath. Kirchengemeinde Steinfeld, 2019)
OCLC: 1150391685
Keywords: 👤 hermann joseph of steinfeld

Der Heilig Kreuz Altar aus der Klosterkirche Ahnaberg - König, Alexandra (Mittelalterliche Retabel in Hessen: Werke, Kontexte, Ensembles, 2019)
Keywords: ahnaberg

Die Handschrift rkps 67 des Prämonstratenserinnenstifts Zwierzyniec bei Krakau: Sicherung und Organisation konstitutiven Wissens - Kornemann, Ivonne (Von der Ostsee zum Mittelmeer: Forschungen zur mittelalterlichen Geschichte für Wolfgang Huschner, 2019)
Keywords: zwierzyniec

Der selige Hroznata von Tepl im Lichte der neueren Forschung - Kubín, Petr (Analecta Praemonstratensia, 2019)
Keywords: 👤 hroznata of bohemia

Juliana Alžběta Sekerková ze Sedčic, převorka kláštera premonstrátek v Doksanech a spoluautorka válečných pamětí - Kuchařová, Hedvika (Bohemia Occidentalis Historica, 2019)
The essay focuses on the life and activities of Juliana Alžběta Sekerková of Sedčice. She was born 1615 in a noble family, probably non -Catholic. After the death of her parents she entered the Premonstratensian Canonry in Doksany (1636) where she later became prioress (1655). Her early life in the religious community was aff ected by the wartime’s violence and danger which repeatedly forced the whole convent to leave Doksany. As prioress Juliana Alžběta was involved in a controversy between Vincent, Abbot of Strahov and Cyrill, Provost of Doksany on the side of the latter. Wartime and the following years (to 1683) were described in her chronicle which continued a previous chronicle by provost Nicholas. She also authored „Vitae“ of the Doksany canonesses of her time.
Accepted: 2021-03-11T09:20:07Z Publisher: viaCentrum
Keywords: doksany

Kein Stein blieb auf dem anderen ...: Frauenabtei Klosterkumbd und die Beziehungen zum Kloster Maria Engelport bei Treis-Karden - Kugel, Heinz (Jahrbuch Hunsrückverein, 2019)
Keywords: engelport

Die Pfarr- und Klosterkirche Windberg: ein sternenübersätes Gotteshaus für die Herrin der Sterne - Kugler, Hermann Josef (Schnell & Steiner, 2019)
Keywords: windberg

Man on Fire. The Life and Spirit of Norbert of Xanten - Kunkel, Thomas (Center for Norbertine Studies, 2019)
Keywords: 👤 norbert of xanten

Kennen Sie das Kloster Heiligenthal?: Der Prämonstratenser-Orden fand auf einem ritterlichen Gut in Siebelingsborstel, das in Hilgendale umbenannt wurde, ein Zuhause - Lange, Irene (Quadrat, 2019)
Keywords: heiligenthal

Prémontrés et frontières du Nord sous l'Ancien Régime - Leduc, Christophe (Actes officiels du 44e colloque du Centre d'Etudes et de Recherches Prémontrées. Circarie de Gascogne. Les prémontrés et la frontière. Pays Basque, 2018, 2019)
Keywords: 🇫🇷 france (general)

Die Prälatenversammlung der Schwäbischen Zirkarie in Waldsee 1567 - Leinsle, Ulrich G. (Analecta Praemonstratensia, 2019)
Keywords: 🇩🇪 germany (general)

Vrejlev Klosterkirkes middelalderlige bygningshistorie - Lindholt, Pia Katrine; Larsen, Morten (Kuml, 2019)
Number: 68
Keywords: vrejlev

Quellen zur Geschichte des Stiftes Flaesheim im 14. Jahrhundert, I - Lindken, Theodor; Schwabe, Gabriele (Vestische Zeitschrift, 2019)
Keywords: flaesheim

El monestir premonstratès de Santa Maria de Bellpuig de les Avellanes, panteó comtal - Llevot, Francesc Fité i (De Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà, 2019)
Autoría: Francesc Fité i Llevot. Localización: De Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà, 2019. Artículo de Libro en Dialnet.
Section: De Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà
Keywords: bellpuig de las avellanes

La tradition érémitique en Champagne au Moyen Âge: l'exemple de saint Berthauld et des prémontrés à Chaumont-Porcien - Lusse, Jackie (Revue historique ardennaise, 2019)
Keywords: chaumont-porcien

Konrad von Biberegg - Bischof von Chur, Mitstifter von Kloster Roggenburg: Untersuchungen zum genealogischen Zusammenhang der Herrschaften Biberegg-Roggenburg und Neuffen - Manhalter, Ralph (Der Heimatfreund: Verein Heimatpflege Illertissen und Umgebung e.V, 2019)
Keywords: roggenburg

Peter Abelard, Anselm of Havelberg, and Nicholas of Cusa - Mews, Constant J. (Inventing Modernity in Medieval European Thought ca. 1100-ca. 1550, 2019)
Keywords: 👤 anselm of havelberg

Chartes et documents de l'ancienne abbaye de Fontaine-André - Meyer, Dominique A. (Dominique A. Meyer, 2019)
Keywords: fontaine-andré

Bellpuig: de monestir a marquesat. Fonts, problemàtica i interrogants històrics - Muntaner, Antonio Picazo (De Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà, 2019)
Section: De Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà
Keywords: bellpuig de las avellanes

Bauhistorische Forschungen in den Prämonstratenserklöstern Veßra und Trostadt, Lkr. Hildburghausen - Nitz, Thomas (Die Grafschaft Henneberg und ihre Klöster, 2019)
Keywords: trostadt; veßra

Violence in European medieval monasteries: Skeletal trauma in Teplá monastery (Czech Republic) - Pankowská, Anna; Galeta, Patrik; Uhlík Spěváčková, Petra; Nováček, Karel (International Journal of Osteoarchaeology, 2019)
Medieval monasteries often went beyond their religious mission and developed into economic, social, and educational centres. These were not spared from violent attack on the part of the gentry. The defence of such monasteries is, however, a poorly investigated area in bioarchaeological studies. A recently excavated skeletal sample found in front of the western gate of the Abbey Church at the Teplá monastery (Czech Republic) dated between the 13th and 15th century AD provides us a unique opportunity to fill this gap. The analysis of skeletal trauma reveals that 13 out of 30 individuals exhibited trauma, of which 69% were confidently related to violence. All individuals with injuries were males, and half of them were younger than 30 years of age. The presence of ante-mortem injuries indicates that males likely had previous combat experience, were successfully treated, and their bodies were buried with respect and care. The most probable explanation of our findings is that the individuals were a group of clients who were tasked with the defence of the Teplá monastery. Other, less likely explanations assume that individuals were laity, monastery benefactors, and/or canons killed during several different violent attacks directed at the monastery.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/oa.2804
Keywords: teplá

Introducció. Del Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà - Roig, Albert Cassanyes; Puigserver, Pere Fullana (De Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà, 2019)
Section: De Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà
Keywords: bellpuig de artá; bellpuig de las avellanes

Les fonts per a l'estudi del monestir de les Avellanes - Roigé, Robert Porta i (De Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà, 2019)
Section: De Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà
Keywords: bellpuig de las avellanes

Kilka uwag o historii klasztoru w Opolu-Czarnowasach - Sadowski, Piotr (Opolskie Studia Administracyjno-Prawne, 2019)
OCLC: 1242190039
Keywords: czarnowąsy

El particularismo de las fábricas premonstratenses hispanas en la Edad Media. Una revisión necesaria: balance y nuevas aportaciones - Sanz, Maria Teresa López de Guereño (De Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà, 2019)
Section: De Bellpuig a Bellpuig: els premonstratesos, de les Avellanes a Artà
Keywords: 🇪🇸 spain (general)

Zur Geschichte Westfalens und der ehemaligen Prämonstratenserklöster in der Stadt Arnsberg - Schmalor, Hermann-Josef (Freundeskreis Oelinghausen e.V., 2019)
Keywords: wedinghausen

Krzyż i chwała : błogosławiona Bronisława i Konwent Panien Norbertanek na Zwierzyńcu w Krakowie = The cross and glory : blessed Bronislava and Norbertine Canonesses Convent in Zwierzyniec, Cracow - Stefaniak, Piotr (Księgarnia św. Jacka, 2019)
Keywords: zwierzyniec; 👤 bronislava of kamień

Drei Augustinus-Biographien des XII. Jahrhunderts: Ivo von Chartres, Rupert von Deutz, Philipp von Harvengt - Stiene, Heinz Erich (Hiersemann Verlag, 2019)
Keywords: 👤 philip of harvengt

Neugierde, diebische Absicht oder irregeleitete Frömmigkeit?: die Reliquie im Tumbengrab der seligen Gertrud von Altenberg und deren Beschädigung um das Jahr 1921 - Sturm, Holger (Nassauische Annalen, 2019)
Keywords: altenberg

Chef d'oeuvre en péril: le sauvetage de la Grange de Durance et sa mise en valeur - Trézéguet, Jean-Louis (Revue de l'Agenais, 2019)
Keywords: durance

Les peintures murales de l'église de la Grange de Durance: un ensemble exceptionnel - Trézéguet, Jean-Louis (Revue de l'Agenais, 2019)
Keywords: durance

Monument en péril: le sauvetage du prieuré de la Grange de Durance et sa mise en valeur - Trézéguet, Jean-Louis (Revue de l'Agenais, 2019)
Keywords: durance

Hroznata a úřad probošta v Teplé - Trnka, Pavel (Minulostí Západočeského kraje, 2019)
[Hroznata and office of provost of Teplá]
Keywords: teplá; 👤 hroznata of bohemia

Vztah Chotěšova a Teplé na konci středověku - Trnka, Pavel (Minulostí Západočeského kraje, 2019)
[The relation between the monasteries of Chotěšov and Teplá at the end of the Middle Ages]
Keywords: chotěšov; teplá

Gratteri, Chiesa di S. Giorgio. L'indagine archeologica - Tullio, Amedeo (Arte e storia delle Madonie. Studi per Nico Marino, 2019)
Keywords: gratteri

Gejaagd door de wind. Premonstratenzers en windmolens in de Lage Landen - Van den Branden, Walter (Abdijmolens. Natuurkracht ten dienste van norbertijnen en norbertinessen, 2019)
Pages: 17-28
Keywords: 🇳🇱 netherlands (general)

De abdij van Park en haar abdijdomein, van Haspengouw tot Noord-Brabant - Van Lani, Stefan (Premonstratenzers en premonstratenzerinnen in Brabant, 2019)
Pages: 38-48
Keywords: park

De abdij van Park in het kaartboek van 1665 - Van Lani, Stefan (Ex abundantia cordis. Vriendenboek Mark Derez, 2019)
Pages: 41-42
Keywords: park

De orgelgeschiedenis van de premonstratenzerabdij van Averbode ca. 1434-2001. Zes eeuwen orgelbouwkunst in Brabant. - Van Osta, J. (Katholieke Universiteit Leuven, 2019)
In the musicology of the Netherlands, the history of organ construction has its own place. For the Southern Netherlands, the organ history of the abbey of Averbode is particulary interesting. The size of the preserved old documents or the archive pieces go back to the fifteenth century. Other churches or abbeys also have valuable information, but it is often fragmented. Not only the size of the archives is important, but also the continuity. A chronological insight is given into a quasi-continuous organ history from the beginning of the fifteenth century until today. Information can be found about the late Gothic instrument, the Renaissance organ and its renovations to a Baroque organ and the new Rococo organ. After the period of the French Revolution, there is the transition from the classical to the romantic period. The building of the monumental romantic organ is a lasting reminder of this evolution. The present new Baroque organ illustrates the evolution of organ construction in the twentieth century. Both in older works and in more recent literature, the organ history of Averbode was the theme of several scientific publications. However, some of them restrict themselves to a fragmentary edition of archive pieces[1], or simply mention some instruments.[2] The sources are not further analysed or investigated within a broader organological context. Other researchers interpreted the sources from an obsolete and idealized romantic sound idiom. In that sense, there was almost no attention payed to the specific development of the organ type in the Southern Netherlands from the late Gothic to the Rococo period.[3] Yet other historians studied the individual instruments from the published archives, but they did not explain the link between the successive organs, their alterations and the evolution of the changing dispositions.[4] The present investigation wants to demonstrate that the publication of a synthesis of the organ history in Averbode — which has hitherto been lacking — is a valuable tool for the organological research of the Southern Netherlands and in particular of Brabant. The dissertation is structured chronologically. In addition to the discussion of the well-known and new archive pieces, the recent literature about organ building and organ builders working in Averbode, is critically discussed. The study begins with the earliest mentions of organs in the fifteenth and early sixteenth century. Subsequently the late Gothic instrument of Willem Boets van Heyst is discussed. The research focuses further on the activities of master Anthonis Toers and the specific developments of organ culture in the mid-sixteenth century. The organ of master Gielis Brebos of 1562 is a highlight of the sixteenth century organ history. The repairs, renovation, restoration and new construction by Martin Posselius, Jan Dillingen and Jan van Weert precede the in 1662 new built organ of Jan Dekens. Despite repairs and maintenance by various organ builders, the Jan Dekens organ is sold at the end of the eighteenth century. Averbode then asked Guillaume Robustelly to build a completely new instrument. Unfortunately, this remarkable instrument has only functioned during a short period. It is sold in the late days of the French time. After the reestablishment of the abbey in 1834, Arnold Graindorge builds a rather small instrument for the abbey church. However, this is replaced fairly quickly by a solid, romantic organ by Hippolyte Loret. This instrument has been preserved in an almost unspoilt state until today. However, it is waiting for a thorough restoration. In the quest for a new Baroque sound, Bernard Pels built a choir organ in 1979. As the Loret instrument became unplayable at the end of the twentieth century, the abbey chose to build a new transept organ by Léon III Verschueren in 2001. This Organ is the provisional endpoint of the rich organ history of the monastery of Averbode. In the second part of this study, all mentioned archives with regard to the instruments and their builders are published, with corrections where necessary. They are supplemented with other published transcriptions if they particularly concern the history of Averbode. Numerous newly discovered archive pieces of Averbode are published. They represent an important addition to what was already known, in particular concerning the design of the Renaissance organ (1530-1540), the difficulties in placing the Robustelly organ (1770-1773) and the ambiguities about the transitional instrument of Arnold Graindorge (1834-1844). The archives concerning the romantic instrument of Hippolyte Loret (1852-1859) have so far not been published. The construction history of the more recent instruments (1978, 1982 and 2001) are situated within the search for the authentic organ sound of mechanical organs with respect to the scientific research of ancient instruments. In supplementary annexes we offer a list of the main organists and composers connected to the abbey church of Averbode, the use of the organ in the premonstratensian liturgy, the relationship of Flor Peeters with the monastery of Averbode and the Organ Congresses which took place in the abbey. The registers on persons (organ builders), places, archives and authors want to be a service to the further critical examination of the organ culture in the Southern Netherlands. In this sense, this dissertation situates itself in the tradition of similar music historical monographs on the art of organ building in a particular church or location, or on a dynasty of organ builders that transcend local historiography[5]. [1] Norbertine and historian Placied Lefevre published in the years 1930 a lot of source material about the art history of Averbode with the fragmentary mentions of the organ history. P. Lefevre, Textes concernant l'histoire artistique de l'abbaye d'AverbodeIn Revue Belge d'Archéologie et d'Histoire de l'Art, 1935, 45-58. P. Lefevre, Textes concernant l'histoire artistique de l'abbaye d'Averbode aux Xviie Et XviiiE SièclesIn Revue Belge d'Archéologie et d'Histoire de l'Art, 1936, 151-176; 331-350 En 1937, 57-76. [2] E. Ganbat, Historique de la facture et des facteurs d'orgue avec la nomenclature des principales orgues placées dans les Pays-Bas et dans les provinces flamandes de la Belgique, suivi de la Galerie biographique d'organistes célèbres et d'une Notice sur les maître de Chapelle Et organistes de la cathédrale d'Anvers, Anvers, 1865, Avec une introduction et une nomenclature par Ghislain PotvliegHey, Frits Kaino, Amsterdam, 1972; J. Kreps, The Organ in The, Villagracia, 1933. [3] F. Van Der Mueren, Het orgel in de Nederlanden. Verre traditie - gebruik in de kerkelijke diensten - meubel - decoratieve houtversiering - orgelregistratie - orgelliteratuur - parallel-vergelijking tusschen al deze bestanddeelen, Leuven, 1931. [4] Jan (Trudo) Gerits (ex-confrater) published in the years 1960 and 1970 numerous articles on Averbodes organ history without however writing a monograph and clarifying the interconnections. [5] Good examples in Belgium and the Netherlands are: Persoons 1981; Lemmens 1985; van Nieuwkoop 1988; van Biezen 1995.
Keywords: averbode

Ninove. Abbaye prémontrée flamande à la frontière du Brabant, entre ville et campagne, à l’ombre de la frontière linguistique - Vande Winkel, Georges (Circarie de Gascogne. Les prémontrés et la frontière. Actes officiels du 44e colloque du Centre d’Études et de Recherches Prémontrées. Pays basque - 2018, 2019)
Pages: 185-189
Keywords: ninove

Staalkaart van het molenpatrimonium van Norbertijnen en Norbertinessen in België en Nederland - Verpaalen, John (Abdijmolens. Natuurkracht ten dienste van norbertijnen en norbertinessen, 2019)
Pages: 37-47
Keywords: 🇧🇪 belgium (general); 🇳🇱 netherlands (general)

Stredoveké notované fragmenty zo Slovenského národného archívu, Fond Hodnoverného miesta Konventu premonštrátov v Lelese - Veselovská, Eva (Historický časopis, 2019)
Keywords: leles; 🎶 musicology

Chronik der Stadt Usedom und ihres Prämonstratenser-Klosters Grobe - Voth, Roland; Ehrig, Gottfried; Putzke, Erwin (Roland Voth, 2019)
Google-Books-ID: QYE7zQEACAAJ
Keywords: grobe

Das Prämonstratenserstifl Weißenau. Geschichte, Erinnerung und Förderer im Spiegel der Acta sancti Petri in Augia - Waldschütz, Johannes (Von den Welfen zu den Staufern: Der Tod Welfs VII. 1167 und die Grundlegung Oberschwabens im Mittelalter, 2019)
Keywords: weissenau

À Saint-Tricat, l’église de Saint-Nicaise unique témoin d’un passé agité (La Voix du Nord, 2018)
Keywords: saint-tricat

L’Abbazia di S. Pietro di Licusati, antico cenobio basiliano - Attanasio, Francesco (Sapri roui nata, 2018)
Keywords: camerota

Äbte und Chorherren des Prämonstratenserstifts Steinfeld, Teil 1 - Joester, Ingrid (Akademie der Wissenschaften zu Göttingen, 2018)
Das Kloster Steinfeld in der Eifel im Erzbistum Köln wurde im 10. oder 11. Jahrhundert gegründet und schloss sich zwischen 1136 und 1142 dem Prämonstratenserorden an. Steinfeld galt als Tochterkloster von Prémontré und nahm schon bald eine führende Stellung in der Zirkarie Westfalen ein. Die Bedeutung Steinfelds kommt darin zum Ausdruck, dass die Äbte im 15. und 16. Jahrhundert vom Generalkapitel umfangreiche Aufträge zu Visitation und Reform anderer Ordensstifte erhielten und durchführten und dass sie vom 17. Jahrhundert bis zur Aufhebung im Jahr 1802 als Generalvikare des Abtes von Prémontré in den Zirkarien Westfalen, Ilfeld und Wadgassen mit weitreichenden Vollmachten fungierten. Der hier publizierte Personenkatalog liefert in zwei Teilbänden Informationen zum Personal des Konvents. Die Viten der Pröpste und Äbte sind im ersten Teil abgehandelt, der zweite Teil enthält die biographischen Informationen zu den Chorherren des Stifts. Die Besitzungen des Prämonstratenserstifts Steinfeld sind separat im dritten Supplementband der Germania Sacra aufgearbeitet.
Google-Books-ID: PiFrDwAAQBAJ
Keywords: steinfeld

Äbte und Chorherren des Prämonstratenserstifts Steinfeld, Teil 2 - Joester, Ingrid (Akademie der Wissenschaften zu Göttingen, 2018)
Das Kloster Steinfeld in der Eifel im Erzbistum Köln wurde im 10. oder 11. Jahrhundert gegründet und schloss sich zwischen 1136 und 1142 dem Prämonstratenserorden an. Steinfeld galt als Tochterkloster von Prémontré und nahm schon bald eine führende Stellung in der Zirkarie Westfalen ein. Die Bedeutung Steinfelds kommt darin zum Ausdruck, dass die Äbte im 15. und 16. Jahrhundert vom Generalkapitel umfangreiche Aufträge zu Visitation und Reform anderer Ordensstifte erhielten und durchführten und dass sie vom 17. Jahrhundert bis zur Aufhebung im Jahr 1802 als Generalvikare des Abtes von Prémontré in den Zirkarien Westfalen, Ilfeld und Wadgassen mit weitreichenden Vollmachten fungierten. Der hier publizierte Personenkatalog liefert in zwei Teilbänden Informationen zum Personal des Konvents. Die Viten der Pröpste und Äbte sind im ersten Teil abgehandelt, der zweite Teil enthält die biographischen Informationen zu den Chorherren des Stifts. Die Besitzungen des Prämonstratenserstifts Steinfeld sind separat im dritten Supplementband der Germania Sacra aufgearbeitet.
Google-Books-ID: PiFrDwAAQBAJ
Keywords: steinfeld

Der Besitz des Prämonstratenserstifts Steinfeld - Joester, Ingrid (Akademie der Wissenschaften zu Göttingen, 2018)
Das Kloster Steinfeld in der Eifel im Erzbistum Köln wurde im 10. oder 11. Jahrhundert gegründet und schloss sich zwischen 1136 und 1142 dem Prämonstratenserorden an. Steinfeld galt als Tochterkloster von Prémontré und nahm schon bald eine führende Stellung in der Zirkarie Westfalen ein. Die Bedeutung Steinfelds kommt darin zum Ausdruck, dass die Äbte im 15. und 16. Jahrhundert vom Generalkapitel umfangreiche Aufträge zu Visitation und Reform anderer Ordensstifte erhielten und durchführten und dass sie vom 17. Jahrhundert bis zur Aufhebung im Jahr 1802 als Generalvikare des Abtes von Prémontré in den Zirkarien Westfalen, Ilfeld und Wadgassen mit weitreichenden Vollmachten fungierten. Der hier publizierte Personenkatalog liefert in zwei Teilbänden Informationen zum Personal des Konvents. Die Viten der Pröpste und Äbte sind im ersten Teil abgehandelt, der zweite Teil enthält die biographischen Informationen zu den Chorherren des Stifts. Die Besitzungen des Prämonstratenserstifts Steinfeld sind separat im dritten Supplementband der Germania Sacra aufgearbeitet.
Google-Books-ID: PiFrDwAAQBAJ
Keywords: steinfeld

Coverham Abbey - one of North Yorkshire's ancient gems - Lloyd, Chris (Darlington and Stockton Times, 2018)
Keywords: coverham

The Arnstein Bible: a grand monastic Bible - Doyle, Kathleen (British Library Medieval Manuscripts Blog, 2018)
Keywords: arnstein

The Tongerlo Apocalypse in the 16th and 17th Centuries - Kidd, Peter (Medieval Manuscripts Provenance, 2018)
Keywords: tongerlo

A Previously Unrecognised Tongerlo Provenance - Kidd, Peter (Medieval Manuscripts Provenance, 2018)
Keywords: tongerlo

Historie van Altforst: boerderijen (Kwekkertje: Dorpsblaadje van Altforst, 2018)
Keywords: altforst

L’ancien monastère Ste-Marguerite de Crécy à Brécy-Brières - Grossin, Emmanuel (Le Curieux Vouzinois, 2018)
Keywords: crécy

More stained glass fragments from Park Abbey (Leuven) discovered in Quebec - LaBrecque, Claire (Vidimus, 2018)
Keywords: park

Essai sur le patrimoine temporel de l'abbaye d'Arthous (XIIe-XVe s.) - Abadie, Stéphane (Bulletin de la Société de Borda, 2018)
Keywords: arthous

La mobilité d'un abbé au XVe siècle. Itinéraires et liens de communications de Thierry de Tuldel - Appelmans, Janick (Mobilité et stabilité chez les Prémontrés. Guerres, catastrophes et calamités. Actes officiels des 38e et 39e colloques du Centre d'Études et de Recherches Prémontrées. Amiens, 2012 - Troyes 2013, 2018)
Keywords: park

Sœurs et pères en détresse: les prémontrés des anciens Pays-Bas face aux guerres, catastrophes et calamités - Appelmans, Janick (Mobilité et stabilité chez les Prémontrés. Guerres, catastrophes et calamités. Actes officiels des 38e et 39e colloques du Centre d'Études et de Recherches Prémontrées. Amiens, 2012 - Troyes 2013, 2018)
Keywords: 🇳🇱 netherlands (general)

Kísérlet a bárdudvarnok-szentbenedeki premontrei prépostság környezeti rekonstrukciójára - Aradi, Csilla M.; Molnár, István (Genius loci – Laszlovszky 60, 2018)
[An attempt to reconstruct the environment of the Premonstratensian abbey of Bárdudvarnok-Szentbenedek]
Num Pages: 407 Pp.
Keywords: kaposfő

Beauport. L'abbaye prémontrée de Bretagne. Histoires et vie quotidienne - Ballini, Annie-Claude (Association des amis de l'abbaye de Beauport, 2018)
Keywords: beauport

The Abbey of Meszes: New Insights on the Site Location - Bencze, Ünige (Genius loci – Laszlovszky 60, 2018)
Keywords: meszes

Das Prämonstratenserkloster Langen zwischen dem 14. und 16. Jahrhundert. 3: Die versuchte Übertragung von 1434: Akteure und Konsequenzen - Bley, Matthias (Emder Jahrbuch, 2018)
Keywords: langen

Die Bibliothek des Prämonstratenser-Stifts Heiligenberg - Bösche, Hartmut (Von Wernigerode nach Heiligenberg: Kloster Heiligenberg/Mons Sanctae Mariae: erschienen anlässlich der 800-Jahrfeier im Auftrag der Gemeinde Bruchhausen-Vilsen, 2018)
Keywords: heiligenberg

San Norberto en algunas estampas flamencas del siglo XVII - Calvo Portela, Juan Isaac (Espacio, Tiempo y Forma. Serie VII, Historia del Arte, 2018)
Keywords: 👤 norbert of xanten

Uit het Regionaal Archief Nijmegen. Het ‘gevluchte’ archief van het nonnenklooster van de heilige Maria Magdalena te Nijmegen (1250-1562) - Camps, Rob (Jaarboek Numaga, 2018)
Keywords: nijmegen

Problem genezy formalnej prezbiterium w krakowskim kościele Norbertanek na Zwierzyńcu - Cierpisz, Szymon (Rocznik krakowski Towarzystwo Miłośników Historii i Zabytków Krakowa, 2018)
Keywords: zwierzyniec

Weißenau, Prämonstratenserkloster, Teil 3: Akten: 1152-1809 - Clauß, Susanne; Zausch, Marion; Löffler, Gabriele (Landesarchiv Baden-Württemberg, 2018)
Keywords: weissenau

Premonstratensian Settlement in the Czech Lands and Ireland, 1142-1250 - Clyne, Miriam (Journal of Medieval Monastic Studies, 2018)
The settlement of Premonstratensian canons and nuns is addressed against the backdrop of the political and ecclesiastical settings of the Czech Lands and Ireland. Colonization was accomplished through political alliances, religious circles, and interaction with the central authority at Prémontré during transitional phases of diocesan reform in Bohemia, Moravia, and Connacht, and Anglo-Norman acculturation in Ulster. The letters of the father abbot at Steinfeld and the abbots of Prémontré indicate their concerns for the future prospects of the distant monasteries, the needs of new communities, and how they reacted in different ways to maintain standards of uniformity and discipline.
Keywords: 🇨🇿 czechia (general); 🇮🇪 ireland (general)

Az ócsai premontrei prépostság régészeti kutatása - Csoltkó, Emese (Micae mediaevales VII. Fiatal történészek dolgozatai a középkori Magyarországról és Európáról, 2018)
The village of Ócsa is situated to the south of Budapest in Pest County. The first mention of the existence of the Premonstratensian provostry is dated to 1234 in the so-called Catalogue of Ninive, which mentions that Ócsa is the filial of the convent of Jászó ( Jasov, Slovakia). The church with three naves and two towers at its western facade was built in the first half of the 13th century. During the construction works there were some modifications in the original plans, as the church was planned with another vaulting section towards at the west, but that was, along with the vaulting of the naves, never finished. Minor reconstruction works can be dated to the Middle Ages; for example wall-paintings and the Gothic pastoforium. The Premonstratensians left Ócsa before the Ottoman occupation period, but as a parish church, it didn’t lose the function which is attested by the 15th century demolition of the rood-screen. The church was used by the Calvinist congregation since 1560. As part of the preparation for the reconstruction works, there was archaeological research between 1986 and 1992 which was led by Juan Cabello. This included a systematic, full-scale excavation in the church and in the churchyard. In the course of the excavation, the monastery building with the one side and three pit houses from the 12th–13th century was found. The surrounding and inside of the church were used as a cemetery. The first reconstruction work was realized in the second half of the 18th century ( József Teleki’s works between 1774 and 1777). In the 18th century the church was damaged by natural disasters like lightning and fire. Thus another renovation was necessary, led by Ottó Tandor (1897–1900). In 1909 Ottó Sztehlo renewed the damaged northern portal. The elevation of the towers of the church was carried out by Ernő Foerk in 1923. Finally, the recent renovation of the church was conducted by Tibor Gál between 1989 and 1995.
Keywords: ócsa

Archeologia a San Cataldo – scavi e scoperte - Cucco, Rosa Maria; Correra, Marco (Notiziario Archeologico 41/2018 della Soprintendenza di Palermo, 2018)
Keywords: terrasini

"He proved to be an inseperable travel companion": Emo of Wittewierum and his Rome journey in 1211-1212 - De Boer, Dick (Gender, Companionship, and Travel: Discourses in Pre-modern and Modern Travel Literature, 2018)
Keywords: bloemhof

De rots van Floreffe en de bouwstenen van de abdij - De Ceukelaire, Marleen (Stenen voor mensen, marmer voor God. Materialen op de rots van Floreffe, 2018)
Keywords: floreffe

Vloeren in de abdij van Floreffe - De Ceukelaire, Marleen (Stenen voor mensen, marmer voor God. Materialen op de rots van Floreffe, 2018)
Keywords: floreffe

Die Prämonstratenser-Abtei von Fontaine-André - De Reynier, C. (Archaologie der Schweiz, 2018)
Keywords: fontaine-andré

De abdij van Floreffe waar de stenen en de dakkappen de weg wijzen naar de middeleeuwen - Doperé, Frans (Stenen voor mensen, marmer voor God. Materialen op de rots van Floreffe, 2018)
Keywords: floreffe

Die Prämonstratenser in Sachsen - Eick, Stefan (Von Wernigerode nach Heiligenberg: Kloster Heiligenberg/Mons Sanctae Mariae: erschienen anlässlich der 800-Jahrfeier im Auftrag der Gemeinde Bruchhausen-Vilsen, 2018)
Keywords: 🇩🇪 germany (general)

Exkurs: Die geistlichen Predigten der Chorherren in Heiligenberg - Eick, Stefan (Von Wernigerode nach Heiligenberg: Kloster Heiligenberg/Mons Sanctae Mariae: erschienen anlässlich der 800-Jahrfeier im Auftrag der Gemeinde Bruchhausen-Vilsen, 2018)
Keywords: heiligenberg

Bestattungen des Stader Klosterfriedhofes St. Georg entdeckt - Finck, Andrea (Archäologie in Niedersachsen, 2018)
Keywords: stade

Szent Euszták és vértanú társai prépostság | Háros-sziget, Budapest XXII. - Galuska, Tünde (A pálos rend építészeti emlékei, 2018)
Keywords: csút

Spätgotische Handwerkergraffiti in der ehemaligen Klosterkirche St. Katharina in Wenau (Kreis Düren) - Heckner, Ulrike (Historische Graffiti als Quellen : Methoden und Perspektiven eines jungen Forschungsbereichs : Beiträge der Konferenz am Institut für Klassische Archäologie der LMU München, 20.-22. April 2017, 2018)
Keywords: wenau

MA-XRF investigation of the Altenberg Retable from 1330 - Hoffmann, P.; Flege, S.; Ensinger, W.; Wolf, F.; Weber, C.; Seeberg, S.; Sander, J.; Schultz, J.; Krekel, C.; Tagle, R.; Wittkopp, A. (X-Ray Spectrometry, 2018)
The Altenberg Retable is one of the most important works of German art from the early 14th century. Composed of a shrine, a Madonna figure, and painted wings, it once adorned the high altar of the convent church in Altenberg/Lahn. The side and rear walls of the shrine were overpainted in 1609. Although conventional methods such as infrared reflectography and X-ray radiography could not reveal the underlying medieval paint layer, we succeeded by conducting μ-X-Ray fluorescent studies. The latter measurements included a handheld spectrometer as well as μ-X-Ray fluorescent large area scanner. Nine sections of the side and rear walls were examined as well as a field on one of the wings (as a reference). In each section, spectra were recorded that comprised about 20 elements ranging from K to Bi. Maps of Ca, Fe, Co, Cu, Zn, As, Hg, and Pb were evaluated and interpreted on the basis of the results of prior color sampling analysis. By superposing several element maps, the original medieval iconographic program with its rows of standing saints could be revealed. With the help of iconographic comparison, these saints could be identified: St. Christopher in the central part of the rear wall, flanked by the 4 female saints Clare, Agnes, Dorothy, and Barbara. On the side walls, the apostles Peter and Paul, as well as the deacons Stephen and Lawrence were depicted. Discussed are not only different scenarios of usage for these images behind the altar but also the limits and possibilities of the measurement technology in this specific application.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/xrs.2829
Keywords: altenberg

Eine hochmittelalterliche Warmluftheizung im Arnsberger Kloster Wedinghausen - Holtfester, Ulrich (Archäologie in Westfalen-Lippe, 2018)
Place: Langenweißbach Publisher: Beier & Beran, 2010-
Keywords: wedinghausen

Les grandes heures de l'Abbaye Royale Notre-Dame d'Abbecourt, Orgeval-Yvelines - Hubert, Jeannine (Association Histoire d'Orgeval, 2018)
OCLC: 1194448278
Keywords: abbecourt

Heiligenbergs Gründung vor dem Hintergrund der Reichsgeschichte in der Zeit um 1218 - Hucker, Bernd Ulrich (Von Wernigerode nach Heiligenberg: Kloster Heiligenberg, Mons Sanctae Mariae : erschienen anlässlich der 800-Jahrfeier im Auftrag der Gemeinde Bruchhausen-Vilsen, 2018)
Keywords: heiligenberg

The Stained Glass Biblia Pauperum Windows of Steinfeld Abbey: Monastic Spirituality, Salvation History and the Theological Imagination - Hyland, William (The Moving Text: Interdisciplinary Perspectives on David Brown and the Bible, 2018)
Keywords: steinfeld

Die Stellung der Abtei Steinfeld im Prämonstratenserorden - Joester, Ingrid (Analecta Praemonstratensia, 2018)
Keywords: steinfeld

St. Nikolaus in Köln-Dünnwald: Pfarrkirche und ehemalige Klosterstiftskirche - Juraschek-Eckstein, Markus (Kunstverlag Josef Fink, 2018)
Keywords: dünnwald

Lateinische Rivalen in Konstantinopel: Anselm von Havelberg und Hugo Eterianus - Kapriev, Georgi (Peeters, 2018)
Keywords: 👤 anselm of havelberg

Les épisodes noirs de la blanche abbaye d'Ardenne - Khedine, Françoise (Actes officiels du 39e colloque du Centre d'études et de recherches prémontrées. Guerres, catastrophes et calamités. Troyes, 2013, 2018)
Keywords: ardenne

Penitential punishment and purgatory: a drama of purification through pain - Kirakosian, Racha (Punishment and Penitential Practices in Medieval German Writing, 2018)
Num Pages: 208 Pp.
Keywords: 👤 christina of hane

Adalékok a jászói Keresztelo Szent János premontrei monostor középkori történelméhez - Kotrusová, Júlia (Micae mediaevales VII. Fiatal történészek dolgozatai a középkori Magyarországról és Európáról, 2018)
The Monastery of St. John the Baptist in Jasov belongs among the oldest Premonstratensian monasteries in modern Slovakia. The circumstances surrounding the arrival of Premonstratensians in Jasov and the year of foundation of the monastery are amongst the most debated problems in the history of the Jasov provostship. The source of these controversies is the fact that the foundation charter was not preserved. The opinions of historians on the foundation of the monastery vary. A number of historians assume that it was founded at the turn of the 12th and 13th centuries, possibly at the beginning of the 13th century. I argue that a charter issued by King Béla IV in 1255 can contribute to clarification of the foundation of the convent. The document re-establishes the originalprivileges of the monastery. The earliest references to Premonstratensian monasteries in Hungary is preserved in the Ninive catalogue, specifically in its second registry. The properties of the monastery also raise a number of questions. The institution owned properties of high value in the Middle Ages. The oldest mention of their estate possession dates back to the above mentioned charter issued by King Béla IV in 1255. The lands mentioned in the charter were compact. Besides the original property described by the charter, in 1255 lands were provided for the monastery that Béla acquired from Duke Coloman. During the medieval and early modern period Jasov was a central property of the Jasov provostship. Due to its location and its vicinity to the monastery, it became more and more prominent in the 13th century, when it gained urban privileges, most importantly market rights.
Keywords: jasov

Kláštor premonštrátov v Kláštore pod Znievom: stavebný vývoj v stredoveku - Kürthy, Luboš (Architektúra kláštorov a rehoľných domov na Slovensku : dejiny a pamiatková ochrana, 2018)
Keywords: klaštor pod znievom

Norbertanki płockie - Kuźniewska, Zofia H. (Rocznik Towarzystwa Naukowego Płockiego, 2018)
Keywords: płock

Krypta unter dem Turm der Stiftskirche in Flaesheim? - Laakmann, Heiner (Halterner Jahrbuch, 2018)
Keywords: flaesheim

Alleen God en de zon: negen eeuwen Hof te Kattem - Liedekerke, Luc Van (Luc Van Liedekerke, 2018)
Google-Books-ID: TudruwEACAAJ
Keywords: kattem

Die ehemalige Klosterkirche in Rumbeck bei Arnsberg, eine frühe Hallenkirche in Westfalen - Lobbedey, Uwe (Gotik : der Paderborner Dom und die Baukultur des 13. Jahrhunderts in Europa : Katalog zur Ausstellung im Erzbischöflichen Diözesanmuseum Paderborn, 2018)
Keywords: rumbeck

Floreffe sur le chemin de saint Norbert - Lombet, Jean (Stenen voor mensen, marmer voor God. Materialen op de rots van Floreffe, 2018)
Keywords: floreffe

Von Stiftern, Fälschern und Forschern. Die hochmittelalterlichen Urkunden für Cappenberg und ihre Bedeutung für das Stift und seine Geschichte - Lubich, Gerhard (... sich einen Kopf machen. Cappenberger Vorträge zum Mittelalter, 2018)
Keywords: cappenberg

The deeds of Count Ludwig of Arnstein (d. 1185) - Lyon, Jonathan R. (Noble Society : Five lives from twelfth-century Germany, 2018)
Keywords: arnstein

La fondation de l'abbaye de Beauport par le prince de Bretagne, Alain de Goëlo (1202) - Morvan, Frédéric (Église, religion, croyances du Moyen Âge à nos jours, 2018)
Keywords: beauport

Voneinander gelernt? Ein vergleichender Blick auf die Bildprogramme der Klosterbibliotheken von Wiblingen, St. Peter auf dem Schwarzwald, Bad Schussenried und ein Exkurs zu Weissenau - Mühleisen, Hans-Otto (Herrschaftswissen Bbibliotheks- und Archivbauten im Alten Reich, 2018)
Keywords: schussenried

The Leake Cartulary and the Derbyshire Estates of Welbeck Abbey - Munford, Anthony P.; Hopkinson, Aileen M. (Derbyshire Record Society, 2018)
Keywords: welbeck

Spätmittelalterliche Frömmigkeit im Prämonstratenserkloster Gramzow: eine Seelenmessenstiftung aus dem Jahr 1500 - Neitmann, Klaus (Angermünder Heimatkalender, 2018)
Keywords: gramzow

2018:084 - Abbots Road, Whiteabbey, Antrim - O'Regan, Christine (Excavations.ie, 2018)
Keywords: whiteabbey

Cutting their cloth: the Scottish Premonstratensians, c. 1150 to c. 1350 - Oram, Richard (Places of worship in Britain and Ireland, 1150-1350, 2018)
Keywords: 🇬🇧 great britain (general)

Spory cystersów sulejowskich i norbertanów witowskich w XIII i XIV w - Parol, Jakub (Nasza Przeszłość : studia z dziejów Kościoła i kultury katolickiej w Polsce, 2018)
Keywords: witów

Kardinalsunterschriften als Fälschungsindiz: das Privileg Eugens III. für das Stift Rot an der Rot (JL 9618) und seine Vorlagen - Petersen, Stefan (Archiv für Diplomatik, 2018)
Keywords: rot an der rot

San Pietro di Acqua Alta - Piselli, Daniele (Comunità laica e religiosa di Montegabbione: chiese ed abazie nei sec. XII-XIV, 2018)
Keywords: aqualta

Scheda: Kloster - Rittergut - Landwirtschaftlicher Betrieb. Erstmalige Erwähnung schon in einer Urkunde aus dem Jahr 1147 - Platte, Hartmut (Heimatkalender des Kreises Soest, 2018)
Keywords: scheda

L'abbaye Notre-Dame et Saint-Jean-Baptiste de Basse-Fontaine [commune de Brienne-la-Vieille]. L'abbaye Notre-Dame de Beaulieu [commune de Trannes] - Plouvier, Martine (Actes officiels du 39e colloque du Centre d'études et de recherches prémontrées. Guerres, catastrophes et calamités. Troyes, 2013, 2018)
Keywords: basse fontaine; beaulieu

“Copy destroyed”: de lotgevallen van een verdwenen incunabel - Popkema, Anne Tjerk; De Vries, Herre (De Gulden Passer, 2018)
[“Copy destroyed”: the fate of a missing incunabula]
Keywords: averbode

Sapientes Nostri. I Dialogi (O Antikeimenon) di Anselmo di Havelberg e la circolazione dei testi di Gregorio di Nazianzo nell'Europa latina del XII secolo - Saccenti, Riccardo (Revue d'histoire ecclésiastique, 2018)
Keywords: 👤 anselm of havelberg

Stiftskirche Cappenberg - Saeger, Klaus (Schnell & Steiner, 2018)
Keywords: cappenberg

The Translation of St. Norbert’s Remains to Prague in 1627: True account of a letter sent by St. Michael’s of Antwerp to the Canons Regular of the Monastery of Saint Norbert of Madrid - Sands, Rosemary (Communicator: The English Speaking Circary of the Order of Prémontré, 2018)
Keywords: 👤 norbert of xanten

Geschiedenis van de twee watermolens en van de houten korenwindmolen van de abdij van Ninove te Ninove - Souffreau, Georges Léon (Georges L. Souffreau, 2018)
Keywords: ninove

Zabytkowe hafty norbertanek żukowskich. Stan badań po czterdziestu latach - Stanilewicz, Karolina (Folia Historica Cracoviensia, 2018)
Publisher: Wydawnictwo Naukowe Uniwersytetu Papieskiego Jana Pawła II w Krakowie
Keywords: żukowo

Prämonstratenser-Klöster Nova Rise und Geras im Vergleich von der Gründung bis zur Gegenwart - Štroblová, Lada (Masaryk University, 2018)
Keywords: geras; nová říše

Gyulafirátót, avagy a rendi építészeti hagyományok átjárhatósága - Szakács, Béla Zsolt (Genius Loci. Laszlovszky 60, 2018)
(Gyulafirátót or the permeability of the monastic architectural traditions)
Keywords: gyulafirátót

Liber ordinarius klasztoru premonstratensów na Ołbinie. Przyczynek do dalszych badań nad rękopisem - Szukiel, Piotr (Od Benedyktynów i Premonstratensów do Salezjanów: dzieje kościoła i parafii Św. Michała Archanioła na wrocławskim Ołbinie : materiały konferencji naukowej z okazji 70-lecia obecności salezjanów na wrocławskim Ołbinie (Wrocław, 28-29 kwietnia 2017 r.), 2018)
Keywords: wrocław

Autels et cheminées marbrières dans l’abbaye de Floreffe - Tourneur, Francis (Stenen voor mensen, marmer voor God. Materialen op de rots van Floreffe, 2018)
Keywords: floreffe

A levéltárak titkos élete. A Csornai Premontrei Apátság levéltárainak évszázadai - Vajk, Ádám (Soproni Szemle: Helytörténeti folyóirat, 2018)
[The secret life of archives. Centuries of the archives of the Premonstratensian abbey of Csorna]
Keywords: csorna

Geschreven bronnen over de bouw van de eerste Ninoofse abdijkerk - Van De Perre, Dirk (Het Land van Aalst, 2018)
Keywords: ninove

Het kaartenarchief van de Ninoofse abdij herbekeken - Van De Perre, Dirk (Het Land van Aalst, 2018)
Keywords: ninove

La position des abbayes prémontrées, en particulier celle de Ninove, pendant la guerre civile et religieuse dans les Pays-Bas (1578-1587) - Van De Perre, Dirk (Mobilité et stabilité chez les Prémontrés. Guerres, catastrophes et calamités. Actes officiels des 38e et 39e colloques du Centre d'Études et de Recherches Prémontrées. Amiens, 2012 - Troyes 2013, 2018)
Keywords: ninove

Litomyšlské biskupství po roce 1421 - Večeře, Vojtěch (Studia Medievalia Bohemica, 2018)
Keywords: litomyšl

Un scribe au travail pour deux abbayes: Gérard de Cologne, chanoine prémontré (fin XIIIe siècle), à travers ses livres d’archives - Verpeaux, Nathalie (Scriptorium, 2018)
Keywords: 📚 premonstratensian (general)

Kloster Reichenstein, Monschau - Fortschreibung der Denkmaleintragung und Ergänzung der Außenanlagen - Walter, Kerstin (Jahrbuch der rheinischen Denkmalpflege, 2018)
Keywords: reichenstein

"Ducalis Parthenon Domûs Dei" : uwagi o architekturze i wymowie ideowej norbertańskiego kompleksu klasztornego w Czarnowąsach - Wojtyla, Arkadiusz (Sztuka dawnego Opola, 2018)
OCLC: 1242209532
Keywords: czarnowąsy

Die Prämonstratenserstifte Ober- und Nieder-Ilbenstadt - Wolf, Jürgen Rainer (De Gruyter, 2018)
Keywords: ilbenstadt; niederilbenstadt

Henry Zdik, bishop of Olomouc and Premonstratensian - Wolverton, Lisa Ann (Portraits of Medieval Eastern Europe, 900-1400, 2018)
Keywords: 📚 premonstratensian (general)

Z histórie opevneného kláštora v Bzovíku - Žažová, Henrieta; Maliniak, Pavol; Kožiak, Rastislav (OZ Pod hradom, 2018)
Keywords: bzovík

Premonstrátský klášter a kostel sv. Jiljí v Milevsku - Zelenková, Pavla (Katolická teologická fakulta Univerzity Karlovy v Praze, 2018)
OCLC: 1039819939
Keywords: milevsko

Terrasini, a due anni dal restauro la chiesa di San Cataldo è una discarica - Catalano, Maria Carola (Palermo Today, 2017)
Keywords: terrasini

La parole à l’archéologie - Labeyriotte, Maïté (Sud Ouest, 2017)
Keywords: arthous

Monestir de Santa Maria de Bellpuig d'Artà - Esteva Rosselló, Antoni (Revista Bellpuig, 2017)
Keywords: bellpuig de artá

St Mary the Virgin, Blanchland: An Archaeological Assessment - Ryder, Peter F. (2017)
Keywords: blanchland

“Dwellers in Shadows” & Abbatial Jerusalem: Reformed Monastic Ideas by the Third Crusade in the Sermons of Garnerius of Rochefort and Adam the Scot - Upton, Todd (Quidditas, 2017)
Keywords: 👤 adam of dryburgh

Kirchenführer St. Jakobi Coesfeld (St. Lamberti Gemeinde, 2017)
Keywords: coesfeld (st. jakobi)

Steine erzählen: Führer durch die Lambertikirche (Coesfeld, 2017)
Keywords: coesfeld (st. lamberti)

Torre Abbey (2017)
Keywords: torre

"[qu'] ilz facent bon et brief droit". Les prémontrés brabançons et le recours à la justice diocésaine, ducale et papale au XVe siècle - Appelmans, Janick (Grandes et petites figures de l'ordre de Prémontré. Les prémontrés et la justice. Actes officiels des 36e et 37e colloques du Centre d'Études et de Recherches Prémontrées. Auvergne, 2010 - Normandie, 2011, 2017)
Keywords: 🇫🇷 france (general)

Charity, action and contemplation : twelfth-century Cistercian and Premonstratensian teachings - Bandeniece, Beatrise (University of St Andrews, 2017)
Keywords: 📚 premonstratensian (general)

Der Dom zu Riga - aktuelle kunsthistorische Forschungsergebnisse - Bergholde-Wolf, Agnese (Die maritime Stadt: Hafenstädte an der Ostsee vom Mittelalter bis in die Gegenwart: Miasto nad morzem - miasta portowe nad Baltykiem od sredniowiecza do wspolczesnosci ; Beiträge der 21. Tagung des Arbeitskreises deutscher und polnischer Kunsthistoriker und Denkmalpfleger in Gdansk 18-21 September 2013; Materialy 21 Konferencji Grupy Roboczej Polskich i Niemieckich Historyków Sztuki i Konserwatorów Zabytkow w Gdansku 18-21 wrzesnia 2013, 2017)
Keywords: rīga

Das Prämonstratenserinnenkloster in Nieder-Ilbenstadt: Überlegungen zu seiner Gründung und Beobchtungen zur Baugeschichte - Bewerunge, Norbert (Archiv für mittelrheinische Kirchengeschichte, 2017)
Keywords: niederilbenstadt

Das Prämonstratenserkloster Langen zwischen dem 14. und 16. Jahrhundert, 2: zur inneren Struktur des Konvents: Doppel-, Männer- oder Frauenkloster? - Bley, Matthias (Emder Jahrbuch, 2017)
Keywords: langen

Promeny pecetí moravských premonstrátských opatu v pozdním stredoveku a raném novoveku - Bolom-Kotari, Martina (Mikulovské kolejní kabinety pomocných ved historických I.: sborník z mezinárodní konference Z pomocných ved historických konané 6. listopadu 2013 v Mikulove, 2017)
Keywords: 🇨🇿 czechia (general)

L'abbazia normanna di San Giorgio a Gratteri. La prima fondazione cistercense nel Regno di Sicilia? - Capitummino, Francesco (Convivium. Exchanges and interactions, 2017)
Keywords: gratteri

Au pays de Saint Gilbert, Aubeterre et Neuffonts - Carré, Philippe (Grandes et petites figures de l'ordre de Prémontré. Les prémontrés et la justice. Actes officiels des 36e et 37e colloques du Centre d'Études et de Recherches Prémontrées. Auvergne, 2010 - Normandie, 2011, 2017)
Keywords: aubeterre; neuffontaines

Les abbayes normandes - Chaline, Olivier (Grandes et petites figures de l'ordre de Prémontré. Les prémontrés et la justice. Actes officiels des 36e et 37e colloques du Centre d'Études et de Recherches Prémontrées. Auvergne, 2010 - Normandie, 2011, 2017)
Keywords: 🇫🇷 france (general)

Enclosing Ditch Uncovered at Annaghdown - Crumlish, Richard (Journal of the Galway Archaeological and Historical Society, 2017)
Keywords: annaghdown

Emo's reis - Een historisch culturele ontdekkingstocht door Europa in 1212 - De Boer, Dick (Uitgeverij Verloren, 2017)
Keywords: bloemhof

Of making many books there is no end. Father Cosmas Dillen's Dedication of Tongerlo's Library Catalogue to Abbot Adriaan Stalpaerts, 1625: A Critical Edition and Translation - Delsaerdt, Pierre; Deneire, Tom; Theyssens, Thomas (Felici curiositate. Studies in Latin Literature and Textual Criticism from Antiquity to the Twentieth Century. In Honour of Rita Beyers, 2017)
Keywords: tongerlo

Das Prämonstratenserkloster Belbuck als eine Keimzelle der Reformation im südlichen Ostseeraum - Ehricht, Christoph (Gdański Rocznik Ewangelicki, 2017)
The monastery in Belbuck near Treptow upon Rega in the former Duchy of Pomerania (today Białoboki / Trzebiatów in Pomorze Zachodnie/ Westpomerania, Poland) was founded in the end of the 12th century by Premonstratensians from Lund. In the beginning of the 16th century some very im-portant theologiansworked there. They were friends of Johannes Bugenhagen who, later on, becamea friend of Martin Luther and Reformer of the northern Germany and of the Kingdom of Denmark. His friends in Belbuckwere Johannes Boldewan, Johannes Äpinus, Christian Ketelhodt, Andreas Knopken. Connected with the monastery was a nunnery in Treptow, where Elisabeth von Meseritz (Elisabeth Cruciger) lived. They all exerted great influence on the Reformation and stabilization of the Lutheran Church from Copenhagenas far as Riga. The monastery itself has been, since 1616, completely destroyed, but remembrance of its history may be helpful for a more diverse understanding of very various processes occurring during the early time of “Reformation” in the Southern Baltic Sea region.
Keywords: białoboki

Saint-Jacques de Doue: premiers résultats de l'étude archéologique d'une abbaye prémontrée - Éneau-Brun, Lise; Reveyron, Nicolas (Grandes et petites figures de l'ordre de Prémontré. Les prémontrés et la justice. Actes officiels des 36e et 37e colloques du Centre d'Études et de Recherches Prémontrées. Auvergne, 2010 - Normandie, 2011, 2017)
Keywords: doue

Le cartulaire prémontré de Saint-Paul de Verdun - Évrard, Jean-Pol (Originaux et cartulaires dans la Lorraine médiévale (XIIe - XVIe siècles): Recueil d'études, 2017)
Keywords: verdun

Klášter premostrátek v Chotěšově - Forstová, Lada (University of West Bohemia, 2017)
Práce je věnovaná historii kláštera premonstrátek v Chotěšově. Popisuje dějiny od jeho založení po současnost. Představuje premonstrátský řád a jeho zakladatele sv. Norberta, zakladatele kláštera blahoslaveného Hroznatu a jeho sestru Vojslavu. Popisuje také život v klášteře, budovy a vnitřní zařízení.
Accepted: 2018-01-15T15:00:26Z Publisher: Západočeská univerzita v Plzni
Keywords: chotěšov

Oll Kloster Barthe - Hesel - Frees, Karl-Heinz (Sagen und Flurnamen in Ostfriesland: Begleitband zu einer Ausstellung in den Ostfriesischen Sparkassen 2017, 2017)
Keywords: barthe

Die Kirchen und Kapellen der Gemeinde Kastelbell-Tschars Dekanat Naturns - Diözese Bozen-Brixen - Friedrich, Verena (Kunstverlag Peda Gregor e.K, 2017)
OCLC: 992475350
Keywords: tschars

L’abbaye de Beauport - Gallet, Yves (Congrès archéologique de France : séances générales, 2017)
Keywords: beauport

Zum ewigen Gedächtnis: Wedinghausen als Grablege der Arnsberger Grafenfamilie, die Grafentumba und das Grafenbegängnis - Gosmann, Michael (SüdWestfalen Archiv, 2017)
Keywords: wedinghausen

Il magico cenobio: la biblioteca di Strahov a Praga. - Guernelli, Daniele (Alumina. Pagine miniate, 2017)
Keywords: strahov

Blahoslavený Hroznata, rytíř a řeholník - Hlinomaz, Milan (Biskupství plzeňské, 2017)
OCLC: 1000511348
Keywords: 👤 hroznata of bohemia

Les paroisses de l'abbaye Saint-André de Clermont - Hours, Bernard (Grandes et petites figures de l'ordre de Prémontré. Les prémontrés et la justice. Actes officiels des 36e et 37e colloques du Centre d'Études et de Recherches Prémontrées. Auvergne, 2010 - Normandie, 2011, 2017)
Keywords: clermont

Lautenbach/Renchtal: Pfarr- und Wallfahrtskirche "Mariä Krönung" - Huber, Rudolf (Schnell & Steiner, 2017)
Keywords: lautenbach

Evangelische und katholische Lämmer: Kurioses rund um die Ordenszeichen der Stiftsdamen von Stift Keppel - Isenberg, Erwin (Siegerländer Heimatkalender, 2017)
Keywords: keppel

Brouwen van bier door de Abdij van Averbode - Janssens, Hans (Bier brouwen in Brabant tot aan de Franse tijd in het bijzonder in de norbertijinenabdijen, 2017)
Keywords: averbode

Die spätromanische Hallenkirche St. Nikolaus in Arnsberg-Rumbeck - Kaiser, Roswitha (Zugänge zu Archäologie, Bauforschung und Kunstgeschichte - nicht nur in Westfalen: Festschrift für Uwe Lobbedey zum 80. Geburtstag, 2017)
Keywords: rumbeck

Bauforschung am ehemaligen Stiftsgebäude des Prämonstratenserstiftes St. Wiperti in Quedlinburg, 2006/07 - Karlson, Olaf (Vom Leben im Kloster und Stift – Wissenschaftliche Tagung zur Bauforschung im mitteldeutschen Raum vom 7. Bis 9. April 2016 im Kloster Huysburg, 2017)
Keywords: quedlinburg

La vision spirituelle dans l’espace corporel et le pouvoir performatif du langage dans la biographie mystique de Christina de Hane - Kirakosian, Racha (Le Moyen Age, 2017)
Medieval mystical texts are concerned with authenticating the stories they contain. Especially when they are written in a hagiographical tone, validating the ineffable through language becomes essential for the proof of sanctity. The retelling of mystical moments evolving in a visionary space reserved to the mystic, poses particular challenges for the mystical account which is read in a collective environment. The mystical Life of Christina of Hane serves as a case study for illustrating the relationship between the personal realm of the visionary and the communal physical space. Mapping between inner and outer perceptions as experienced by the Premonstratensian nun, the mystical text establishes analogies which translate non-figurative concepts – such as the mystical rapture – into corporeal manifestations. Despite claims to its apophatic nature, language plays a key role in the communication of the mystical moment: figures featuring in Christina’s visions perform speech acts, which bridge the gap between the visionary and the corporeal.
Bibliographie_available: 0 Cairndomain: www.cairn.info Cite Par_available: 0 Publisher: De Boeck Supérieur
Keywords: 👤 christina of hane

Musical heaven and heavenly music: at the crossroads of liturgical music and mystical texts - Kirakosian, Racha (Viator: Medieval and Renaissance Studies, 2017)
Keywords: 👤 christina of hane

Dejiny premonštrátskeho kláštora sv. Jána Krstiteľa v Jasove v stredoveku - Kotrusová, Júlia (Typi Universitatis Tyrnaviensis, 2017)
Keywords: jasov

Lelesz patrónusai - Kovács, Viktória (Történelmi Szemle, 2017)
The Patrons of Lelesz. Based on a number of hitherto unused sources, the present paper outlines the history of patronage over the Premonstratensian priory of Lelesz from its foundation until the end of the Middle Ages. It seeks to answer the question of what foundations the authority of the archbishop of Esztergom was based on, and when was it effectively extended over this church in the diocese of Eger, which was founded by another prelate, and had been mostly subjected to private patronage until the middle of the 14th century. The annex contains the publication of the judicial decision which, in 1355, annulled the claim to the patronage over Lelesz of the Eszenyi and Sztritei branches of the Baksa kin, who had thus far regarded the monastery as a kind of „family church”.
Keywords: leles

Bl. Hroznata z Teple ve svetle noveho badani - Kubín, Petr (Minulostí západoceského kraje, 2017)
Keywords: 👤 hroznata of bohemia

Legenda o bratru Hroznatovi = Vita fratris Hroznatae - Kubín, Petr; Bok, Václav (Togga, 2017)
OCLC: 1031044773
Keywords: 👤 hroznata of bohemia

Kloster Speinshart. Ein verborgenes Juwel in der Oberpfalz - Kugler, Hermann Josef (Schnell & Steiner, 2017)
Keywords: speinshart

Stift Stoppenberg und Stift Rellinghausen: Forschungsstand und -perspektiven - Küppers-Braun, Ute (Aus der Nähe betrachtet: regionale Vernetzungen des Essener Frauenstiftes in Mittelalter und früher Neuzeit, 2017)
Keywords: stoppenberg

Portrétní galerie proboštů a opatů kanonie premonstrátek v Chotěšově - Kysučan, Lubor; Oppeltová, Jana (Minulostí Západočeského kraje, 2017)
Keywords: chotěšov

The choir stalls of the monasteries of Pöhlde and St Alexander's in Einbeck: observations on their time of origin from an epigraphical and historical point of view - Lampe, Jörg H. (Choir stalls and their workshops: proceedings of the Misericordia International colloquium 2016, 2017)
Keywords: pöhlde

Den Baufugen sei Dank - Die Rekonstruktion einer Kapelle in der Klosterkirche in Germerode - Liedmann, Mareike (Universitätsbibliothek Heidelberg, 2017)
Keywords: germerode

Vrejlev kloster - et nordjysk præmonstratensernonnekloster - Lindholdt, Pia Katrine (Middelalder-Arkæologisk Nyhedsbrev, 2017)
OCLC: 993660432
Keywords: vrejlev

Ermida do Paiva: arquitetura e implantação monástica na serra de Montemuro - Lopes Cunha, Cláudia Gonçalves (Genius Loci: lugares e significados, 2017)
Keywords: ermida do paiva

Le cloître de l’abbaye de Leffe (Dinant) - Maggi, Christophe (Pré-actes des Journées d'Archéologie en Wallonie, Namur 2017, 2017)
Le cloître de l’abbaye de Leffe (Dinant)
Keywords: leffe

Parkbier - Magnus, Kristiaan (Bier brouwen in Brabant tot aan de Franse tijd in het bijzonder in de norbertijinenabdijen, 2017)
Keywords: park

Majetkové poměry a správa kláštera Chotěšov ve druhé polovině 16. století - Mírka, Jakub (Minulostí Západočeského kraje, 2017)
Keywords: chotěšov

L'abbé de Fontaine-André, patron de l'église Saint-Martin de Cressier et collateur de l'église de Meyriez et de la chapelle Sainte-Catherine devant Morat : documentation - Mühlebach, Hans (Communauté des frères des écoles chrétiennes, 2017)
Keywords: fontaine-andré

Hospodářské dějiny kláštera premonstrátů v Brně-Zábrdovicích ve 14. a 15. století - Müller, Tomáš (Masaryk University, 2017)
Keywords: zábrdovice

Anselm of Havelberg's controversies with the Greeks: a moment in the scholastic culture of disputation - Novikoff, Alex James (Dialogues and debates from late antiquity to late Byzantium, 2017)
Keywords: 👤 anselm of havelberg

Courtly Splendours: Hugh IV's Bellapais Abbey and the English Decorated Style - Olympios, Michalis (Decorated Revisited: English architectural style in context, 1250-1400, 2017)
Keywords: bellapais

Les premières chartes de l'abbaye de Combelongue - Pailhès, Claudine (Archives Ariégeoises, 2017)
Keywords: combelongue

Hroznata v listině z roku 1216 - Pátková, Hana (Minulostí Západočeského kraje, 2017)
Keywords: 👤 hroznata of bohemia

Beatrix von Engelport - Fakten und Legenden - Pies, Norbert J. (Hunsrücker Heimatblätter, 2017)
Keywords: engelport

Présentation de l'abbaye de Bellozanne - Plouvier, Martine (Grandes et petites figures de l'ordre de Prémontré. Les prémontrés et la justice. Actes officiels des 36e et 37e colloques du Centre d'Études et de Recherches Prémontrées. Auvergne, 2010 - Normandie, 2011, 2017)
Keywords: bellozanne

Visite de l'abbaye de Bellevaux - Plouvier, Martine (Grandes et petites figures de l'ordre de Prémontré. Les prémontrés et la justice. Actes officiels des 36e et 37e colloques du Centre d'Études et de Recherches Prémontrées. Auvergne, 2010 - Normandie, 2011, 2017)
Keywords: bellevaux

Visite de l'abbaye de l'Isle-Dieu - Plouvier, Martine (Grandes et petites figures de l'ordre de Prémontré. Les prémontrés et la justice. Actes officiels des 36e et 37e colloques du Centre d'Études et de Recherches Prémontrées. Auvergne, 2010 - Normandie, 2011, 2017)
Keywords: isle-dieu

Die Marchtaler Fälschungen: das Prämonstratenserstift Marchtal im politischen Kräftespiel der Pfalzgrafen von Tübingen, der Bischöfe von Konstanz und der Habsburger (1171-1312) - Schöntag, Wilfried (De Gruyter, 2017)
Keywords: marchtal

Ortenberger Marienaltar oder Ortenberger Wenzelsaltar? Marientheologie und Bildpolitik. Vorschläge zur Provenienz und Datierung des Ortenberger Retabels - Schroeder, Michael (Hessisches Jahrbuch für Landesgeschichte, 2017)
Keywords: konradsdorf

Restoration of the arches in the cloister at the Monastery of St Mary of Bellpuig de les Avellanes - Solé, Ramon (Rescat: Centre de Restauració de Béns Mobles de Catalunya, 2017)
Keywords: bellpuig de las avellanes

Zbořený kostel sv. Václava kláštera Chotěšov, pokus o rekonstrukci jeho podoby před zbořením a osudy vybavení kostela - Soukup, Jan (Minulostí Západočeského kraje, 2017)
Keywords: chotěšov

"A také klášter Hradisko u Olomouce byl obnoven naším rádem": konkurence mezi reholními rády a kolektivní identity kléru v ceských zemích ve 12. století - Šrámek, Josef (Vlastivedny vestnik moravsky, 2017)
Keywords: hradisko

Het klooster van 's Hertogen Eiland (Insula ducis) te Gempe - Steenberghen, Jean (2017)
Keywords: gempe

Opowieść o „Domu Bożym”. Z dziejów zespołu klasztornego i kościoła pw. Bożego Ciała i św. Norberta w Czarnowąsach (1206/1228–2016) - Stefaniak, Piotr (2017)
Keywords: czarnowąsy

De nonnen van Klooster Heiligerlee - Stolk, Cees (De verhalen van Groningen, 2017)
De nonnen van Mons Sinaï zaten pal in de vuurlinie: voor de poorten van hun klooster werd de Slag bij Heiligerlee geleverd (1568) en de gesneuvelde graaf Adolf werd opgebaard in hun kloosterkerk.
Keywords: heiligerlee

The Premonstratensian Nunnery in Strzelno (12th-14th c.): Sacral Architecture, Life and Death - Sułkowska-Tuszyńska, Krystyna (4th International Multidisciplinary Scientific Conference on Social Sciences and Arts SGEM2017, 2017)
Keywords: strzelno

Odraz zaniklých soukromých knihoven patnáctého a šestnáctého století z území kostnické diecéze v rukopisné sbírce pražské lobkowiczké knihovny - Svobodová, Milada (Studie o rukopisech, 2017)
Keywords: weissenau

Von der Wahrheit des Fälschers : die Gründungsgeschichte des Prämonstratenserklosters Humilimont (Marsens) in neuem Licht - Tremp, Ernst (Freiburger Geschichtsblätter, 2017)
Keywords: humilimont

Klášter, nebo hrad? Rezidence litomyšlských biskupů v letech 1344–1421, její hypotetická rekonstrukce a klasifikace - Večeře, Vojtěch (Castellologica bohemica, 2017)
Keywords: litomyšl

Erkenntnisse über bedeutende Klosteranlage: geophysikalische Prospektion von Rothenkirchen - Werling, Michael (Donnersberg-Jahrbuch, 2017)
Keywords: rothenkirchen

Jerusalem in Tønsberg: round churches and storytelling - Wienberg, Jes (Jerusalem in medieval Scandinavia: kings, crusaders, and monastic orders, 2017)
Keywords: tønsberg

Mönch oder Kanoniker?: Bernhard von Clairvaux versus Norbert von Xanten - Winkler, Gerhard (Patrimonium-Verlag, 2017)
Pages: 224 Series Title: Patrimonium Cisterciense
Keywords: 👤 norbert of xanten

Les sceaux de l'abbaye Saint-André de Clermont - Zang, Marie-Astrid (Grandes et petites figures de l'ordre de Prémontré. Les prémontrés et la justice. Actes officiels des 36e et 37e colloques du Centre d'Études et de Recherches Prémontrées. Auvergne, 2010 - Normandie, 2011, 2017)
Keywords: clermont

Miera koncentrácie majetkovej držby a jej vplyv na zemepanskú správu v prostredí premonštrátskych konventov v Bzovíku, Šahách a Kláštore pod Znievom - Žažová, Henrieta (Studia historica Tyrnaviensia, 2017)
The rate of concentration of property holdings and their impact on land administration in the surroundings of the Premonstratensian convents in Bzovík, Šahy and Kláštor pod Znievom
Keywords: bzovík; klaštor pod znievom; šahy

Stredoveké premonštrátske kláštory v slovenskej časti územia bývalého Ostrihomského arcibiskupstva - Žažová, Henrieta (Typi Universitatis Tyrnaviensis, 2017)
Keywords: 🇸🇰 slovakia (general)

Les ardoises gravées de l’abbaye de Prémontré (Aisne), un support de notation musicale aux xve-xvie siècles - Galmiche, Thierry; Buccio, Vincent (Archéologie médiévale, 2016)
L’abbaye de Prémontré a été fondée en 1121 dans l’évêché de Laon. Trois ardoises gravées de notations musicales ont été mises au jour lors de fouilles archéologiques réalisées dans l’enceinte abbatiale entre 2010 et 2012. Pour deux d’entre elles, ces inscriptions consistent uniquement en des portées. Pour l’autre ardoise, des notes de musique ont, en outre, été dessinées.Un premier recensement indique que ce type d’artefact n’est pas isolé, trente-trois objets similaires ont en effet été dénombrés. Ils sont tous datés des xve-xve siècle. Dans l’état actuel des recherches, l’aire géographique de ces découvertes s’étend du sud-ouest de la France aux îles Britanniques en passant par la Bretagne, l’Île-de-France, la Picardie, la Belgique et les Pays-Bas.L’essentiel de ces ardoises ont été retrouvées en contexte ecclésiastique. Leur examen fait ressortir des disparités tant au niveau de la forme des ardoises que des dimensions, parfois difficiles à apprécier, et des inscriptions qui y sont portées. A minima, des portées sont présentes (à l’exception de l’exemplaire de la chapelle de Lopikerkapel, les notes sont en notation blanche mesurée). Dans d’autres cas, l’intention de réaliser des supports destinés à être réutilisés est patente.Ces différences nous ont conduits à définir trois catégories d’ardoise. Les premières, sur lesquelles sont inscrites des portées et, de façon occasionnelle des notes, ont été utilisées comme simple support à noter de la musique. Après chaque usage, elles sont effacées. Ces supports ont ainsi pu servir pour l’apprentissage de la composition ou pour l’entraînement à la concordance des voix. Les ardoises 2 et 3 de Prémontré ont été rangées dans ce groupe. Des extraits musicaux sont intentionnellement gravés sur les schistes de la deuxième catégorie mais leur usage est unique. L’emploi de ces ardoises comme support temporaire de composition peut être proposé. Une fois l’extrait recopié, l’ardoise est jetée. La troisième catégorie, numériquement moins importante, est constituée d’ardoises à usages répétés. Ces schistes pourraient avoir été utilisés dans l’apprentissage par mémorisation ou comme supports pour des choristes. L’exemplaire 1 de Prémontré, classé dans cette catégorie, est le plus complet : il est exceptionnel par son état de conservation et par la longueur du fragment musical gravé. Chacune de ces ardoises pourrait donc avoir été utilisée dans la composition ou l’apprentissage de la musique.
Keywords: prémontré; 🎶 musicology

The Cartulary of the Abbey of Prémontré: A Story of Conflict and Resolution - Wacha, Heather (Essays in Medieval Studies, 2016)
In lieu of an abstract, here is a brief excerpt of the content: The Cartulary of the Abbey of Prémontré: A Story of Conflict and Resolution Heather Wacha Introduction Monastic cartularies offer important evidence for the study of an institution’s social and economic history. Compiled of papal bulls, privileges, donations, confirmations, and property transactions, the textual evidence found in cartulary charters can narrate the growth and decline of an abbey’s revenues and rights over the course of decades. It can also recount the stability and fluidity of social relationships with lay patrons, other religious institutions, and dependent houses. In addition to charter content, the process of selecting and organizing charters for cartulary construction provides further insights into a religious institution’s historical context.1 For the cartulary of the Abbey Saint-Jean Baptiste de Prémontré, located in the region of Picardy, France, the textual and codicological evidence together tell a story of how two long-term conflicts and the abbey’s desire to memorialize their resolution resulted in the completion of its cartulary in 1239. At present there exists no critical edition of the Abbey of Prémontré’s cartulary. In 1975, the Centre d’études et de recherches prémontrées (CERP) launched a cartulary edition project based on the original manuscript, Soissons, Bibliothèque municipale (henceforth Bm), MS. 7. By 1988, Françoise Muret had finished the transcriptions of all cartulary acts, found today at the Institut de recherche d’histoire des textes (henceforth IRHT) in Orléans and Paris, yet her substantial work and significant contributions remain unpublished.2 The cartulary’s notice, also held at the IRHT, posits a range of dates for the completion of the abbey’s cartulary between 1239 and 1250, but no follow-up studies have narrowed this window. This article argues that the cartulary was completed no later than 1239 and that this date was not an arbitrary one. The origins of the Abbey of Saint-Jean Baptiste de Prémontré, the founding abbey of the eponymous order, date from 1121, when Norbert of Xantan [End Page 125] (c. 1080–1134) established his houses of religious brothers and sisters at the confluence of three rivers northeast of Paris and west of Laon.3 When Norbert of Xantan left Prémontré in 1126 to become archbishop at Magdeburg, Germany, the abbey continued to flourish under the leadership of Hugh of Fosses (1126–1164), who codified the order’s statutes and liturgy.4 Much of the scholarship addressing the twelfth-and thirteenth-century history of the Abbey of Prémontré has focused on Norbert of Xantan and his spiritual vision for the order as a whole.5 As a result, the abbey’s early history is often portrayed as a time of rapid growth for the order, casting Prémontré as the central force that held the houses and order together.6 Prémontré’s cartulary, however, reveals a moment in the abbey’s history in which tension and conflict were rife, to such a degree that the desire to reinstate a sense of peace and order influenced the process of cartulary construction, as well as the date of completion. While the Abbey of Prémontré is widely accepted and respected as the mother abbey of the Premonstratensian order today, in the thirteenth century challenges from its houses in Germany suggest that this status had yet to be firmly secured. In 1234, Pope Gregory IX drew attention to what had become a general lack of consistent practice across houses within the Premonstratensian order. Within his more global agenda of reform, the pope specifically called for the rewriting of the Premonstratensian statutes, requesting that the abbot-general reconsider the central governing structure of the order, the governing of individual abbeys, and the uniformity of customs and liturgy.7 In essence, the pope sought universal agreement within the order as to who was in charge and what it meant to be a member of the Premonstratensian order. As part of the response to the Pope’s call for reform, Abbot Conrad (1220–1233) and his secretary/librarian, later Abbot Hugh III (1238–1242), initiated Prémontré’s cartulary. Although cartulary construction began in earnest sometime shortly before or around 1234, the settlement of the...
Keywords: prémontré

Unravelling the medieval mystery of our pirate priests - Grant, Sheena (The East Anglian Daily Times, 2016)
Keywords: leiston

Team hunting for Leiston Abbey’s ‘priest pirates’ - Cornwell, Richard (The East Anglian Daily Times, 2016)
Keywords: leiston

Détour par Laval-Dieu - Theret, Jacques (Terres Ardennaises, 2016)
Keywords: laval dieu

Aportaciones a la arquitectura y la historia del monasterio de Sancti Spiritus de Ávila - Blanco, Raimundo Moreno (Espacio Tiempo y Forma. Serie VII, Historia del Arte, 2016)
Keywords: ávila

À la recherche de l'abbaye disparue - Bracquemart, Sophie (L'Ardennais, 2016)
Keywords: chaumont-porcien

Un temporel monastique dans l'espace médiéval gascon : l'abbaye prémontrée de la Casedieu (Gers), XIIe-XVIe s - Abadie, Stéphane (Université de Toulouse 2, 2016)
L'abbaye de la Casedieu (v. 1135-1790) a été le premier établissement de l'ordre prémontré en Gascogne et la tête d’une circarie éponyme dans le sud de la France et le nord de l'Espagne. L'archéologie du mobilier dispersé et l'étude documentaire permettent de restituer en partie l'histoire riche et complexe d'une grande abbaye disparue qui fonda une trentaine d'abbayes-filles et prieurés.La documentation écrite permet également de restituer un réseau dense de granges agricoles, formées aux XIIe et XIIIe siècles, qui ont évolué pour se transformer en bastides ou en terres affermées à partir du XIVe siècle. Les prémontrés disposaient également de deux prieurés-filles, d'un réseau d'églises paroissiales et de moulins qui fonctionna jusqu'au XVIIIe siècle.L'étude des bastides fondées par les prémontrés montre aussi la capacité d'évolution économique des chanoines, qui implantent des " maisons des abbés " à but résidentiel et commercial et tentent de s'opposer à l'installation des ordres mendiants.L'adaptation aux crises de la fin du Moyen Âge permet également d'observer le rôle, souvent positif, des abbés commendataires, la mise en défense militaire de l'abbaye ou encore la participation aux collégiales de bastides, avant les destructions des guerres de Religion.
Keywords: case dieu

Archaeological Investigations at Coverham Abbey, North Yorkshire 1995–2015 - Pinnock, Dave (Yorkshire Archaeological Journal, 2016)
Coverham Abbey near Middleham, North Yorkshire is the site of a former Premonstratensian monastery. As well as a fine late medieval gatehouse, there are some standing remains of the abbey church including parts of the eastern elevation of the chancel, the north transept, the western elevation of the nave, the south transept, and three standing pillars of the arcade of the nave’s south aisle. Later dwellings on the site incorporate substantial masonry from the abbey’s west claustral range. A number of small scale, developer-funded archaeological investigations have been undertaken since 1995 that shed light on the layout and design of the medieval monastery. In particular, the various investigations have revealed the layout of the hitherto unknown east and south claustral ranges, as well as further aspects of the west range. The buried remains of an elaborately carved lavatorium arcade were also found, which is a highly significant example of monastic decorative architecture.
Keywords: coverham

Strahov: Klášter, Abbey, Stift (2016)
Keywords: strahov

A bárdudvarnoki premontrei prépostság területén 2015-ben végzett régészeti feltárás - Aradi, Csilla M.; Molnár, István (Archaeologia - Altum Castrum Online, 2016)
Keywords: kaposfő

Das mittelalterliche Ensemble des Doms zu Riga - Bergholde-Wolf, Agnese (Kunstiteaduslikke Uurimusi, 2016)
Keywords: rīga

Rennemoulin (Yvelines), "Chapelle Saint-Nicolas": Rapport de fouille - Beurtheret, Maude; Collomb, Camile; Gaucher, Agathe; Peck, Mylène (Archeodunum, 2016)
Keywords: rennemoulin

Základná Antropologická Charakteristika Jedincov z Cintorína Pri Premonstrátskom Klástore v Lelesi (Okres Trebisov, 10-16. Stor. N. L.) - Bodorikova, Silvia (2016)
Keywords: leles

Ratzeburg: Domstift S. Maria, S. Johannes Evangelist (Ordo Praemonstratensis / Prämonstratenser; Säkularkanoniker) - Bünz, Enno (Mecklenburgisches Klosterbuch, 2016)
Keywords: ratzeburg

Los abades perpetuos del Monasterio Premonstratense de Sancti Spiritus (1171-1571) y la crónica de su fundación - Calvo Gómez, José Antonio (Cuadernos abulenses, 2016)
Keywords: ávila

Prilog poznavanju izgradnje crkve sv. Marije u Kloštar Ivanicu u razdoblju srednjeg vijeka - Cepetic Rogic, Maja (Peristil, 2016)
Keywords: ivanić

Křtinská záhada - klášter premonstrátek - Charouz, Jindřich Zdeněk (Dějiny a dějepis, 2016)
Keywords: křtiny

Ein gräflicher Stützpunkt im Spessart: hochmittelalterlicher Straßenposten und Kloster Elisabethenzell: Stadt Rieneck, Landkreis Main-Spessart, Unterfranken - Enders, David (Das archäologische Jahr in Bayern, 2016)
Keywords: einsiedel

The ‘Reform' of religious landscape 950-1200: Premonstratensians and their predecessors at Barlings Abbey, Lincolnshire - Everson, Paul; Stocker, David A. (Places of worship in Britain and Ireland, 950-1150, 2016)
Keywords: barlings

Das ehemalige Kloster Weissenau - der "ohnvermeidlich höchstnothwendige" Umbau?: Aspekte zur Landschaftsgeschichte, Blütezeit und Abwicklung eines Kleinstaates im südlichen Stadtgebiet Ravensburgs - Ewald, Rainer (Altstadt-Aspekte: Mitteilungen des Bürgerforums Altstadt Ravensburg e.V., 2016)
Keywords: weissenau

De digitale publicatie van een nieuw deel van de inventaris van het roerend kunstpatrimonium van de Norbertijnenabdij van Tongerlo: een stand van zaken. - Eyck, Griet van (Bulletin. Institut Royal du Patrimoine Artistique, 2016)
Keywords: tongerlo

Urkunden und Regesten des Prämonstratenserstiftes Varlar (1118–1782) - Frese, Werner; Wermert, Christian (Kreisheimatverein Coesfeld, 2016)
Keywords: varlar

Das Upgrade einer karolingischen Saalkirche - die romanische Basilika von Kloster Konradsdorf - Friedrich, Waltraud (Denkmalpflege und Kulturgeschichte, 2016)
Keywords: konradsdorf

Das Kloster Speinshart zwischen Reformation und Wiederbesiedlung (1556-1661) - Fuchs, Bernhard (Oberpfälzer Klosterlandschaft: die Klöster, Stifte und Kollegien der Oberen Pfalz, 2016)
Keywords: speinshart

Richmond Castle and Easby Abbey - Goodall, John Archibald (English Heritage, 2016)
Keywords: easby

Die Dachrestaurierung der Propsteikirche St. Walburga in Werl: Reparaturen am "Chorturm" und am Langhausdachwerk im zweiten Bauabschnitt - Halekotte, Theo (Werl gestern, heute, morgen. Ein Jahrbuch der Stadt Werl und des Neuen Heimat- und Geschichtsvereins Werl, 2016)
Keywords: werl

Broda: Chorherrenstift S. Maria, S. Peter und Paul (Ordo Praemonstratensis / Prämonstratenser) - Hardt, Matthias (Mecklenburgisches Klosterbuch: Handbuch der Klöster, Stifte und Kommanden (10. - 16. Jahrhundert), 2016)
Keywords: broda

Der Ort Hamborn und seine Abtei von 1461 bis 1500 - Horstkötter, Ludger (Verlagshaus Monsenstein und Vannerdat, 2016)
Keywords: hamborn

Graduál loucký - Hrbáčová, Jana (Chrám věd a múz : 450 let Vědecké knihovny v Olomouci, 2016)
Keywords: louka

Pouvoirs et autorités dans les établissements prémontrés au Moyen Âge au regard des circaries de l’Ouest - Jeanneau, Cédric Jacques (Pouvoir(s) et autorité(s) chez les prémontrés, 40e colloque du Centre d’Etudes et de Recherches Prémontrées, La Mondaye 2014, 2016)
Keywords: 🇫🇷 france (general)

Virga Versatur: remarques sur l'iconographie des vitraux romans d'Arnstein-sur-la-Lahn. - Kalinowski, Lech (Ars vitrea: collected writings on mediaeval stained glass, 2016)
Keywords: arnstein

Historisches Messgewand der Stiftskirche St. Maria Magdalena Flaesheim - Klatt, Hartmut (Flaesheimer Heimatverein e.V., 2016)
Keywords: flaesheim

Liebfrauen und St-Yved in Braine - Klein, Bruno (Liebfrauen in Trier. Architektur und Ausstattung von der Gotik bis zur Gegenwart, 2016)
Keywords: braine

Lika ideal, skilda uttryck- cistercienserna och premonstratenserna i ostra Danmark - Kockum, Jan (Mellan slott och slagg. Vänbok till Anders Ödman, 2016)
Keywords: 🇩🇰 denmark (general)

Počátky mnišství v evropském kontinentálním prostoru Premonstráti v západních Čechách - Kostilníková, Renata (University of West Bohemia, 2016)
Kvalifikační práce pojednává o premonstrátském řádu v Čechách s důrazem na historický vývoj a současnost kláštera premonstrátů v Teplé. Cílem práce je odhalit různé aspekty, kterými klášter v Teplé přispěl k duchovnímu a kulturnímu rozvoji na území západních Čech. Kromě duchovní, kulturní a i hospodářské činnosti se tepelští premonstráti podíleli na šíření vzdělanosti. Začátek práce je zaměřen na samotné založení premonstrátského řádu, jehož zakladatelem byl svatý Norbert z Xantenu. Příchod premonstrátů do Čech sebou přinesl nové zakládání klášterů. Značné ztráty zaznamenal premonstrátský řád během husitských válek, kdy přišel skoro o všechny kláštery. Obnovení klášterů nastalo až během rekatolizace protestantských oblastí v 16. století. Nejvíce pozornosti se v práci dostává tepelskému klášteru. Podkapitoly se zabývají dějinami kláštera od založení blahoslaveným Hroznatou až do současnosti. Střídaly se období pádů a vrcholů. Hroznata založil i ženský klášter premonstrátek v Chotěšově. Knihovna, které je věnována samostatná kapitola obsahuje přes 100 000 knih a patří k největším knihovnám u nás. Další samostatná část je zaměřena na významnou osobnost premonstrátského řádu, kterou je Josef Heřman Tyl. Současný vývoj kláštera je doplněn i o osobní rozhovor s opatem Filipem Zdeňkem Lobkowiczem, Opraem. V roce 2008 se stal klášter Teplá národní kulturní památkou. Klášter má duchoví a kulturní přínos již více než 800 let své existence. Velká zásluha byla zaznamenána především v oblasti školství. Tepelští premonstráti učili na plzeňském gymnáziu a podporovali nadané žáky. Největší přínos, který klášter mohl západním Čechám poskytnout, bylo založení Mariánských Lázní opatem Karlem K. Reitenbergerem.
Accepted: 2017-02-21T08:10:46Z Publisher: Západočeská univerzita v Plzni
Keywords: 🇨🇿 czechia (general)

Nález gotického architektonického článku na klášteřišti zaniklého řeholního domu premonstrátek v Louňovicích pod Blaníkem - Kovář, Miroslav (Časopis Společnosti přátel starožitností : recenzovaný časopis pro historickou vlastivědu a národní kulturní dědictví, 2016)
Keywords: louňovice

Das Prämonstratenserstift Arnstein im 12. Jahrhundert - Krings, Bruno (Verein für Geschichte/Denkmal- und Landschaftspflege e.V., 2016)
Keywords: arnstein

Histoire de l'Abbaye de Chaumont Saint-Berthauld - Le Barzic, Patrick (2016)
Keywords: chaumont-porcien

Quellen zur Geschichte des Stiftes Flaesheim im 13. Jahrhundert (IV) - Lindken, Theodor; Schwabe, Gabriele (Vestische Zeitschrift, 2016)
Keywords: flaesheim

Hermann quondam ludaeus: ein Konvertit im Kloster Scheda: vom spirituellem Aufbruch im 12. Jahrhundert zur rationalen Musterwirtschaft - Löer, Ulrich (Heimatkalender des Kreises Soest, 2016)
Keywords: scheda

Geoffroy du Loroux et l’abbaye Sainte-Marie de Pleine-Selve. La fondation d’une abbaye prémontrée en Bordelais au XIIe siècle : une volonté épiscopale ? - Masson, Juliette (Pouvoir(s) et autorité(s) chez les Prémontrés, 40ème colloque du Centre d’Etudes et de Recherches Prémontrées, 27 septembre 2014 à l’abbaye de Mondaye (Calvados), 2016)
Keywords: pleineselve

L'abbaye de Combelongue en 3 D - Mirguet-Avanzi, Jean (Roman en Couserans, 2016)
Keywords: combelongue

Řád premonstrátů v Čechách : minulost a současnost - Novotná, Petra (University of West Bohemia, 2016)
Práce se zabývá popisem historie a činnosti řádu premonstrátů v Čechách od dob středověku do současnosti. Autorka popisuje život v klášteře a činnosti, které s ním souvisí. V České republice se nachází čtyři premonstrátské kanonie - v Želivu, Nové Říši, Teplé a na Strahově. Na poslední dvě jmenované se autorka zaměřila blíže. Kromě premonstrátských řeholníků jsou součástí řádu i sestry premonstrátky, jejichž činnost je popsána v předposlední kapitole. Na závěr autorka představila významné osobnosti řádu.
Accepted: 2017-02-21T08:10:49Z Publisher: Západočeská univerzita v Plzni
Keywords: 🇨🇿 czechia (general)

Znaczenie opactwa premonstrateńskiego w Brzesku-Hebdowie w strukturze zakonu i Kościoła w XIV–XV wieku - Podgórska-Mikuła, Arkadia (Studia z Dziejów Państwa i Prawa, 2016)
Th e importance of the Premonstratensian Abbey in Brzesko–Hebdów for the structure of the Order and the Church in the 14th and 15th centuries
Th e importance of the Premonstratensian Abbey in Brzesko–Hebdów for the structure of the Order and the Church in the 14th and 15th centuries
Keywords: brzesko

Composition and Microstructure of Plasters in Convent of the Želiv Monastery (Czech Republic) - Rezek, Petr; Martinec, Petr; Ščučka, Jiří; Majstríková, Tereza (Key Engineering Materials, 2016)
The paper deals with analyses of composition and structure of historic plasters from the convent building of the Želiv Monastery (Czech Republic). Composition and microstructure of plaster samples taken from the historic object have been assessed using both traditional and advanced analytical methods. The following techniques have been used for the assessment of binders and fine aggregates in plasters: optical microscopy of thin sections, mineralogical and petrographic analysis of separated components, infrared spectroscopy, and thermal analysis. Presented results show significant differences in character of the studied materials of varying age and demonstrate the effectiveness of the taken analytical approach.
Conference Name: Proceedings of the 17th Conference on the Rehabilitation and Reconstruction of Buildings (CRRB 2015) ISBN: 9783038357193 Publisher: Trans Tech Publications Ltd
Keywords: želiv

Ecos en piedra de las imágenes miniadas del siglo XII: el paralelismo de tipos iconográficos entre los capiteles de Santa María la Real (Aguilar de Campoo) y la Biblia de Ávila (Biblioteca Nacional, Madrid, Vit. 15-1) - Rodríguez Velasco, María (Boletín del Museo Arqueológico Nacional, 2016)
Keywords: aguilar de campoo

Schaufenster des Himmels : Der Altenberger Altar und seine Bildausstattung = Heaven on Display : The Altenberg Altar and Its Imagery - Sander, Jochen (Deutscher Kunstverlag, 2016)
Keywords: altenberg

Scientific Renewal and Reformed Religious Life: The Case of the Arnstein Bible - Schonhardt, Michael (Journal of medieval monastic studies, 2016)
Keywords: arnstein

'Ten Thousand Women': Gender, Affinity, and the Development of the Premonstratensian Order in Medieval France - Seale, Yvonne (University of Iowa, 2016)
Keywords: 🇫🇷 france (general)

Well-Behaved Women? Agnès of Baudement and Agnès of Braine as Mediators and Patrons of the Premonstratensian Order - Seale, Yvonne (Haskins Society Journal: Studies in Medieval History, 2016)
Keywords: braine

Oficium ke sv. Norbertovi a jeho vývoj - Sojka, Václav (Charles University, 2016)
Keywords: 🛐 liturgy

The Last Days of the Abbeys of Durford and Titchfield and a Case of Mistaken Identity - Stevenson, Janet H. (Proceedings of the Hampshire Field Club and Archaeological Society, 2016)
Keywords: durford; titchfield

Klášter premonstrátů v Nové Říši a jeho význam pro region v období 1918-1938 - Stoklasa, Jan; Polehla, Petr (Pavel Mervart, 2016)
OCLC: 982101314
Keywords: nová říše

Boren aan de rand van Nijenklooster in Holwierde (gemeente Delfzijl) - Stöver, J.; Van der Heiden, M. (2016)
Keywords: nijenklooster

Summa Norbertina: die Ausmalung der Bibliothek des Prämonstratenserklosters Speinshart (Oberpfalz) aus dem Jahr 1773 - Telesko, Werner (Armarium - Buchkultur in Oberpfälzer Klöster: Symposion vom 3. bis 4. Juli 2015 veranstaltet von der Provinzialbibliothek Amberg, 2016)
Keywords: speinshart

La Bibbia atlantica di Bellelay - Togni, Nadia (Les Bibles atlantiques. Le manuscrit biblique à l'époque de la réforme de l'église du XIe siècle, 2016)
Keywords: bellelay

Rapports de fouilles (aile du réfectoire et de la cuisine) - Tournier, Fanny (Service régional d'archéologie de Bretagne, 2016)
Keywords: beauport

Diplomatika a správa kláštera Teplá ve 2. polovině 15. století - Trnka, Pavel (Univerzita Karlova, 2016)
[Diplomatics and Administration of the Monastery of Teplá in the Second Half of the Fifteenth Century]
Keywords: teplá

Der Notar als Fälscher : die Gründungsurkunde des Prämonstratenserklosters Humilimont/Marsens (1137) - Utz Tremp, Kathrin; Tremp, Ernst (Schweizerische Zeitschrift für Religions- und Kulturgeschichte, 2016)
Keywords: humilimont

Ninove, een Vlaamse premonstratenzer abdij op de grens van Brabant en op het breukvlak van stad en plateland - Vande Winkel, Georges (De premonstratenzer Abdijkerk van Ninove. Barokke pracht in luister hersteld, 2016)
Keywords: ninove

Geneza i historia Rytu Premonstrateńskiego - Wendland, Mateusz (Liturgia Sacra, 2016)
The Premonstratensian, or Norbertine Rite is strictly related to the Order of Canons Regular, also known as the White Canons. Founded in the 12th century by Saint Norbert, the order at first adhered to liturgical practices that were common among the Canons Regular of Saint Augustine. The following article talks about the genesis and development of Norbertine liturgy, which survived the changes in practices made by the Council of Trent, but was eventually made obsolete by the Second Vatican Council.
Keywords: 🛐 liturgy

Die Klausuranlage des ehemaligen Prämonstratenserklosters Veßra - ein bedeutendes mittelalterliches Denkmal in Thüringen - Witter, Thomas (Heimat Thüringen, 2016)
Keywords: veßra

Die Prämonstratenserniederlassung in Jerichow im 12. und 13. Jahrhundert - Wochnik, Fritz (Lapidarium Jerichowense, 2016)
Keywords: jerichow

Rehna: Kloster / Chorfrauenstift S. Maria, S. Elisabeth (Ordo Sancti Benedicti / Benediktinerinnen, Ordo Praemonstratensis / Prämonstratenserinnen, Ordo Cisterciensis / Zisterzienserinnen) - Wurm, Johann Peter (Mecklenburgisches Klosterbuch, 2016)
Keywords: rehna

Le prieuré Sainte-Marguerite dit de Monaqueville - Bavay, Jeannine (Vikland: la revue du Cotentin, 2015)
Keywords: monaqueville

Terrasini, completato il restauro della chiesa di San Cataldo - Catalano, Maria Carola (Palermo Today, 2015)
Keywords: terrasini

On the Life of Those Who Dwell in Enclosure - Scot, Adam (Cistercian Studies Quarterly, 2015)
The article presents a sermon about Mary Magdalene by Anglo-Scottish theologian Adam Scot, also known as Adam of Dryburgh or Adam the Carthusian, dedicated to the Canons Regular of Prémontré. The sermon considers how Mary reminds about the singular privilege of those who live in enclosure within God, and of those who come near the Lord himself and cling to him tenaciously. It also looks at what the Gospel say about Mary, about anointing Jesus' feet with a pound of costly perfume.
Publisher: Cistercian Studies Quarterly
Keywords: 👤 adam of dryburgh

Stained Glass from the Corcoran Gallery to Return to Park Abbey - Shortell, Ellen M. (Vidimus, 2015)
Keywords: park

'Clothing for the Soul Divine': Burials at the Tomb of St Ninian: Excavations at Whithorn Priory, 1957-67 - Lowe, Christopher E. (Historic Environment Scotland, 2015)
Whithorn, known as Scotland's Cradle of Christianity, is unique as a centre of worship, administration, and ultimately pilgrimage, dating back to the 5th century.The work carried out at Whithorn Priory by Roy Ritchie in the late 1950s and 1960s is the only modern excavation campaign to focus on the high status burials near the high altar of a major Scottish medieval church. Remains of earlier graves, as well as structures now recognised as parts of the extended medieval cathedral church, were uncovered. Among the uppermost level of graves are those that belong to a number of Whithorn's bishops, some of whom are tentatively named.This volume details the results of historical and scientific analysis of the remains of the bishops - who they were and where they came from, together with the circumstances of their deaths and burial. Many of these graves were richly furnished - including altar plate and the famous Whithorn crozier - and the full assemblage of artefacts from the excavation is published here for the first time. This publication also resolves, once and for all, the nature and date of the earliest graves that were identified at the base of the trench. The story of one of Scotland's most important 'lost excavations' can now be told.
Google-Books-ID: JkWNRAAACAAJ
Keywords: whithorn

Ancient abbey dig set to resume at Leiston - Potter, Tom (The East Anglian Daily Times, 2015)
Keywords: leiston

Nacht van Geschiedenis belicht 864 jaar Hof te Kattem (VILT, 2015)
Keywords: kattem

La redécouverte de l’abbaye d’Abbecourt (Orgeval, Yvelines) (La lettre d'aristeas, 2015)
Keywords: abbecourt

Kanonie premonstrátů Teplá: Národní kulturní památka (2015)
Keywords: teplá

Kloster Speinshart Panorama Rundgang (2015)

St. Norbert and His Order (Mediatrix Press, 2015)
Keywords: 👤 norbert of xanten; 📚 premonstratensian (general)

Kurze Geschichte des Klosters Maria Engelport von 1220 bis heute - Ackermann, Stephan; Pies, Norbert J. (100 Jahre Lourdesgrotte Kloster Maria Engelport : Festschrift, 2015)
Keywords: engelport

El monasterio premonstratense de Santa María de la Vid (Burgos). Siglos XII-XV - Angulo Fuertes, María Teresa (Universidad Nacional de Educación a Distancia, 2015)
Keywords: la vid

Premontrei prépostság feltárása Bárdudvarnokon - Aradi, Csilla M.; Molnár, István (Fiatal Középkoros Régészek VI. Konferenciájának Tanulmánykötete, 2015)
Keywords: kaposfő

Discours d'ouverture: les Prémontrés et Beauport - Ardura, Bernard (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Deux décennies de travaux et découvertes à l'abbaye de Beauport (1992-2012) - Ballini, Annie-Claude (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Neues zum Cappenberger Barbarossakopf - Balzer, Edeltraud (Westfalen, 2015)
Keywords: cappenberg

Lahonce (64), Abbaye : rapport de diagnostic - Béague, Nadine; Fabrice, Leroy (Inrap GSO, 2015)
Keywords: lahonce

Inventarien der Klöster Weidas und Münsterdreisen 1553 - Becker, Christa (Kaiserslauterer Jahrbuch für pfälzische Geschichte und Volkskunde, 2015)
Keywords: münsterdreisen

Une présence anglaise à Beauport, Le marbre de Purbeck XIIIe siècle - Beneult, Dominique (Les Cahiers de Beauport, 2015)
Keywords: beauport

Rīgas Doma viduslaiku arhitektūra un būvplastika eiropeisko analoģiju kontekstā - Bergholde, Agnese (Latvijas Māksalas akadēmijas Mākslas vēstures institūts, 2015)
Keywords: rīga

Die Eigenkirche der Grafen von Cappenberg als Urzelle des Klosters Ilbenstadt - Bewerunge, Norbert (Archiv für mittelrheinische Kirchengeschichte, 2015)
Keywords: ilbenstadt

Neue Forschungen zum Prämonstratenserstift Grobe auf der Indsel Usedom: Ausgrabungen am Wilhelmshofer Priesterkamp im Jahre 2010 - Biermann, Felix Paul (Bodendenkmalpflege in Mecklenburg-Vorpommern, 2015)
Keywords: grobe

Archäologische Forschungen am Prämonastratenserstift Belbuck bei Treptow an der Rega - Biermann, Felix Paul; Dworaczyk, Marek; Rebkowski, Marian (Baltische Studien, 2015)
Keywords: białoboki

Statuten mittelalterlicher Ordensgemeinschaften: Strategien normativer Stabilisierung mittels statutarischer Gesetzgebung am Beispiel der Zisterzienser, Prämonstratenser, Dominikaner und Franziskaner - Bitterlich, Markus (Technische Universität Dresden, 2015)
Keywords: ⚖️ chapters and statutes; 📚 premonstratensian (general)

Late Romanesque Convent Church of the Norbetine Sisters in Zwierzyniec in Cracow in the Light of Architectural Research from 2010-2011 - Bojes-Bialasik, Anna; Czechowicz, Jacek (Cihla a stavební keramika ve stredoveku a novoveku v mestské architekture strední Evropy, 2015)
Keywords: zwierzyniec

Die Siegel der mährischen Pramonstratenser als Quelle zur Geschichte der Zirkarie - Bolom-Kotari, Martina (Ordenshistoriographie in Mitteleuropa: Gestaltung und Wandlung des institutionalen und persönlichen Gedächtnisses in der frühen Neuzeit ; Referate der gleichnamigen Tagung in St. Pölten von 22. bis 23 September 2014, 2015)
Keywords: 🇨🇿 czechia (general)

O klobouku na pečetích zábrdovických premonstrátů - Bolom-Kotari, Martina (Archivum amicus historici est : sborník příspěvků k životnímu jubileu Hany Jordánkové, 2015)
Keywords: zábrdovice

Het Norbertinessenklooster Sint-Gerlach te Houthem. 1200-1800 - Bosmans, J. (Zusterkloosters in de Premonstratenzer Orde, 2015)
Keywords: sint-gerlach

Les saints de Beauport - Bourgès, André-Yves (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Rothenkirchen, St. Maria: Prämonstratenserabtei: Rothenkircherhof, Stadt Kirchheimbolanden, Verbandsgemeinde Kirchheimbolanden, Donnersbergkreis - Burkhart, Ulrich; Werling, Michael (Pfälzisches Klosterlexikon, 2015)
Keywords: rothenkirchen

San Catauru: luogo della memoria. Identità di un Santo. Identità di una contrada, identità di una chiesa - Cavaretta, Irene; Cipriano, Margherita; Cardinale, Ino (Arti Grafiche Abbate, 2015)
Keywords: terrasini

La pierre à Beauport. Un polylithisme coloré - Chauris, Louis (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

La noblesse et Beauport au XIIIe siècle - Coativy, Yves (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

La blanche brebis, l'âne et le bouc: les prémontrés dans la littérature exemplaire au Moyen Âge - Debert, Aline (Actes officiels des 34e et 35e Colloques du Centre d'études et de recherches prémontrées : Sarthe, 2008, Lorraine 2009, 2015)
Keywords: 📚 premonstratensian (general)

Der Cappenberger Barbarossakopf und sein Reliquienkreuz - Dethlefs, Gerd (Westfalen, 2015)
Keywords: cappenberg

Heurts et malheurs d'une abbaye royale navarro-labourdine : Salbatore d'Urdazubi - Duvert, Mikel (Terres de Navarre, 2015)
Keywords: urdax

Die Prämonstratenserinnen im deutschen Sprachraum und ihr Verhältnis zu den geistlichen und weltlichen Herren - Ehlers-Kisseler, Ingrid (Analecta Praemonstratensia, 2015)
Keywords: 🇩🇪 germany (general)

Neuere Forschungen zur Entstehung und Entwicklung der Frauengemeinschaften im Prämonstratenserorden - Ehlers-Kisseler, Ingrid (Zusterkloosters in de Premonstratenzer Orde, 2015)
Keywords: 📚 premonstratensian (general)

Les Chartes de l'abbaye de Beauport des origines à 1305: analyse des données - Evans, Claude (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Histoires d'argent: emprunts et prêts dans les chartes de l'abbaye de Beauport - Evans, K. Paul (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Die Beziehungen zwischen dem Kloster Speinshart und den Markgrafen von Bayreuth - Fuchs, Bernhard (Archiv für die Geschichte von Oberfranken, 2015)
Keywords: speinshart

Erinnerungsstätte und Wahrzeichen. Geschichte und Nachleben des ehemaligen Prämonstratenserstifts St. Marien auf dem Harlungerberg in Brandenburg an der Havel - Gahlbeck, Christian (Die Mark Brandenburg unter den frühen Hohenzollern. Beiträge zur höfischen Kunst und Architektur im 15. Jahrhundert, 2015)
Keywords: brandenburg:st marien

Beauport: architecture, hiérarchie, circulations dans une abbaye prémontrée du XIIIe siècle - Gallet, Yves (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Beauport, le paradis perdu du chanoine Le Sage - Gicquel, Samuel (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Beauport: l'invention d'une histoire - Gondolle, Sophie (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Eine verschwundene Quaternionendarstellung im Kloster Schussenried - Graf, Klaus (Archivalia, 2015)
Keywords: schussenried

F. W. E. Roth und die Briefsammlung des Prämonstratensers Ulrich von Steinfeld - Graf, Klaus (Archivalia, 2015)
Keywords: steinfeld

Déplacer les morts à l'abbaye d'Ardenne. De la réduction de corps à la sépulture secondaire - Guillon, Mark (Déplacer les morts. Voyages, funérailles, manipulations, exhumations et réinhumations, 2015)
Keywords: ardenne

Die Innenrestaurierung der Propsteikirche St. Walburga in Werl: weitere Ergebnisse der Bauforschung - Halekotte, Theo (Werl gestern, heute, morgen. Ein Jahrbuch der Stadt Werl und des Neuen Heimat- und Geschichtsvereins Werl, 2015)
Keywords: werl

Un prémontré au purgatoire: le livre de prières d'Heinrich Österreicher. - Hamburger, Jeffrey F. (Art de l'enluminure, 2015)
Keywords: 📚 premonstratensian (general)

Willem II of Floris de Voogd? Vragen rond een grafmonument en een skelet in de Koorkerk te Middelburg - Henderikx, Peter A. (Bijdragen en mededelingen betreffende de geschiedenis der Nederlanden, 2015)
William II or Florence the Guardian?: Questions about a Tomb and a Skeleton in the Abbey Church at Middelburg Both William II, Count of Holland and Zeeland and King of the Holy Roman Empire (†1256, re-interred 1282) and his brother Florence the Guardian (†1258) are buried in the Norbertine abbey church in Middelburg. In 1817 a skeleton was found in a bricked up niche, along with the remains of a tombstone on which was carved a knightly figure whose shield bears the coat of arms of Holland. Based on the results of an examination of the bones by George J.R. Maat and his team (Leiden University Medical Centre), Henderikx takes it that the skeleton could be either that of the King of the Holy Roman Empire or of Florence the Guardian. Considering that the skeleton, burial space and tombstone formed a coherent whole, and the high-relief on the tombstone almost certainly does not refer to the King of Rome but to his brother, Henderikx concludes that the skeleton must be the earthly remains of Florence the Guardian.
Keywords: middelburg

La situation monastique de la Bretagne jusqu'en 1202, année de la fondation de l'abbaye prémontrée de Beauport - Hillion, Yannick (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Krajiny trí klášteru (Teplá, Chotešov, Vyšší Brod): nástin problematiky - Hlinomaz, Milan (Krajina jako antropologická cítanka, 2015)
Keywords: chotěšov; teplá

Die mittelalterliche Klosteranlage von Sankt Salvator am Steinkart. Eine Spurensuche - Huber, Markus T. (Landkreis Passau, Kulturreferat, 2015)
Keywords: griesbach

Antropologia i arqueologia dels enterraments de l'exterior de l'església de Bellpuig (Artà) - Inglada Grau, Helena; Prats Picó, Noemi; Cardona López, Francisca; Llinàs Riera, Maria; Vila Socias, Llorenç (Bolletí de la Societat Arqueològica Lul·liana, 2015)
Keywords: bellpuig de artá

Des chanoines prémontrés en Goëlo et dans l'ouest de la France - Jeanneau, Cédric (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: goëlo

L'abbaye de Beauport et son insertion en Goëlo: liens avec les autorités ecclésiastiques, appuis aristocratiques et stratégies domaniales - Jeanneau, Cédric (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport; goëlo

Une abbaye prémontrée en Bas-Poitou: Lieu-Dieu-en-Jard - Jeanneau, Cédric (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: lieu-dieu-en-jard

Medieval law and materiality: shipwrecks, finders and property on the Suffolk coast, ca. 1380-1410 - Johnson, Tom (American Historical Review, 2015)
Keywords: leiston

Die Bestattungen beim spätmittelalterlichen Prämonstratenserstift Grobe (Wilhelmshof) auf der Insel Usedom: Ergebnisse der anthropologischen Analysen - Jungklaus, Bettina (Bodendenkmalpflege in Mecklenburg-Vorpommern, 2015)
Keywords: grobe

Zur Namensgebung der Marienkirche Gelnhausen: Zusammenstellung der Bezeichnungen - Kappel, Hans-Henning (Gelnhäuser Geschichtsblätter, 2015)
Keywords: gelnhausen (marienkirche)

Kult świętych w średniowiecznym Nowym Sączy - Kazienko, Ewelina (Nasza Przeszłość. Studia z dziejów Kościoła i kultury katolickiej w Polsce, 2015)
Keywords: nowy sącz

Petersberg, St. Peter: aufgegebene Klostergründung, später Propstei der Prämonstratenserabtei Arnstein: Gemeinde Gau-Odernheim, Verbandsgemeinde Alzey-Land, Landkreis Alzey-Worms - Keddigkeit, Jürgen; Misamer, Julia; Untermann, Matthias (Pfälzisches Klosterlexikon, 2015)
Keywords: petersberg

Politické aspekty ikonografie nástěnných maleb v kapli sv. Michala v premonstrátském klášteře v Lelesu - Kolářová Takácsová, Kornélia (Obrazy uctívané, obdivované a interpretované: Sborník k 60. narozeninám profesora Jana Royta, 2015)
Politische Aspekte der Ikonographie der Wandgemälde in der Michaelskapelle des Prämonstratenserkloster in Leles
Num Pages: 520 Pp.
Keywords: leles

A leleszi premontreiek szalókai birtoklásának háttere - Kovács, Viktória (Történelmi Szemle, 2015)
[The Background to the Landowning of the Premonstratensians of Lelesz at Szalóka] Although the founding charter of the Holy Cross provostry at Lelesz (today Leles, Slovakia) from 1214, of dubious authenticity, has not survived in the original, one of its later transcriptions from 1334 lists among the grants made by bishop Boleslo of Vác in favor of the provostry a possession called Zolunta. The people of Zolunta are reported to have robbed Russian tradesmen, an act later proved by the tradesmen through ordeal in the church of Buda, whereupon Zolunta was adjudicated to them by court ispán (comes curialis) Egyed. The village was eventually bought by the bishop of Vác from the tradesmen for 82 marks. The possession in question has traditionally been identified in the research with Szalonta in the medieval county of Borsod (Hejőszalonta, Hungary). According to Ambrus Pleidell, however, the provostry owned Szalóka (Solovka, Ukraine), which was variously regarded as belonging to the counties of Bereg and Ung in the Middle Ages. In the course of various lawsuits in 1336, 1343 and 1378, the monastery proved its title to Szalóka in Bereg with the founding charter and its later transcriptions. It is likewise Szalóka that is recorded as a possession of the provostry by the tax register of 1550. In order to establish which possession was in fact owned by the monastery of Lelesz, the author examines the charters which have preserved the relevant part of the founding charter, as well as the medieval variants of the names of the two settlements and their history. Two among the three textual traditions of the founding charter (1214/1334/1342/1364/1406, 1214/1334, 1214/1362) contain variants of the toponym Szalonta, which thus probably figured in the charter of 1214 as well. In the summary transcriptions connected to the presentation of titles in lawsuits (1336, 1343, 1378) it is Szalóka which appears without exception. The forms of toponyms, while fairly similar to each other, certainly refer to different settlements. As for Szalonta, prior to 1319 it was owned by the Ákos kindred, and thereafter by Dózsa Debreceni, voevode of Transylvania – consequently, it surely did not belong to the monastery of Lelesz in the early 14th century. Szalóka, on the other hand, was owned in the first half of the 13th century by Artolf of the Aba kindred, from whom it was purchased by the son-in-law of ban Bánk called Simon. In 1270 it was in the possession of Mihály son of Endre of the Rosd kindred, and in 1285 in that of his widow and new husband, Jakab Lónyai. In a protest made before the chapter of Eger in 1302 the provost of Lelesz claimed that Szalóka belonged to his monastery. On the basis of this information, the most probable solution seems to be that, while the provostry had originally come into the possession of Szalonta by virtue of the founding charter, later in the Angevin period it used the document to prove its title to landowning at Szalóka. During the lawsuits, the monastery probably argued that the Zolunta/Zolounta figuring in the charters in fact referred to Szalóka in Bereg.
Keywords: leles

Deutsche Literatur des Mittelalters in Handschriften aus dem Kloster Weißenau - Kruse, Norbert (Ulm und Oberschwaben, 2015)
Keywords: weissenau

Het voormalige Norbertinessenklooster van Gempe ('s Hertogeneiland) in Sint-Joris-Winge - Lani, Stefan van (Zusterkloosters in de Premonstratenzer Orde, 2015)
Keywords: gempe

L'obituaire de l'abbaye de Beauport - Le Goff, Amandine (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Ermida do Paiva: Arquitetura e Escultura - Lopes Cunha, Cláudia Gonçalves (University of Porto, 2015)
Keywords: ermida do paiva

Ke stavu poznání stavebních dejin bý valého kláštera premonstrátek Rosa Coeli v Dolních Kounicích: Nález románského obytného objektu pod stavbou barokního konventu - Merta, David; Peška, Marek (Archaeologia historica, 2015)
[Zum Erkenntnisstand über die Baugeschichte des ehemaligen Prämonstratenserinnenklosters Rosa Coeli in Dolní Kounice]
Keywords: kounice

Majetkové spory zábrdovického kláštera v polovině 15. století - Mlateček, Karel (Vyškovský sborník : sborník Moravského zemského archivu v Brně, Státního okresního archivu Vyškov, 2015)
Keywords: zábrdovice

L'abbaye du Perray-Neuf - Présentation historique et architecturale - Moulin, Jacques (Actes officiels des 34e et 35e colloques du Centre d'Études et de Recherches Prémontrées, 2015)
Keywords: perray-neuf

Życie norbertanek żukowskich w wieku XV i na początku XVI stulecia - Możejko, Beata (Res Gestae, 2015)
Keywords: żukowo

Secessit clarissimi viri ... primogenitus – Fragment einer Grabinschrift in der Klosterkirche Hane - Müller, Gerald F. W. (Jahrbuch für das Land um den Donnersberg, 2015)
Keywords: hane

Meister Eckhart auf der Wartburg: Fundbericht anlässlich der Wiederentdeckung einer frühen Eckhart-Handschrift aus dem Prämonstratenserinnenstift Altenberg im Bestand der Wartburg-Stiftung - Nemes, Balázs J. (Wartburg-Jahrbuch, 2015)
Keywords: altenberg

Prämonstratensische Wege nach Rom: Die Papsturkunden der fränkischen und schwäbischen Stifte bis 1378 - Petersen, Stefan (Böhlau Verlag, 2015)
Keywords: 📚 premonstratensian (general)

Chronologie de l'abbaye du Perray-Neuf - Plouvier, Martine (Actes officiels des 34e et 35e colloques du Centre d'Études et de Recherches Prémontrées, 2015)
Keywords: perray-neuf

Destins croisés des abbayes prémontrées de l'ouest de la France Moyen Âge. La place de Beauport dans le réseau médiéval - Plouvier, Martine (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Belbuc, Belboch, Bialoboki. Über das Projekt zur Erforschung des Prämonstratenserstift - Rębkowski, Marian (Klasztor premonstratensów w Bialobokach. Archeologia i historia, 2015)
Keywords: białoboki

Belbuc, Belboch, Bialoboki. Wprowadzenie do badan klasztoru prem onstratensów - Rębkowski, Marian (Klasztor premonstratensów w Bialobokach. Archeologia i historia, 2015)
Keywords: białoboki

Klasztor premonstratensów w Białobokach: archeologia i historia - Rębkowski, Marian; Biermann, Felix (Instytut Archeologii i Etnologii Polskiej Akademii Nauk : Ośrodek Archeologii Średniowiecza Krajów Nadbałtyckich, 2015)
Das Prämonstratenserstift in Belbuck : Archäologie und Geschichte
OCLC: 911225361
Keywords: białoboki

Der Dom zu Havelberg und sein mittelalterlicher Lettner - Reichel, Antje (Verlag Janos Stekovics, 2015)
Keywords: havelberg

Devon's Torre Abbey: Faith, Politics and Grand Designs - Rhodes, Michael (The History Press, 2015)
Keywords: torre

Imagen religiosa e indumentaria en torno a 1500: las pinturas de Nuestra Señora de Brazacorta (Burgos) - Sanz, María Teresa López de Guereño (Boletín de la Asociación Española de Amigos de la Arqueología, 2015)
Imagen religiosa e indumentaria en torno a 1500: las pinturas de Nuestra Señora de Brazacorta (Burgos)
Keywords: brazacorta

Saint-Pierremont en Lorraine: une abbaye de chanoines réguliers et son pays aux XIIe et XIIIe siècles - Schleef, Yorick (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: saint-pierremont

"... eine böse neuwe zeytung ... ": das Ende des Prämonstratenserinnenklosters Gommersheim - Schnabel, Berthold (Heimatjahrbuch Landkreis Alzey-Worms, 2015)
Keywords: gommersheim

Marienthal, St. Maria: Prämonstratenserinnenstift St. Mariental: Stadtteil Marienthal, Stadt und Verbandsgemeinde Rockenhausen, Donnersbergkreis - Schnabel, Berthold; Wenz, Martin; Untermann, Matthias (Pfälzisches Klosterlexikon : Handbuch der pfälzischen Klöster, Stifte und Kommenden, 2015)
Keywords: marienthal

Münsterdreisen, St. Saturnius: Frauengemeinschaft, später (Regular-)Kanonikerstift, dann Prämonstratenserabtei: Münsterhof, Gemeinde Dreisen, Verbandsgemeinde Göllheim, Donnersbergkreis - Schnabel, Berthold; Werling, Michael (Pfälzisches Klosterlexikon, 2015)
Keywords: münsterdreisen

Laval Dieu: Une abbaye prémontrée dans les Ardennes, 1128-1791 - Schrub, Bernard (CREHLOM, 2015)
Keywords: laval dieu

Die Abtei von Saint-Martin in Tournai im Spannungsfeld zwischen Cluny, Citeaux und Prémontré? Zur Konstruktion kollektiver Identität im Liber de restauratione Hermanns von Tournai - Sellner, Harald (Identität und Gemeinschaft: Vier Zugänge zu Eigengeschichten und Selbstbildern institutioneller Ordnungen, 2015)
Keywords: 📚 premonstratensian (general)

Abbaye Saint Nicolas de Septfontaines en Bassigny. Dix siècles d'histoire-Essai de chronologie - Selva, R. de (Actes officiels des 34e et 35e Colloques du Centre d'études et de recherches prémontrées : Sarthe, 2008, Lorraine 2009, 2015)
Keywords: septfontaines en bassigny

Komplexní obnova konventního kostela Narození Panny Marie v Želivě restaurování hlavního oltáře - Severa, Petr (Památky Vysočiny, 2015)
OCLC: 1224326282
Keywords: želiv

Bayham Abbey, East Sussex Historic Buildings Watching Brief - Shapland, M. (2015)
Keywords: bayham

Flora in Stein: Florale Motive im Bauschmuck im Kloster Jerichow - Telemann, Josefine (Lapidarium Jerichowense, 2015)
Keywords: jerichow

La commémoration des morts dans la liturgie de Prémontré: les trois obituaires de l'abbaye de Ninove. Quelques remarques à l'occasion de l'édition critique du texte - Van De Perre, Dirk (Actes officiels des 34e et 35e Colloques du Centre d'études et de recherches prémontrées : Sarthe, 2008, Lorraine 2009, 2015)
Keywords: ninove

Hermoesestraat 17 in Zennewijnen - Van Rooij, J.A.G. (DANS Data Station Archaeology, 2015)
Keywords: zennewijnen

Majetkový vývoj kláštera Louka u Znojma do husitských válek - Vohryzek, Stanislav (2015)
Cílem článku je podat přehled majetkového vývoje premonstrátského kláštera v Louce u Znojma od jeho založení roku 1190 knížetem Konrádem II. Otou do počátku husitských válek. Základním pramenem pro poznání vývoje klášterního majetku jsou listiny klášterního archivu. První část práce v chronologické řadě pojednává o založení kláštera a jednotlivých panovnických i šlechtických donacích. Velká pozornost je věnována zejména určení jednotlivých lokalit, které jsou zmiňovány v těchto listinách. Druhá část se zabývá vztahy kláštera ke kostelům, které mu byly inkorporovány již od počátku, nebo u nichž získal v průběhu času desátky či patronátní práva a inkorporace dosáhl později. Podán je zde i výčet sporů kláštera o tyto kostely a jejich desátky s jinými duchovními institucemi. Exkurz je věnován vztahu kláštera a města Znojma, např. problematice klášterních majetků, o které klášter přišel při vzniku města, způsobem jeho odškodnění, různým pozdějším vzájemným sporům, vlivu kláštera na ustanovování městského rychtáře apod.
Keywords: louka

Založení kláštera v Nové Ríši a otázka zakladatelských práv k nemu do válek husitských - Vohryzek, Stanislav (Casopis matice moravské, 2015)
[The Foundation of the Monastery in Nová Ríše and the Question of Founder Rights over It]
Keywords: nová říše

Voix et présence. Lettres historiées d'un missel du XIIIe siècle à l'usage de Notre-Dame de Belval (Charleville-Mézières, BM, ms. 243) - Voyer, Cécile (Le manuscrit, entre écriture et texte, 2015)
Keywords: belval

Von adeliger Gründerin, erfundenen Meisterinnen und bürgerlicher Liquidierung 1808: das Chorfrauenstift Nieder-Ilbenstadt - Wolf, Jürgen Rainer (Analecta Praemonstratensia, 2015)
Keywords: niederilbenstadt

Norbert Ksantenskiy i sv. Avgustin. K voprosu ikonografii miniatyury v rukopisi «Vita beati Norberti» iz sobraniya Bavarskoy gosudarstvennoy biblioteki/Норберт Ксантенский и св. Августин. К вопросу иконографии миниатюры в рукописи «Vita beati Norberti» из собрания Баварской государственной библиотеки - Zotova, Yelizaveta Valentinovna (Observatoriya kul'tury, 2014)
The article is devoted to the study of the only surviving illuminated manuscript of the life of Norbert of Xanten. The author analyzes the iconography of the miniature from this manuscript, compares it with miniatures and other illuminated lives of the holy archbishops, manuscripts of the works of St. Augustine, created in Germany in the same period (XII century).
Number: 6
Keywords: 👤 norbert of xanten

Rhetorics of Sanctity: Christina of Hane in the Early Modern Period with a Comparison to a Mary Magdalene Legend - Kirakosian, Racha (Oxford German Studies, 2014)
This study presents the particular case of the medieval mystic Christina of Hane in the Early Modern transmission to uncover the dynamics of sanctity across traditional period boundaries. It discusses the interest of copying and transmitting the Life of this local saintly figure with a legend on Mary Magdalene’s conversion in the sixteenth century. Christina of Hane’s medieval Life becomes refashioned in a seventeenth-century Flemish text that addresses the religious needs of its time, stressing apolitical forms of devotion such as prayers for the souls in purgatory.
Keywords: 👤 christina of hane

Složení a degradace omítek historického objektu Kláštera Želiv - Rezek, P.; Martinec, P. (Koroze a ochrana materialu, 2014)
Composition and degradation of plasters from the historical Želiv monastery. Příspěvek se zabývá charakteristikou omítek odebraných v historickém objektu Kláštera Želiv. Cílem tohoto výzkumu bylo získat informace o původních surovinách a stanovit druh poškození na fasádě zkoumaného objektu. Bylo použito zejména termické analýzy a infračervené spektrometrie, jež umožňují identifi kovat materiály pojiv, v některých případech i pomoci určit druh jejich poškození (resp. zasolení). Byly zkoumány 4 vzorky pojiv omítek. Analýzy historických omítek mohou případně v budoucnu napomoci vyhledat a aplikovat kompatibilní hmotu. Byly kvalitativně i kvantitativně stanoveny primární složky odebraných omítek a stanoveny hlavní příčiny jejich degradace. Komplexní hodnocení složení a degradace omítek vyžaduje využití široké škály analytických metod.
Keywords: želiv

Les incroyables trésors de la chapelle Saint-Blaise (Le Parisien, 2014)
Keywords: silly-tillard

Which is the Greatest - Kirakosian, Racha (Medieval Mystical Theology, 2014)
This paper deals with the medieval theological debate on the primacy of knowledge, love, or enjoyment of God by comparing the biography of the Premonstratensian nun Christina of Hane with the German mystical writings of the Dominican preacher and scholar Meister Eckhart. It shows the ways in which female vernacular thought engaged with a primarily scholastic and male-dominated debate and suggests a performative understanding of the female mystical account. Challenging existing presumptions about Christina’s mystical biography as being inconsistent and composed by several authors, the results of this research demonstrate to what extent the text can still be considered cohesive when discarding gender specified authorial conceptions which cannot be determined in this case.
Publisher: Routledge _eprint: https://doi.org/10.1179/2046572614Z.00000000016
Keywords: 👤 christina of hane

Future of Park Abbey Windows Unclear (Vidimus, 2014)
Keywords: park

Leiston: Are these the bones of devil dog, Black Shuck? - Potter, Tom (The East Anglian Daily Times, 2014)
Keywords: leiston

Sept-Fontaines : l'abbaye des Sept-Fontaines a traversé près de dix siècles d'histoire - Menvielle, Virginie (La Semaine des Ardennes, 2014)
Keywords: septfontaines en thiérache

L'abbaye Notre-Dame de Septfontaine - Theret, Jacques (Chez nous, 2014)
Keywords: septfontaines en thiérache

Archeologists to revisit medieval site for second ‘crowdfunded’ dig - Potter, Tom (The East Anglian Daily Times, 2014)
Keywords: leiston

De la circulation des "locis sanctis" - le Mons Sion à Prague - Benešovská, Klára (Convivium, 2014)
In 1143, a Premonstratensian abbey with a church dedicated to Mary was founded on Prague's Strahov hill, and the place was called Mons Sion. One of its founders was Jindřich Zdík, a Moravian bishop, who had been a member of the chapter of the Holy Sepulchre in Jerusalem in 1137-38. After returning to Bohemia, Bishop Zdik worked to implement church reforms with the help of regular canons and, later, assistance from the Premonstratensians from Steinfeld. Mons Sion evoked Jerusalem not only through its placement and dedication, but also through its monumental architecture without decoration: its plainness, displaying without distraction the building's harmonious proportions and technically perfect construction, was a response to the proclaimed reforms. the workshop of the abbey played a major role in the twelfth-century building boom of Romanesque Prague. The route of the Palm Sunday pilgrimage processions between the Přemyslid castle and Strahov also confirmed the importance of Mons Sion. The pilgrimages were patterned after the Jerusalem processions between the Holy Sepulchre and Mount Zion. Mons Sion, the Přemyslid castle and the Knights of St. John thus formed a symbolic triangle on the left bank of Vltava river, connected by a new stone bridge to the settlement of the right bank and the other Přemyslid residence, Vyšehrad.
Publisher: Masarykova Univerzita
Keywords: strahov

Schrift- und Schreibmystik. Christina von Hane - Suerbaum, Almut M. V. (Oxford University, 2014)
The subject of my thesis is a little-studied hagiographical work that gives important insights into rewriting processes and their significance in medieval textual culture. The anonymous Life of Christina of Hane, a thirteenth-century Premonstratensian nun from the Palatinate, is an example of bridal
Keywords: 👤 christina of hane

Bibliotheca Laureshamensis – Digital: Virtuelle Klosterbibliothek Lorsch (2014)
Keywords: lorsch

Von Krautgärten, Äckern, Gülten und Hühnern: Studien zur Besitz- und Wirtschaftsgeschichte des Prämonstratenserstifts Adelberg im Mittelalter 1178 - 1535 - Albus-Kötz, Stefanie (Jan Thorbecke Verlag, 2014)
Keywords: adelberg

Zur Sachkultur im Prämonstratenser-Stift Jerichow vor der Auflösung des Konvents im 16. Jahrhundert - Alper, Götz (Mitteldeutschland im Zeitalter der Reformation, 2014)
Keywords: jerichow

Premontrei prépostságok a középkori Magyarországon, különös tekintettel a Kaposfői Szent Benedek prépostságra - Aradi, Csilla M. (A Kaposvári Rippl-Rónai Múzeum Közleményei, 2014)
Keywords: kaposfő; 🇭🇺 hungary (general)

Premontrei monostor feltárása Bárdudvarnokon - Aradi, Csilla M.; Molnár, István (Archaeologia - Altum Castrum Online, 2014)
Keywords: kaposfő

Zum steten frommen Andenken an das 700jährige Jubiläum des Prämonstratenser-Reichsstifts Schussenried - Beck, Paul A. (Diözesan-Archiv von Schwaben : Organ für Geschichte, Altertumskunde, Kunst und Kultur der Diözese Rottenburg und der angrenzenden Gebiete, 2014)
Place: Stuttgart Publisher: Dt. Volksblatt, 1884-1907
Keywords: schussenried

Die neuesten Ergebnisse über den Dom zu Riga - Bergholde, Agnese (Beiträge zur Tagung vom 1. und 2. September 2011, Backsteinfunde der Archäologie, Beiträge zur Tagung vom 6. und 7. September 2012, Klosterformat und Klöster, 2014)
Keywords: rīga

Seals of Moravian Premonstratensian canonries in the period from the second half of the fifteenth century until the end of the sixteenth century - Bolom-Kotari, Martina (Analecta Praemonstratensia, 2014)
Keywords: 🇨🇿 czechia (general)

Hane, St. Maria, Augustinerchorherrenstift, später Prämonstratenserinnenstift - Burkhart, Ulrich; Heberer, Pia (Pfälzisches Klosterlexikon, 2014)
Keywords: hane

Prémontré's Ordestatuten 1505, 1509 gedrukt - Coppens, C. (Bibliotheek van de Abdij van Park, 2014)
Keywords: ⚖️ chapters and statutes

Az ócsai református (egykor premontrei) templom építéstörténetének vázlata - Csoltkó, Emese (A múltnak kútja: Fiatal középkoros régészek V. konferenciájának tanulmánykötete, 2014)
[Sketches to the Building History of the Calvinist (Former Premonstratensian) Church of Ócsa]
Keywords: ócsa

Du temps où les Prémontrés s'implantèrent en Pays Basque - Duvert, Mikel (Terres de Navarre, 2014)
Keywords: 🇪🇸 spain (general); 🇫🇷 france (general)

Écrire à Verdun au XIIIe siècle. Le cartulaire de l'abbaye prémontrée Saint-Paul de Verdun. Approche codicologique et paléographique - Évrard, Jean-Pol (L'écrit et le livre peint en Lorraine, de Saint-Mihiel à Verdun (IXe-XVe siècles), 2014)
Keywords: verdun

Die Prämonstratenserpropstei St. Jakob im Prättigau ca.1222–1526 - Fischer, Albert (Bischöfliches Archiv Chur, 2014)
Keywords: prättigau

A Privilege of Pope Innocent III for the Premonstratensian House of Bellpuig de les Avellanes - Freedman, Paul; Smith, Damian (Römische Historische Mitteilungen, 2014)
Siglenverzeichnis Bericht des Historischen Instituts beim Österreichischen Kulturforum in Rom für das Studienjahr 2011/2012 Astrid Larcher - Manuele Laimer, Ascoli Satriano, Gianera Piccola. Vorbericht zu den Grabungskampagnen 2010-2012 Paul Freedman - Damian Smith, A Privilege of Pope Innocent III for the Premonstratensian House of Bellpuig de les Avellanes Rudolf S. Stefec, Die Überlieferung der Deklamationen Polemons Petr Maťa, The false Orsini from over the Alps: Negotiating aristocratic identity in late medieval and early modern Europe Tomáš Černušák, Die Böhmische Kammer als Thema der Prager Nuntiatur zu Beginn des 17. Jahrhunderts Alessandro Metlica, Il Parnasso dell `Istro. Eugenio di San Giuseppe, Caramuel y Lobkowitz e la prima accademia italiana di Vienna (1657) Péter Tusor, Kardinalsnominierungen durch das Haus Habsburg im 17. Jahrhundert Rita Tolomeo, Potenze Protetrici e Unionismo nelle Terre Bulgare Andreas Gottsmann, "Warum lässt uns der Hl.Stuhl im Stich?" Die vatikanische Haltung zur Regierung Schuschnigg hinsichtlich Restauration und staatlicher Selbstständigkeit Inge Podbrecky, Gio Ponti in Wien. Das italienische Kulturinstitut im Palais Lützow-Fürstenberg Zusammenfassungen
Keywords: bellpuig de las avellanes

El monasterio premostratense de Santa María de La Vid durante los siglos XIV y XV: formas de explotación del dominio - Fuertes, Maria Teresa Angulo (Espacio Tiempo y Forma. Serie III, Historia Medieval, 2014)
En el presente artículo analizamos la evolución de las formas de explotación del dominio de un importante monasterio premostratense castellano, el de Santa María de La Vid, durante la baja Edad Media. En el siglo XV cambia la dinámica económica del cenobio que pasa de administrar directamente sus granjas a darlas a censo enfitéutico, bien a particulares, bien a los concejos de los lugares en los que se encontraban ubicadas. Se analizan las razones de este cambio y se compara esta evolución con la de otros monasterios y conventos peninsulares así como las razones que los diferentes estudiosos señalan para esta transformación en la forma de organización económica de los cenobios mencionados.This article examines the evolution of various forms of domain management by an important Castilian Premonstratensian monastery, Santa María de la Vid, during the late Middle Ages. During the fifteenth century an important economic shift takes place as the monastery relinquishes direct management of its domains and leases the land through emphyteutic tenure either to individuals, or to the town councils located near their land. The reasons for this change will be examined. Morevoer, the development of this phenomenon will be compared to that of other Peninsular monasteries and convents. Finally, the motives given by specialists for the shift in economic organization of these monasteries will be assessed.
Keywords: la vid

Visitationsrecht des Abts Leonard Dürr von Adelberg über die Prämonstratenser-Ordensprovinz Schwaben 1518 - Giefel, Joseph Anton (Diözesan-Archiv von Schwaben : Organ für Geschichte, Altertumskunde, Kunst und Kultur der Diözese Rottenburg und der angrenzenden Gebiete, 2014)
Place: Stuttgart Publisher: Dt. Volksblatt, 1884-1907
Keywords: adelberg; 🇩🇪 germany (general)

‘Ante omnia, fratres carissimi, diligatur Deus, deinde proximus’: Herman/Judah’s Opusculum de conversione sua Re-examined - Hames, Harvey J. (Conﬂict and Religious Conversation in Latin Christendom: Studies in Honour of Ora Limor, 2014)
Keywords: 👤 hermann of cologne

Neue Untersuchungen im Süd-West-Flügel der Prämonstratenserabtei Speinshart (Lkr. Neustadt a. d. Waldnaab) - Heidenreich, Anja (Beiträge zur Archäologie in der Oberpfalz und in Regensburg, 2014)
Keywords: speinshart

De graven en grafmonumenten van graaf/rooms-koning Willem II en Floris de Voogd in het koor van de abdijkerk Middelburg - Henderikx, Peter A. (Archief: mededelingen van het Koninklijk Zeeuwsch Genootschap der Wetenschappen, 2014)
Keywords: middelburg

Neues vom untergegangenen Prämonstratenserstift Heiligenberg bei Bruchhausen-Vilsen - Hucker, Bernd Ulrich (Althannoverscher Volkskalender, 2014)
Keywords: heiligenberg

Getuigenissen van een groots verleden. Materiële sporen van de Antwerpse Sint-Michielsabdij - Janssens, Herman (Abdij Averbode, 2014)
Keywords: antwerp

Manuscript Work of the Zwierzyniec Norbertine Nuns of the Seventeenth and Eighteenth Century - Kaczor-Scheitler, Katarzyna (Analecta Praemonstratensia, 2014)
Keywords: zwierzyniec

Die Prämonstratenser-Stiftskirche Jerichow und der frühe Backsteinbau in der Altmark und im Jerichower Land - Kaufmann, Damian (Beiträge zur Tagung vom 1. und 2. September 2011 Backsteinfunde der Archäologie; Beiträge zur Tagung vom 6. und 7. September 2012 Klosterformat und Klöster, 2014)
Keywords: jerichow

Poutní a farní chrám Páně Jména Panny Marie ve Křtinách - Kavička, Karel (Kartuziánské nakladatelství, 2014)
Keywords: křtiny

Kleinbockenheim, St. Martin, Propstei "Auf dem Berg" des Prämonstratenserstifts Wadgassen - Keddigkeit, Jürgen; Lagemann, Charlotte (Pfälzisches Klosterlexikon, 2014)
Keywords: kleinbockenheim

Enkenbach, St. Maria, Prämonstratenserinnenstift, später Prämonstratenserpropstei - Keddigkeit, Jürgen; Untermann, Matthias (Pfälzisches Klosterlexikon, 2014)
Keywords: enkenbach

Kaiserslautern, St. Maria, Hospitalkloster, später Prämonstratenserstift bzw. -kloster, dann Kollegiatstift St. Marien und St. Martin - Keddigkeit, Jürgen; Wenz, Martin; Untermann, Matthias (Pfälzisches Klosterlexikon, 2014)
Keywords: kaiserslautern

Premontrei breviárium és collectionale – Premonstratensian Breviary and Book of Collects - Knapp, Eva (Kép és kereszténység = Image and Christianity, 2014)
Keywords: 📚 premonstratensian (general)

Premonstrátský klášter Louka u Znojma v době předbělohorské (1526-1620) - Kohoutek, Michael (Masaryk University, 2014)
Keywords: louka

Festsaal und Abtei des Klosters Weißenau - Krins, Hubert (Denkmalpflege in Baden-Württemberg : Nachrichtenblatt der Landesdenkmalpflege, 2014)
Place: Stuttgart Publisher: Landesamt ; Heidelberg : arthistoricum.net, 1972-
Keywords: weissenau

Archeologische begeleiding Woldjerweg 3 en 5 te Wittewierum, gemeente Ten Boer (GR) - Krol, T.N. (DANS Data Station Archaeology, 2014)
Keywords: bloemhof

Børglum domkirke og kloster i middelalderen - Krongaard Kristensen, Hans (Vendsyssel Historiske Museum, 2014)
Keywords: børglum

De abdij van Park en haar historische bibliotheek - Lani, Stefan van (Bibliotheek van de Abdij van Park, 2014)
Keywords: park

Kriegswahrnehmung und Friedensbemühung bei den frühen Prämonstratensern - Leinsle, Ulrich Gottfried (Friedensethik im frühen Mittelalter: Theologie zwischen Kritik und Legitimation von Gewalt, 2014)
Keywords: 📚 premonstratensian (general)

Die Puchberger und das Prämonstratenserstift Osterhofen - Lickleder, Hermann ("... und es hat doch was gebracht !" Festschrift für Karl Schmotz zum 65. Geburtstag, 2014)
Keywords: osterhofen

Quellen zur Geschichte des Stiftes Flaesheim im 13. Jahrhundert (III) - Lindken, Theodor; Schwabe, Gabriele (Vestische Zeitschrift, 2014)
Keywords: flaesheim

Thomas Son of Gospatric and the Premonstratensian Canons of Preston Patrick & the Nature of Shap Abbey's Link with the Westmorland Township After c.1201 to 1540 - Lucas, Peter (PJYL Publishing, 2014)
Keywords: preston patrick; shap

Súkromný archív Leleského konventu z pohľadu stredovekej diplomatiky - Maretta, Robert Gregor (Historia Ecclesiastica, 2014)
Keywords: leles

Évolution et signification des accensements perpétuels et viagers de l'abbaye d'Humilimont (1250-1350) - Morard, Nicolas (Mémoires de la Société pour l'histoire du droit et des institutions des anciens pays bourguignons, 2014)
Keywords: humilimont

Kirche oder Schloss?: das frühere Prämonstratenserkloster Mildenfurth bei Wünschendorf - Nagel, Franz (Heimat Thüringen, 2014)
Keywords: mildenfurth

Pokračování výzkumu v areálu premonstrátské kanonie v Teplé - Nováček, Karel; Široký, Radek; Starková, Lenka (2014)
Keywords: teplá

Der "ordinarius loci" als Problem: Bischof Embricho von Würzburg und die Anfänge der Prämonstratenserstifte Oberzell, Veßra und Tückelhausen - Petersen, Stefan (Jahrbuch für fränkische Landesforschung, 2014)
Keywords: oberzell; tückelhausen; veßra

Die Rechtsstellung des Prämonstratenserinnenstifts Hausen gegenüber Bischof, Vogt und Vaterabt - Petersen, Stefan (Mainfränkisches Jahrbuch für Geschichte und Kunst, 2014)
Keywords: hausen

Fast 800 Jahre Marienverehrung: das Kloster Maria Engelport ist ein seit Jahrhunderten bekannter Wallfahrtsor - Pies, Norbert J. (Jahrbuch für den Kreis Cochem-Zell, 2014)
Keywords: engelport

Nález stredovekého pečatidla hodnoverného miesta jasovského konventu premonštrátov z konca 13. storočia - Ragač, Radoslav (Studia historica Tyrnaviensia, 2014)
The discovery of a late 13th-century seal of authentication at Jasov Premonstratensian convent
Keywords: leles

The foundation by King Wladyslaw Jagiello of the Premonstratensian Abbey in Nowy Sacz and the role of John the Eremit - Rajman, Jerzy (Analecta Praemonstratensia, 2014)
Keywords: nowy sącz

Middeleeuwse muurschilderingen in de Bergkerk in Deventer - Rijn, Elselien van (Analecta Praemonstratensia, 2014)
Keywords: deventer

Rodungsinsel, Kloster, Raststation: die Ausgrabungen des hochmittelalterlichen Klosters Elisabethenzell - Rosmanitz, Harald (Bayerische Archäologie, 2014)
Keywords: einsiedel

Kirchliche Gebäude „Auf dem Berg“ in Niedergründau - Rückriegel, Erwin (Zentrum für Regionalgeschichte (Gelnhausen). Mitteilungsblatt, 2014)
Keywords: niedergründau

Klöster in Oberschwaben: Wiblingen, Schussenried, Ochsenhausen - Sandtner, Claudia (Deutscher Kunstverlag, 2014)
Keywords: schussenried

Gommersheim, St. Maria und Johannes Ev., Prämonstratenserinnenkloster - Schnabel, Berthold; Werling, Michael (Pfälzisches Klosterlexikon : Handbuch der pfälzischen Klöster, Stifte und Kommenden, 2014)
Keywords: gommersheim

Kloster und Wissen - die Arnsteinbibel und ihr Kontext im frühen 13. Jahrhundert - Schonhardt, Michael (Rombach, 2014)
Keywords: arnstein

Monuments in linen: a thirteenth-century embroidered catafalque cover for the members of the Beata Stirps of Saint Elizabeth of Hungary - Seeberg, Stefanie (Dressing the Part: Textiles as Propaganda in the Middle Ages, 2014)
Num Pages: 213 Pp.
Keywords: altenberg

Textile Bildwerke im Kirchenraum: Leinenstickereien im Kontext mittelalterlicher Raumausstattungen aus dem Kloster Altenberg/Lahn - Seeberg, Stefanie (Imhof, 2014)
Keywords: altenberg

L'abbaye de Lieu-Restauré, Un demi-siècle de sauvegarde et de restauration - Smajda, Philippe (CAHMER, 2014)
Keywords: lieu-restauré

Renaissance de La Grange de Durance - Trézéguet, Jean-Louis (Revue de l'Agenais, 2014)
Keywords: durance

Bibliotheek van de Abdij van Park - Van Bragt, Jozefa (Peeters, 2014)
Keywords: park

.. tho memorie vor dat semptlikegeschlechte ... Stiftisches Leben und religiöser Alltag adeliger Konventualinnen aus der Familie von Backem-Unverzagt im Frauenkonvent Stoppenberg - Vauseweh, Arno; Vauseweh, Ramona (Vestische Zeitschrift, 2014)
Keywords: stoppenberg

Působení premonstrátů v Litomyšli v době biskupství (1344-1421) - Večeře, Vojtěch (Pomezí Čech, Moravy a Slezska : sborník prací ze společenských a přírodních věd, 2014)
Keywords: litomyšl

Necessary Priests and Brothers: Male-Female Cooperation in the Premonstratensian Women’s Monasteries of Füssenich and Meer, 1140-1260 - Wolbrink, Shelley Amiste (Partners in spirit : women, men, and religious life in Germany, 1100-1500, 2014)
Keywords: füssenich; meer

L'abbaye du Mont-Saint-Martin - Woznicki, Éric (Éd. Communauté de communes du pays du Vermandois, 2014)
Keywords: mont-saint-martin

Kostol Nanebovzatia Panny Márie v Šahách. Od výstavby stredovekého kostola k výstavbe novovekého - Žažová, Henrieta (Studia historica Tyrnaviensia, 2014)
Die Mariä-Himmelfahrt-Kirche in Šahy. Vom Aufbau der mittelalterlichen Kirche bis zum Aufbau des neuzeitlichen Sakralhaus
Keywords: šahy

Selbolder Regesten : zur Geschichte von Reichsgericht und Stift Selbold in den Jahren 1108-1598 unter besonderer Berücksichtigung der Pfarrei Gelnhausen - Zieg, Michael (Verlag Dr. Kovač, 2014)
Keywords: selbold

Inwentarz dóbr konwentu zwierzynieckiego w roku Pańskim 1722 spisany - Kazusek, Szymon (Nasza Przeszłość, 2013)
The subject of this publication is the only remaining early-modern inventory of the estates of the convent of Premonstratensians at Zwierzyniec near Cracow. This manuscript contains the description of the real estates in twenty villages being in the property of the Zwierzyniec convention in 1722. The inventory is an excellent source for the research on the farm economy in convent estate. The names of convent villages which the described real estates come from have in huge majority endured until contemporary times. At present some places are within the administrative borders of Cracow, Krzeszowice or Będzin, other exist under previous or modified names, whereas one of the described villages (Zakościele) has not remained until present times. Analysing the content of the inventory it is possible to obtain detailed information about the size, the state and the organisation of the buildings that were convent property, as well as about the leases and their financial aspects. The image emerging after studying the inventory shows a wide diversity of technical condition of farm buildings. What is more, the presented description includes information about buildings in very bad state as well as about renovated or new ones.
Keywords: zwierzyniec

Sainte-Marie de Pleine-Selve en Gironde : nouvelles recherches sur une abbaye méconnue de l’ordre de Prémontré - Masson, Juliette (Bulletin du centre d’études médiévales d’Auxerre | BUCEMA, 2013)
L’opération archéologique sur le site de l’abbaye de Pleine-Selve a été programmée dans le cadre d’un doctorat portant sur les fondations liées à l’archevêque de Bordeaux Geoffroy du Loroux (1136-1158) . Seuls subsistent aujourd’hui des vestiges de l’église abbatiale, les bâtiments conventuels ayant totalement disparu. Deux sessions ont été menées en 2007 et en 2008, financées par le Service régional de l’archéologie d’Aquitaine et le Conseil général de Gironde, pour conduire une étude arché...
Keywords: pleineselve

A Norbert for England: Holy Trinity and the Invention of Robert of Knaresborough - Easterling, Joshua (Journal of Medieval Monastic Studies, 2013)
This essay considers the relationship between two monastic vitae and their historical subjects. The prose vita of the English hermit Robert of Knaresborough that is extant in London, British Library, MS Egerton 3143 contains a number of passages borrowed from the Vita B of Norbert of Xanten, the founder of Premontre. These two otherwise unaffiliated figures of religious reform are connected through Robert’s biographer, most likely a brother of the late-established Trinitarian Order, who extracted key details from Norbert’s vita to shape Robert in the founder’s image. In Egerton’s prose vita, Robert is ultimately made to serve as a legitimate origin for, and as a founder of, the Trinitarian Order at Knaresborough.
Publisher: Brepols Publishers
Keywords: 👤 norbert of xanten

Prämonstratenserkloster Heiligenthal (Heimat- und Kulturverein Gellersen, 2013)
Keywords: heiligenthal

Willkommen in Kloster Oelinghausen (2013)
Keywords: oelinghausen

Le domaine de l'abbaye Notre-Dame de Bonne-Espérance et la paroisse de Gentinnes - Annaert, Philippe (Revue d'histoire du Brabant wallon, 2013)
Keywords: bonne-espérance

Fverte como vn león: el Monasterio de San Leonardo de Alba de Tormes entre la historia y la leyenda - Arnaiz Ecker, Juan José (Ediciones de la Diputación de Salamanca, 2013)
OCLC: 870173959
Keywords: alba de tormes

Bases et chapiteaux inédits de l'ancienne abbaye de la Case-Dieu - Balagna, Christophe (Actes de la première journée de l'Archéologie et de l'Histoire de l'Art de l'Isle-Jourdain (2012), 2013)
Keywords: case dieu

Recherches et découvertes archéologiques récentes à l’abbaye de Beauport (1995-2012) - Ballini, Annie-Claude (Mémoires de la société d'histoire et d'archéologie de Bretagne., 2013)
Keywords: beauport

Kloster Schäftlarn und die Entstehung der Stadt München - Bauer, Richard (Historiker) (Studien und Mitteilungen zur Geschichte des Benediktinerordens und seiner Zweige, 2013)
Keywords: schäftlarn

Die Stiftspfarrei Ilbenstadt: konfessionelle Konflikte zwischen Kurmainz und Burg Friedberg - Bewerunge, Norbert (Archiv für mittelrheinische Kirchengeschichte, 2013)
Keywords: ilbenstadt

De Norbertijnen van de O.-L.-Vrouwabdij van Mol-Postel: biografisch lexicon 12de - 21ste eeuw - Billiaert, Ivo Reginald (Studium Generale, 2013)
Keywords: postel

Uzos da Igreia da Ermida do Paiva - Carvalhal, Marta; Azevedo, Eufemia (Junta de Freguesia da Ermida, 2013)
Keywords: ermida do paiva

Keferloh: Nebenkirche St. Aegidius - Dennemarck, Hans-Jürgen; Jocher, Norbert (Erzbischöfliches Ordinariat, Ressort Bauwesen und Kunst, 2013)
OCLC: 873393560
Keywords: keferloh

Das Verhältnis der Mainzer Erzbischöfe zu den Prämonstratensern im Mainzer Schisma und seine Vorgeschichte - Ehlers-Kisseler, Ingrid (Analecta Praemonstratensia, 2013)
Keywords: 🇩🇪 germany (general)

Über den Dächern von Hüttengesäß: der Kirchturm der evangelischen Kirche Hüttengesäß und seine Glocken - Erdt, Reiner (Ronneburger Heimatblätter, 2013)
Keywords: hüttengesäß

Activités autre-Manche des cisterciens de Bégard et des prémontrés de Beauport des origines à 1414 - Evans, Claude (Mémoires de la Société d'histoire et d'archéologie de Bretagne, 2013)
Keywords: beauport

Das vergessene Kloster in Hopels: Beitrag zur Klostergeschichte des Prämonstratenserordens in Ostfriesland - Frees, Karl-Heinz (s.n., 2013)
Keywords: hopels

Abbaye Notre-Dame du Lieu-Dieu-en-Jard - Gilbert, Pierre (Patrimoine du pays jardais, 2013)
Keywords: lieu-dieu-en-jard

L'institutionalisation des religieuses dans les ordres de Prémontré et de Cîteaux (XIIe-XIlle siècles) - Grélois, Alexis (La place et le rôle des femmes dans l'histoire de Cluny : en hommage à Ermengarde de Blesle, mère de Guillaume le Pieux : actes du colloque de Blesle des 23 et 24 avril 2010, 2013)
Keywords: 📚 premonstratensian (general)

A 14th-Century Sculpted Arcade from Coverham Abbey - Harrison, Stuart A. (Journal of the British Archaeological Association, 2013)
Keywords: coverham

De invloed van de abdij van Floreffe in Houthalen en Overpelt - Hendriks, Giel (Invloed van Waalse norbertijnenabdijen in Limburg: Beaurepart en Floreffe, 2013)
Keywords: floreffe

Westbauten als Orte von Totengedenken: Konzepte zur memoria im Westbau des Klosterbasilika Ilbenstadt und im Westchor des Naumburger Doms - Heß, Pascal (Saale-Unstrut-Jahrbuch. Jahrbuch für Kulturgeschichte und Naturkunde der Saale-Unstrut-Region, 2013)
Keywords: ilbenstadt

Beaurepart - Janssens, Herman (Invloed van Waalse norbertijnenabdijen in Limburg: Beaurepart en Floreffe, 2013)
Keywords: beaurepart

De abdij van Floreffe (1121-1796): Beknopte situatieschets - Janssens, Herman (Invloed van Waalse norbertijnenabdijen in Limburg: Beaurepart en Floreffe, 2013)
Keywords: floreffe

Invloed van Waalse norbertijnenabdijen in Limburg : Beaurepart en Floreffe - Janssens, Herman (Werkgroep Norbertijner geschiedenis in de Nederlanden, 2013)
Keywords: beaurepart; floreffe

Die Wirtschaft der Steinfelder Prämonstratenser - Joester, Ingrid (Analecta Praemonstratensia, 2013)
Keywords: steinfeld

A türjei premontrei prépostság templomának falkép-restaurátori kutatása - József, Lángi (Ko kövön: David Ferenc 73. születésnapjára, 2013)
[Die Erforschung der Wandmalereien und Fassungen in der Kirche der Prämonstratenser-Propstei zu Türje]
Keywords: türje

Leitzkau: Stiftskirche "Sancta maria in monte" - Knape, Rose-Marie (Straße der Romanik: eine Entdeckungsreise ins Deutsche Mittelalter, 2013)
Keywords: leitzkau

Drei Ablaßurkunden für das Prämonstratenserstift Pöhlde aus dem 13. Jahrhundert - Könighaus, Waldemar (Archiv für Diplomatik, 2013)
Keywords: pöhlde

Vlastnosti historického zdicího materiálu - Krejčí, Šárka (Technická univerzita Ostrava, 2013)
Koncentrace památkově chráněných objektů na území České republiky je velmi vysoká, proto neustále stoupá zájem o zachování těchto historicky cenných staveb, které se často nachází v nevyhovujícím stavu. Za účelem obnovy památky se provádí stavební, historické a architektonické průzkumy, jejíchž cílem je, mimo jiné, identifikovat a specifikovat použité historické materiály. Hlavní nosnou konstrukcí památkových objektů je obvykle zdivo, které stejně jako ostatní materiály podléhá degradaci, podpořené v mnoha případech statickými i vlhkostními problémy objektu. Ve své práci jsem se zaměřila na studium vlastností historického zdícího materiálu, který prošel degradačními procesy. Teoretická část práce je věnována historii a výrobě keramiky, druhům zděných konstrukcí, vadám a poruchám zdiva a následnému stavebně technickému průzkumu a diagnostice zdiva. Experimentální část práce byla věnována laboratorním metodám pro stanovení a vyhodnocení vlastností historického zdícího materiálu pocházejícího z objektu konventu Kláštera premonstrátů v Želivě.
Accepted: 2014-02-04T13:24:01Z Publisher: Vysoká škola báňská - Technická univerzita Ostrava
Keywords: želiv

Archeologisch booronderzoek Woldjerweg 3 en 5 te Wittewierum, gemeente Ten Boer (GR) - Krol, T.N. (DANS Data Station Archaeology, 2013)
Keywords: bloemhof

Hroznata Tepelský a jeho kult ve stredoveku a raném novoveku: strucný prehled výsledku bádání - Kubín, Petr (Historická dílna, 2013)
Keywords: 👤 hroznata of bohemia

Rola przedstawień drzewa genealogicznego zakonu w środowisku premonstratensów - Kwiatkowska-Frejlich, Lidia (Archiwa, Biblioteki I Muzea Kościelne, 2013)
The commonly known representation of Tree of Jesse, as inspired by the words „And the wand will come out of the root of Jesse and a flower will grow out of from its root” (Isaiah 11:1), proves the interpersonal relationships with Jesus and His messianic prophecy - by indicating on David. But since the earliest times this theme has been explored in the secular art because branching limbs with characters of descendants, growing from the parents’ chest, clearly illustrate the relations resulting from successions of generations within the family framework. This kind of representations was also popular in orders. At that time they not only provided the information on the background of spiritual path but also the assurance of its effectiveness on the way to reach Heaven. The images of the Order of Canons Regular of Prémontré, also known as the Premonstratensians, elaborated upon in this paper, was to make canons regular believe that abiding by the rules and laws made by the Order and praising the Eucharist, canons regular may master themselves to perfection and the saints of the order, who had already successfully fulfilled this recommendation, were the best teachers on the path of spiritual progress.
Keywords: 📚 premonstratensian (general)

Der Reformversuch im Kloster Cappenberg - Lackmann, Heinrich (Verl.-Haus Monsenstein und Vannerdat, 2013)
OCLC: 867872850
Keywords: cappenberg

Autour de la naissance de l'abbaye de Beauport - Le Bonniec, Yves (Mémoires de la Société Historique et Archéologique de Bretagne, 2013)
Keywords: beauport

Zum Weingartenbesitz und Weinbau des Prämonstratenserstiftes Osterhofen in Krems an der Donau und Umgebung - Lickleder, Hermann (Deggendorfer Geschichtsblätter, 2013)
Keywords: osterhofen

De norbertijnen in Rekem: verdwenen maar niet vergeten - Maesen, Mathieu (Invloed van Waalse norbertijnenabdijen in Limburg: Beaurepart en Floreffe, 2013)
Keywords: rekem

Bývalý premonstrátský klášter v Brne - Zábrdovicích: (poznámky ke stredovekým stavebním dejinám) - Merta, David (Kláštery ve stredovekých mestech strední Evropy: Archeologické výzkumy na památkových objektech = Archaeological excavations at protected monuments, 2013)
[Former Premonstratensian monastery in Brno - Zábrdovice (remarks on medieval buildlng history)]
Keywords: zábrdovice

Hugo van Fosses als kanunnik in Fosses-la-Ville en Cambrai (1087/95-1121/23). Bijdrage tot de ontstaansgeschiedenis van de Orde van Prémontré - Mingroot, Erik van (Analecta Praemonstratensia, 2013)
Keywords: 👤 hugh of fosses

O dawnych zwyczajach prawnych w swietle materialów procesovvych klasztoru sw. Wincentego na Oibinic we Wroclawiu z XIV wieku - Mlynarska-Kaletynowa, Marta (Z badan nad kultura spoleczenstw pradziejowych i wczesnosredniowiecznych: ksiega jubileuszowa dedykowana profesorowi Boguslawowi Gedidze, w osiemdziesiata rocznice urodzin przez przyjaciól, kolegów i uczniów, 2013)
Keywords: wrocław

El aprovechamiento del agua en el monasterio de San Pelayo de Cerrato. Contexto histórico y aproximación a partir de los referentes arqueológicos - Moratinos García, Manuel; Palomino Lazaro, Ángel Luis (Monasterios y recursos hídricos en la Edad Media, 2013)
Num Pages: 163 Pp.
Keywords: san pelayo de cerrato

Besitz und Personal des Klosters Trostadt - Mötsch, Johannes (Jahrbuch des Hennebergisch-Fränkischen Geschichtsvereins, 2013)
Keywords: trostadt

Klášter premonstrátů Teplá. Osobnosti vědy a školství - Nováková, Markéta (University of West Bohemia, 2013)
Práce se zabývá vznikem, vzestupem a historií premonstrátského řádu na území Čech, konkrétněji pak kláštera Teplá. Vyzdvihuje zakladatele tohoto kláštera blahoslaveného Hroznatu. Poukazuje na nevšední význam osobností vědy, kultury a školství, které v kláštere působili.Zdůrazňuje na jejich odkaz.Práce se dále přiblíží jejich práci - byli zakladatelé mnoha škol a nejvýznamnějšími šiřiteli vzdělání v západočeském regionu.Práce se také věnuje knihovní sbírce.
Accepted: 2014-02-06T12:45:44Z Publisher: Západočeská univerzita v Plzni
Keywords: teplá

Looking Anew at the curvilinear tracery of the Bellapais Abbey Cloister - Olympios, Michalis (Cahiers du Centre d'Études Chypriotes, 2013)
Keywords: bellapais

Die Anfänge der Prämonstratenser in Franken - Petersen, Stefan (Frankenland, 2013)
Keywords: 🇩🇪 germany (general)

Un bréviaire monumental de 1139 destiné aux prémontrés (?) de Knechtsteden (?) (Codex Bruxellensis 104) - Philippart, Guy (Amicorum societas: mélanges offerts à François Dolbeau pour son 65e anniversaire, 2013)
Keywords: knechtsteden; 🛐 liturgy

Fundacja Opactwa Premonstratensów w Brzesku-Hebdowie - Podgórska, Arkadia (Meandry Historii: Starożytność – średniowiecze – nowożytność. Referaty wygłoSzone na XX ogólnopolskim zjeździe Historyków Studentów w Katowicach, 2013)
Keywords: brzesko

Stredoveká sakrálna architektúra v Bíni : (sumarizácia, korekcia a doplnenie súčasných poznatkov) - Pomfyová, Bibiana; Samuel, Marián; Žažová, Henrieta (Archaeologia historica, 2013)
Príspevok prezentuje najnovší stav poznatkov o stredovekej sakrálnej architektúre v katastri obce Bíňa. Ako ukazujú výsledky archeologických výskumov, lokalita s polykultúrnym osídlením v praveku a včasnej dobe dejinnej zaujímala dôležité postavenie v rámci včasnostredovekej sídliskovej štruktúry na území dnešného Slovenska. Dôležitosť lokality potvrdzuje aj prítomnosť štyroch stredovekých sakrálnych stavieb v katastri dnešnej obce. Dve stavby – bývalý Kostol premonštrátskeho kláštora zasvätený Panne Márii a Rotunda Dvanástich apoštolov v jeho blízkosti sa zachovali dodnes. Súčasťou kláštora bola s najväčšou pravdepodobnosťou aj Kaplnka sv. Kataríny, známa len vďaka novovekým písomným prameňom. Kaplnka zanikla spolu s východným krídlom kláštora v dôsledku eróznej činnosti rieky Hron. Archeologicky odkrytý Kostol sv. Mikuláša v polohe "Opátske" bol súčasťou zaniknutej stredovekej dediny Leánd.
Accepted: 2013-10-14T08:30:27Z
Keywords: bíňa

Klášter premonstrátek v Doksanech a Slánsko : Slánské rozhovory 2012 - Přibyl, Vladimír; Vychodil, Pavel; Přibylová, Dana (Vlastivědné muzeum Slaný, 2013)
Keywords: doksany

Analýza historických malt a omítek ve zdivu budov kláštera Želiv - Rezek, Petr (Technická univerzita Ostrava, 2013)
Při rekonstrukcích nebo obnově fasád objektů se z pohledu stavebního inženýra nebo technika jeví jako primární stavebně – technické problémy (např. trhliny, vlhkostní problémy). Součástí identifikace těchto poruch u památkově chráněných objektů před případnou rekonstrukcí, ve snaze docílit podobného složení materiálu, je průzkum a analýza jeho použitých surovin. Identifikace materiálového složení omítek a malt představuje nezbytnou součást hodnocení historických fasád památkově chráněných objektů. Předložená diplomová práce se zabývá analýzou odebraných omítek některých objektů Kláštera premonstrátů s kostelem Narození P. Marie v Želivě.
Accepted: 2014-02-04T13:23:37Z Publisher: Vysoká škola báňská - Technická univerzita Ostrava
Keywords: želiv

Nouvelles observations sur l'abbaye de Beauport - Rioult, Jean-Jacques (Mémoires de la Société d'Histoire et d'Archéologie de Bretagne, 2013)
Keywords: beauport

Ermida do Paiva: reflexões e problemáticas - Rosas, Lúcia Maria; Botelho, Maria Leonor; Resende, Nuno (Revista da Faculdade de Letras: Ciências e Técnicas do Património, 2013)
With this article we want to reflect and discuss some of the historical issues concerning the Romanesque architecture, taking as an example the Ermida do Paiva (Castro Daire). Problems like the recovery of medieval heritage, the implantation in the territory or the foundational motivation in Portuguese history context are debated.
Keywords: ermida do paiva

Archäologie an der Straße: die Ausgrabungen im Kloster Elisabethenzell bei Rieneck - Rosmanitz, Harald; Wrobel, Kathrin (Beiträge zur Geschichte der Stadt und des Raumes Lohr, 2013)
Keywords: einsiedel

Ausgrabungen in der Klosterwüstung Elisabethenzell: Stadt Rieneck, Landkreis Main-Spessart, Unterfranken - Rosmanitz, Harald; Wrobel, Kathrin (Das archäologische Jahr in Bayern, 2013)
Keywords: einsiedel

Die präventive Konservierung mittelalterlicher Stuckarbeiten und Wandmalereien in der klimaregulierten Krypta zu St. Wiperti in Quedlinburg - Schmidt, Thomas (Wandmalereien in Krypten, Grotten, Katakomben : zur Konservierung gefasster Oberflächen in umweltgeschädigten Räumen, 2013)
Keywords: quedlinburg

"Amidst the ivy thou perceiv'st a ruin". Examining the history and development of St. Andrew's Kirk, Gullane - Sproat, Diana (Transactions of the East Lothian Antiquarian and Field Naturalists' Society, 2013)
Keywords: gullane

Klášter premonstrátů Teplá - historie a současnost - Stehlík, Jan (University of West Bohemia, 2013)
Ústředním cílem bakalářské práce je provedení charakteristiky historického vývoje Kláštera premonstrátů v Teplé a dále vylíčení současného dění tohoto kulturního a duchovního centra v oblasti západních Čech.
Accepted: 2014-02-06T12:44:56Z Publisher: Západočeská univerzita v Plzni
Keywords: teplá

Die wirtschaftlichen Aktivitäten des Prämonstratenserinnenstiftes Rumbeck - Timmermann, Fritz (Heimatblätter (Arnsberg), 2013)
Keywords: rumbeck

La Grange de Durance, le prieuré, l'église et ses peintures murales - Trézéguet, Jean-Louis (Revue de l'Agenais, 2013)
Keywords: durance

Das Leere Grab des heiligen Norbert - Ullrich, Sabine (Magdeburg : Die 99 besonderen Seiten der Stadt Sabine Ullrich, 2013)
Place: Halle (Saale) Publisher: Mitteldt. Verl., 2013, ISBN 978-3-95462-099-9
Keywords: 👤 norbert of xanten

The Bolton Scropes and Easby Abbey: a family mausoleum in context - Werronen, Stephen (Bulletin of international medieval research, 2013)
Keywords: easby

Human remains from the cloister garth of the 'Koningsveld' priory near the medieval city of Delft, ca. 1450-1572AD - Westen, A.A.; Groen, W.J.; Maat, G.J.R. (Stichting ter Financiering van Barge’s Anthropologica, 2013)
Keywords: delft

Studien zum ehemaligen Prämonstratenser(-innen)kloster Pernegg im Waldviertel (Niederösterreich) - Winkelbauer, Iris (University of Vienna, 2013)
Keywords: pernegg

Die Gründung des Klosters Oelinghausen - Wolf, Manfred (Sauerland, 2013)
Keywords: oelinghausen

Počátky premonstrátů v Čechách - Zemanová, Hana (Charles University, 2013)
The Beginnings of Premonstratensian Order in Bohemia. This thesis deals with the beginnings of Premonstratensian Order and their coming to Bohemia. At first, attention is devoted to the history which is briefly characterized by political, economic, and religious conditions in Bohemia in the first half of the twelfth century. The next chapter will take us through the life of St. Norbert, his conversion to Christianity, as well as the foundation and circumstances of the Premonstratensian Order. In this chapter, the Order's form of organisation, characteristics, and daily habits are also discussed. The subject of the fourth chapter is the establishment of the Premonstratensian Order in Bohemia. There are also discussed the persons who had the main credit for coming the Premonstratensian Order to Bohemia. It was their greatest admirer Jindrich Zdik, as well as the bishop Daniel and the provost of Steinfeld named Eberwin. The next section is dedicated to the description of the consequential creation of the first male and female monasteries in Bohemia such as Strahov, Doksany, Litomysl, Zeliv and Lounovice. There are also mentioned the first abbots and priors of these monasteries. In conclusion, there is a brief summary and evaluation of the contribution of the Premonstratensian Order.
Keywords: 🇨🇿 czechia (general)

A magyar királyok genealógiai ciklusa a leleszi premontrei kolostorkápolna középkori falképein - Jékely, Zsombor (Művészettörténeti Értesítő, 2012)
The Premonstratensian monastery of Lelesz, dedicated to the Holy Cross, was founded by Boleszló, the bishop of Vác (1188–1212). Patronage, however, was given over to the king, and later rulers in turn handed patronage of the monastery to their subjects. In 1214, the act of foundation was reinforced and the church of Lelesz consecrated. With the king's support, Lelesz became one of the wealthiest monasteries and an important place of authentication (locus credibilis). The new church of the monastery was built around the middle of the 14th century; in 1362 magister Johannes from Buda was contracted to build the tower. The chapel of Saint Michael, standing to the north of the church, and originally probably also serving as the chapter house, was built under the prior Dominicus of the Pálóci family (1378–1403). Around 1400, this new chapel was fully decorated with wall paintings. Much of the decoration – for example the frescoes of the vault – were destroyed when the chapel was re-vaulted in the 18th century. Still, a complete cycle of wall-paintings survives on the side walls of the chapel. On the south wall, there is a large, three-level image of the Last Judgment, with Christ in the mandorla dominating the scene, accompanied by the apostles on either side. In the lunettes of the north wall, two scenes can be detected: the one to the east depicts Saint Elisabeth of Hungary, while the other is possibly an image of Pope Urban V, in the company of cardinals. On the eastern walls of the chapel, apostles or prophets are depicted, framed by painted tracery. The focus of the paper is the series of figures depicted on the two lower zones of the north wall. As can be determined with the help of fragmentary inscriptions, these figures represent the kings of Hungary, starting from King Saint Stephen. The inscription gives the names of rulers and the number of years they ruled. The cycle is fragmentary, so we do not know exactly how many kings were depicted, but there is enough space for all the Hungarian sovereigns up until the then-current ruler, Sigismund (1387–1437). Such a cycle is unique from the territory of the medieval Kingdom of Hungary. Best parallel is provided by the cycle of initials in the Illuminated Chronicle (c. 1360, Széchényi National Library, Cod. Lat. 404), which also depict the pagan rulers of Hungarian prehistory, giving a complete genealogical cycle. Models of this cycle – just like that of the contemporary Luxemburg genealogy once on the walls of Karlstein castle in Bohemia – were provided by French manuscripts, especially the Grandes Chroniques de France. Emphasis in the cycle is not on individual kings, but on the unity and continuity of the line of Hungarian kings. One figure stands out: the first (badly damaged) ruler of the cycle is depicted enthroned. It is here proposed that the cycle starts with an image of the current ruler, King Sigismund. The style and iconography of the cycle make it a prime example of the International Gothic style, and these characteristic can be explained by the close connections of Lelesz abbey to the royal court.
Keywords: leles

Braine, Église Saint-Yved (Mapping Gothic, 2012)
Keywords: braine

Laon, Église Saint-Martin (Mapping Gothic, 2012)
Keywords: laon

Dale Abbey: A short history and guide - Allen, Roger N.; Allen, Ruth (Moorley's Print & Publishing, 2012)
Keywords: dale

De politieke context van het premonstratenzer Iter Italicum: de Romereizen van Diederik van Tuldel (°1419-†1494) - Appelmans, Janick (Reizen in woelige tijden, 2012)
Keywords: park

Les collèges de l'ordre de Prémontré, du Moyen Âge au concile de Trente - Ardura, Bernard (Die regulierten Kollegien im Europa des Mittelalters und der Renaissance, 2012)
Keywords: 📚 premonstratensian (general)

Cartas de donación particulares en el archivo del monasterio de Santa María la Real de Tórtoles de Esgueva (1152-1240) - Ávila Seoane, Nicolás; Cabezas Fontanilla, Susana (Las donaciones piadosas en el mundo medieval, 2012)
Keywords: tórtoles de esgueva

De nouveaux éléments lapidaires de l'ancienne abbaye de la Case-Dieu - Balagna, Christophe (Bulletin de la Société Archéologique Historique Littéraire et Scientifique du Gers, 2012)
Keywords: case dieu

Zástavní listiny Zikmunda Lucemburského na statky chotešovského kláštera (1420-1437) - Bárta, Stanislav (Mediaevalia historica Bohemica, 2012)
Keywords: chotěšov

L'église Saint-Martin d'Octeville - Bavay, Jeannine (Vikland, la revue du Cotentin, 2012)
Keywords: octeville

Zur Geschichte des Bistums Havelberg: Grundlinien seiner Entwicklung von den Anfängen bis zur Reformation - Bergstedt, Clemens (Der Havelberger Dombau und seine Ausstrahlung, 2012)
Keywords: havelberg

Das ehemalige Wirtschaftsgebäude der Prämonstratenserabtei Wadgassen - Bernard, Christel (ZeitenSprung, 2012)
Keywords: wadgassen

Anselm von Havelberg (1158), die Griechen und die Anfänge einer Geschichtstheologie des hohen Mittelalters - Berschin, Walter (Byzanzrezeption in Europa: Spurensuche über das Mittelalter und die Renaissance bis in die Gegenwart, 2012)
Keywords: 👤 anselm of havelberg

Langen/Blauhaus - Bley, Matthias (Niedersächsisches Klosterbuch. Verzeichnis der Klöster, Stifte, Kommenden und Beginenhäuser in Niedersachsen und Bremen von den Anfängen bis 1810, 2012)
Keywords: blauhaus; langen

Kostely tepelského panství - Bulková, Martina (University of West Bohemia, 2012)
Práce je zaměřena na sakrální objekty, které nechal vystavět či přestavět klášter premonstrátů v Teplé. Stavebně historické analýze bylo podrobeno 22 stojících i zaniklých kostelů. Jednotlivé stavby byly srovnávány na základě svých formálních znaků. Ve skupině se vyskytují kostely se složitějším slohovým vývojem i barokní novostavby. Výsledkem práce je interpretace vývoje stavební produkce tepelského klášterního panství.
Accepted: 2013-06-19T06:52:42Z Publisher: Západočeská univerzita v Plzni
Keywords: teplá

Ecclesia moderna und ecclesia primitiva in den Predigten des Jan Zelivský (Prag 1419) - Cadili, Alberto (Archa verbi, 2012)
Keywords: 👤 jan želivský

Guerres et violences à l’abbaye d’Ardenne - Chevrefils Desbiolles, Yves (Revue LISA, 2012)
Ardenne Abbey (on the outskirts of Caen, Basse-Normandie, France) is nowadays the headquarters of the Institut Mémoires de l’Édition Contemporaine, which houses archives dedicated to the intellectual life of the twentieth century. The mission of the IMEC is well suited to such a place: the images associated with the word “abbey” revolve around the idea of Peace through study, prayer or choral singing. This idyllic vision of an abbey, however, is in no way a protection against the vicissitudes of history. Perhaps even the contrary. An abbey, through what it represents, often becomes a symbolic target that makes it the victim of all sorts of violence. Before focusing on the Second World War, which almost led to its final disappearance, this article discusses the history of Ardenne Abbey from the Middle Ages to the modern era, in the light of the dark topic of violence.
Number: Vol. X – n° 1 Publisher: Presses Universitaires de Rennes
Keywords: ardenne

Le Graduel de Bellelay, aux origines de la liturgie prémontrée - Cullin, Olivier (Le livre et l'écrit. Texte, liturgie et mémoire dans l'Èglise du Moyen Âge, 2012)
Keywords: bellelay; 🛐 liturgy

Crear con imágenes. Los ángeles de Aguilar de Campoo - Debiais, Vincent (Codex Aquilarensis: Cuadernos de investigación del Monasterio de Santa María la Real, 2012)
Keywords: aguilar de campoo

Klasztor Norbertanek w Imbramowicach. Studia i materiały - Dębowska, Maria (Miejska i Powiatowa Biblioteka Publiczna, 2012)
Keywords: imbramowice

Aland - Dolle, Josef (Niedersächsisches Klosterbuch. Verzeichnis der Klöster, Stifte, Kommenden und Beginenhäuser in Niedersachsen und Bremen von den Anfängen bis 1810, 2012)
Keywords: aland

Balna Insula - Dolle, Josef (Niedersächsisches Klosterbuch: Verzeichnis der Klöster, Stifte, Kommenden und Beginenhäuser in Niedersachsen und Bremen von den Anfängen bis 1810, 2012)
OCLC: 930790747
Keywords: balna insula

Palmar - Dolle, Josef (Niedersächsisches Klosterbuch. Verzeichnis der Klöster, Stifte, Kommenden und Beginenhäuser in Niedersachsen und Bremen von den Anfängen bis 1810, 2012)
Keywords: palmar

Ebstorf – Prämonstratenser, ab ca. 1190 Benediktinerinnen, ab 1565 Damenstift (ca. 1160 bis zur Gegenwart) - Dose, Hanna (Niedersächsisches Klosterbuch. Verzeichnis der Klöster, Stifte, Kommenden und Beginenhäuser in Niedersachsen und Bremen von den Anfängen bis 1810, 2012)
Keywords: ebstorf

Les reliques de l'abbaye de La Lucerne - Ducoeur, Danièle (Revue de l'Avranchin et du pays de Granville, 2012)
Keywords: la lucerne

Anselm of Havelberg's use of authorities in his account of the Filioque - Dunkle, Brian (Byzantinische Zeitschrift, 2012)
Keywords: 👤 anselm of havelberg

Essen-Stoppenberg - Stift Stoppenberg - Ehlers-Kisseler, Ingrid (Nordrheinisches Klosterbuch: Lexikon der Stifte und Klöster bis 1815. 2: Düsseldorf-Kleve, 2012)
Keywords: stoppenberg

Voorwoord tot het Cartularium en Raadgevingen aan zijn Opvolgers voor het Bestuur van Abdij van Abt Arnold van Tuldel (prelaat van Averbode van 1368 tot 1394) - Exelmans, Eddy; Wouters, Jos (Mededelingenblad van de Heemkring Averbode, 2012)
Keywords: averbode

Die Geschichte der Doppelklöster, des Prämonstratenserordens und der Stiftung Geras-Pernegg - Ferderbar, Elke (University of Vienna, 2012)
Keywords: geras; pernegg

Beeleigh Abbey: A Guide and History - Foyle, Christopher (Christopher Foyle Publishing, 2012)
Keywords: beeleigh

Das Kloster Bredelar - "Zuerst besiedelt von Prämonstratenserinnen" - Freiburg, A. (Marsberger Geschichten 1: Schlüssel zur Vergangenheit : für die ehemaligen Städte Nieder- und Obermarsberg sowie für alle heutigen Ortsteile der Stadt Marsberg, 2012)
Keywords: bredelar

Die archäologischen Befunde der Ausgrabungen im Refektorium des Klosters Veßra von 2004 bis 2010 - Grasselt, Thomas (Kolloquium zu den neuesten Forschungsergebnissen im Kloster Vessra auf den Gebieten der Archäologie, Bauforschung und Denkmalpflege : Klausur und Kreuzgang : Tagungsband, 2012)
Keywords: veßra

Culture of Place: An Intellectual Profile of the Premonstratensian Order - Grassl, Wolfgang (Traugott Bautz, 2012)
Keywords: 📚 premonstratensian (general)

Konrad von Weissenau - Groß, Werner (Wer glaubt, ist nie allein : Namenstagskalender der Diözese Rottenburg-Stuttgart; Heilige, Selige, Glaubenszeugen, 2012)
Keywords: weissenau

The Hand of God and the Hand of the Scribe: Craft and Collaboration at Arnstein - Hamburger, Jeffrey F. (Die Bibliothek des Mittelalters als dynamischer Prozess, 2012)
Keywords: arnstein

The Premonstratensian House Of Canons At Preston Patrick - Hawkins, Harry (Transactions of the Cumberland and Westmorland Antiquarian and Archaeological Society, 2012)
Keywords: preston patrick

Coldinne - Heinze, Axel (Niedersächsisches Klosterbuch. Verzeichnis der Klöster, Stifte, Kommenden und Beginenhäuser in Niedersachsen und Bremen von den Anfängen bis 1810, 2012)
Keywords: coldinne

Schoo - Heinze, Axel (Niedersächsisches Klosterbuch. Verzeichnis der Klöster, Stifte, Kommenden und Beginenhäuser in Niedersachsen und Bremen von den Anfängen bis 1810, 2012)
Keywords: sconamora

Cazis (Kloster) - Hitz, Florian (Historisches Lexikon der Schweiz, 2012)
Keywords: cazis

Die mittelalterliche Baugeschichte des Havelberger Domes - Hoffmann, Joachim (Lukas Verlag für Kunst- und Geistesgeschichte, 2012)
Keywords: havelberg

Zur mittelalterlichen Baugeschichte des Havelberger Domes - Hoffmann, Joachim (Der Havelberger Dombau und seine Ausstrahlung, 2012)
Keywords: havelberg

Der Ort Hamborn und seine Abtei vom 12. bis 14. Jahrhundert - Horstkötter, Ludger (Verlagshaus Monsenstein und Vannerdat, 2012)
Keywords: hamborn

Premonstratensian Voices of Reform at the Fifteenth-Century Councils - Hyland, William (Reassessing Reform: A Historical Investigation into Church Renewal, 2012)
Keywords: 📚 premonstratensian (general)

Kall-Steinfeld – Abtei Steinfeld - Joester, Ingrid (Nordrheinisches Klosterbuch: Lexikon der Stifte und Klöster bis 1815. Teil 2: Düsseldorf bis Kleve, 2012)
Keywords: steinfeld

Príspevok k ikonografii výmaľby kapitulnej siene kláštora v Lelese - Juránková, Jana (Monument revue, 2012)
Keywords: leles

Premonstrátský klášter Louka u Znojma v době po husitských válkách (1434-1526) - Kohoutek, Michael (Masaryk University, 2012)
Keywords: louka

Katalog der mittelalterlichen Handschriften der Bibliothek des Prämonstratenser-Chorherrenstiftes Wilten - Kompatscher-Gufler, Gabriela; Mairhofer, Daniela; Schretter, Claudia (Verlag der Österreichischen Akademie der Wissenschaften, 2012)
Keywords: wilten

Drei Ablaßurkunden für das Prämonstratenserstift Pöhlde aus dem 13. Jahrhundert - Könighaus, Waldemar (Archiv für Diplomatik, 2012)
Keywords: pöhlde

Das alte Kirchspiel Ripsdorf und seine Wälder: Ripsdorf in seiner besonderen Rolle als Pfarrort - Konrads, Manfred (Jahrbuch des Kreises Euskirchen, 2012)
Keywords: ripsdorf

Das Prämonstratenserstift Broda. Cura animarum im Spiegel der Urkunden - Kornemann, Ivonne (University of Leipzig, 2012)
Keywords: broda

Průzkum, diagnostika a sanace historických konstrukcí - Krejčí, Šárka (Technická univerzita Ostrava, 2012)
Koncentrace památkově chráněných objektů na území České republiky je velmi vysoká, proto neustále stoupá zájem o zachování těchto historicky cenných staveb, které se často nachází v nevyhovujícím stavu. Za účelem obnovy památky se provádí stavební, historické a architektonické průzkumy, jejíchž cílem je šetrný návrh sanačních opatření, s důrazem na použití nedestruktivních sanačních metod. Jednou z nejčastějších poruch historických staveb jsou vlhkostní problémy způsobené často dožitým či chybějícím hydroizolačním opatřením. Z tohoto důvodu jsem práci směřovala na diagnostiku a následnou sanaci objektů trpících zvýšenými hodnotami vlhkosti. V první části jsem se zaměřila na historické metody hydroizolací, příčiny vzniku vlhkosti, diagnostické metody určení hodnot vlhkosti a možná sanační opatření. Druhá část byla věnována předběžnému stavebně technickému průzkumu Kláštera premonstrátů v Želivě.
Accepted: 2012-07-11T08:06:57Z Publisher: Vysoká škola báňská - Technická univerzita Ostrava
Keywords: želiv

Lebensordnung und Gottesdienst im Prämonstratenserinnenkloster Altenberg an der Lahn: mit einer Edition des Altenberger Küsterinnenbuches - Krings, Bruno (Archiv für mittelrheinische Kirchengeschichte, 2012)
Keywords: altenberg

De pastorie van Wakkerzeel. Een parel uit het netwerk van pastoorshuizen van de norbertijnen-abdij van Park in Vlaams-Brabant - Lani, Stefan van (Haachts oudheid- en geschiedkundig tijdschrift, 2012)
Keywords: park

A monastic community in local society: the Beauchief Abbey Cartulary - Liddy, Lisa; Hey, David G. (Cambridge University Press for the Royal Historical Society, 2012)
OCLC: 1023369980
Keywords: beauchief

Quellen zur Geschichte des Stiftes Flaesheim im 13. Jahrhundert - Lindken, Theodor; Schwabe, Gabriele (Vestische Zeitschrift, 2012)
Keywords: flaesheim

Monastisches Gesellschaftsmodell und Zahl im Hochmittelalter: Adams von Dryburgh Stiftshüttentraktat De triplice tabernaculo una cum pictura - Meier, Christel (Was zählt. Ordnungsangebote, Gebrauchsformen und Erfahrungsmodalitäten des "numerus" im Mittelalter, 2012)
Keywords: 👤 adam of dryburgh

Die Innenraumgestaltung des Refektoriums des ehemaligen Prämonstratenser-Chorherrenstifts zu Veßra/Thüringen - Nolte, Steffen (Kolloquium zu den neuesten Forschungsergebnissen im Kloster Vessra auf den Gebieten der Archäologie, Bauforschung und Denkmalpflege : Klausur und Kreuzgang : Tagungsband, 2012)
Keywords: veßra

Augustinerkaniker och premonstratenser i Danmark före ca. 1200 - Nyberg, Tore (Locus Celebris: Dalby kyrka, kloster och gård, 2012)
Keywords: 🇩🇰 denmark (general)

Die Wirtschaftsgeschichte des Klosters Clarholz. II. Teil: Die Bewirtschaftungs- und Ertragsgeschichte - Ossenbrink, Jochen (Analecta Praemonstratensia, 2012)
Keywords: clarholz

La politique de défrichement de la terre par le verre. Les religieux et les territoires du verre en Thiérache XVe et XVIe siècles - Palaude, Stéphane (Revue du Nord, 2012)
Située à l’extrémité septentrionale du département de l’Aisne, la Thiérache constitue depuis toujours une région de forêts qui trouvent leur prolongement tant en Avesnois (Nord), en Botte du Hainaut (Belgique), qu’au pied des contreforts ardennais. Si cette profusion de bois attire les artisans verriers dont les fours de fusion sont dévoreurs de combustible ligneux, leur installation ne s’effectue cependant que dans le dernier tiers du xve siècle, fruit de la volonté d’abbés appliquant une politique de défrichement de la terre par le verre sur leur domaine, tant chez les cisterciens de Foigny que chez les prémontrés de Clairfontaine [1] [1]Clairfontaine, cant. La Capelle, arr. Vervins, dép. Aisne.… . Deux ordres religieux, deux voisins proches, une même politique et une même réussite ayant eu pour facteur déclencheur la guerre. Certes, la combinaison terre-verre-guerre étonne, pourtant la réalité des faits se pose là, avec d’autant plus d’intérêts que, jusqu’ici, personne n’a jamais mis en relation les diverses créations d’établissements verriers dans cette zone forestière. 2 Au lieu de nous attarder sur la fondation des ordres de Cîteaux et Prémontré, présentons succinctement les religieux concernés. Les abbayes d’hommes Notre-Dame de Foigny et, à douze kilomètres au nord, Saint-Nicolas de Clairfontaine sont fondées, la première en 1121 et la seconde quelques années après. S’ouvre alors une période de prospérité morale et économique en Thiérache. L’impénétrable forêt, partie de l’antique Charbonnière qui sert de frontière naturelle depuis des siècles, perd de sa surface au profit des labours. Puis le glas de cette période faste sonne en 1339, lorsque les troupes de Jean de Hainaut et d’Édouard III d’Angleterre saccagent, entre autres, les monastères qui nous intéressent. La guerre débute pour longtemps. Les ravages sont récurrents et vont s’étaler sur plus d’un siècle. Qu’en est-il des verriers ?
Keywords: clairfontaine

Prämonstratenserstift Veßra: Ergebnisse der Bauforschung an Klausur und Kreuzgang - Perlich, Barbara (Kolloquium zu den neuesten Forschungsergebnissen im Kloster Vessra auf den Gebieten der Archäologie, Bauforschung und Denkmalpflege : Klausur und Kreuzgang : Tagungsband, 2012)
Keywords: veßra

Bücher für Liturgie und Wissenschaft - das Skriptorium des Prämonstratenserklosters Schäftlarn - Pfändtner, Karl-Georg (Spurensuche Leben: 1250 Jahre Kloster Schäftlarn: eine Festgabe, 2012)
Keywords: schäftlarn

Document: Edward I's Wars in the Chronicle of Hagnaby Priory - Prestwich, Michael C. (The journal of medieval military history, 2012)
Keywords: hagnaby

Heinsberg - Marienstift - Preuß, Heike (Nordrheinisches Klosterbuch: Lexikon der Stifte und Klöster bis 1815. 2: Düsseldorf-Kleve, 2012)
Keywords: heinsberg

Mittelalterliche Grabplatten im Dom zu Havelberg - Priese, Karl Heinz (Der Havelberger Dombau und seine Ausstrahlung, 2012)
Keywords: havelberg

Pilger und Stifter. Zu den Sakralstiftungen und zur Herkunft des Fürsten Jaxa - Rajman, Jerzy (Monarchische und adlige Sakralstiftungen im mittelalterlichen Polen, 2012)
Num Pages: 556 Pp.
Keywords: zwierzyniec

Grefrath - Prämonstratenser - Rehm, Gerhard (Nordrheinisches Klosterbuch: Lexikon der Stifte und Klöster bis 1815. 2: Düsseldorf-Kleve, 2012)
Keywords: grefrath

Die archäologischen Funde aus dem Refektorium des Klosters Veßra - Römhild, Michael (Kolloquium zu den neuesten Forschungsergebnissen im Kloster Vessra auf den Gebieten der Archäologie, Bauforschung und Denkmalpflege : Klausur und Kreuzgang : Tagungsband, 2012)
Keywords: veßra

Hopels - Schäfer, Burkhard (Niedersächsisches Klosterbuch. Verzeichnis der Klöster, Stifte, Kommenden und Beginenhäuser in Niedersachsen und Bremen von den Anfängen bis 1810, 2012)
Keywords: hopels

Grevenbroich-Langwaden - Prämonstratenserinnen - Schildt-Specker, Barbara (Nordrheinisches Klosterbuch : Lexikon der Stifte und Klöster bis 1815, 2012)
Keywords: langwaden

The Conversion of Herman the Jew: Autobiography, History, and Fiction in the Twelfth Century - Schmitt, Jean-Claude (University of Pennsylvania Press, 2012)
Keywords: 👤 hermann of cologne

Die Klausurgebäude des Havelberger Domstifts: Vergleiche mit den Prämonstratenserstiften in der Ordensprovinz Sachsenc - Schmitt, Reinhard (Der Havelberger Dombau und seine Ausstrahlung, 2012)
Keywords: havelberg

Der Havelberger Dom: die gotischen Umbauten - Schöfbeck, Tilo (Der Havelberger Dombau und seine Ausstrahlung, 2012)
Keywords: havelberg

Der Zelebrationsaltar in St. Martin, Zyfflich, und seine theologische Bedeutung - Scholten, Christoph (Beiträge zur Chronik Zyfflichs, 2012)
Keywords: zyfflich

Das Bistum Konstanz 6: Das reichsunmittelbare Prämonstratenserstift Marchtal - Schöntag, Wilfried (Walter de Gruyter GmbH, 2012)
Keywords: marchtal

Die Gründung des Prämonstratenserklosters Allerheiligen. Ein Beitrag zum Thema "Staufer - Weifen - Zähringer" - Schwarzmaier, Hansmartin (Klöster, Stifter, Dynastien: Studien zur Sozialgeschichte des Adels im Hochmittelalter, 2012)
Keywords: allerheiligen

Women as makers of church decoration: illustrated textiles at the monasteries of Altenberg/Lahn, Rupertsberg, and Heiningen (13th - 14th c.). - Seeberg, Stefanie (Reassessing the Roles of Women as 'Makers' of Medieval Art and Architecture, 2012)
Keywords: altenberg

Zur Sichtbarkeit und Wahrnehmung gestickter Bilder und Inschriften auf Altardecken des Mittelalters - Seeberg, Stefanie (Beziehungsreiche Gewebe: Textilien im Mittelalter, 2012)
Num Pages: 467 Pp.
Keywords: altenberg

Die Wallfahrtskapelle Maria im Buchs. Zur Geschichte des Klosters Himmelspforte in Wyhlen - Segin, Hans A. (Bärenfelser, 2012)
Keywords: himmelspforte (germany)

Visionary Saints in the Gilded Age: The American Afterlife of the Park Abbey Glass - Shortell, Ellen M. (Collections of Stained Glass and their Histories, Transactions of the 25th International Colloquium of the Corpus Vitrearum in Saint Petersburg, The State Hermitage Museum, 2010, 2012)
Keywords: park

Two unknown music fragments in the Grey Collection of the South African Library Cape Town - Steyn, C. (South African Journal of Cultural History, 2012)
Among the Medieval and Renaissance manuscripts in the Grey Collection in the National Library in Cape Town there are two fragments with music notation, one large, one small. Although research has been done on most of the music manuscripts in the Collection, these fragments have not been studied before. Fragments of Medieval and Renaissance manuscripts have been neglected in scholarly research, but recently serious studies have been made have been made in several overseas centres. Of the two fragments discussed in this article, the smaller one, consisting of only two folios, is the more interesting. It forms part of an earlier binding of MS Grey 3c16, a 15th century copy of Guido delle Collone's Historia destructionis Troiae, and although no date or provenance is mentioned in the fragments, it has been possible to establish that it was a 12th century noted missal that had probably belonged to Dryburgh Abbey, a Premonstratensian monastery on the Scottish border. Early noted missals in which chants, readings and prayers appear in the correct liturgical order, as in this fragment,are very rare. The larger fragment, MS 48b3, consists of 43 leaves and is very well preserved and attractive with many decorative initials in bright colours. It formed part of the sanctorale of a very large choir book and was possibly in use in the Bologna region of Italy in the 15th century. A more precise dating and provenance could not be established, however. Twee onbekende musiekfragmente in the Grey-versameling van die Suid-Afrikaanse Biblioteek, Kaapstad Onder die Middeleeuse en Renaissance manuskripte in die Grey-versameling in die Nasionale Biblioteek in Kaapstad is twee fragmente met musieknotasie die een groot, die ander klein. Hoewel navorsing oor die meeste van die musiekmanuskripte in die versameling gedoen is, is hierdie fragmente nog nie vantevore bestudeer nie. Fragmente van Middeleeuse en Renaissance manuskripte is grootliks in akademiese navorsing verontagsaam, maar onlangs is deurdringende navorsing in verskeie oorsese sentra gedoen. Van die twee fragmente wat in hierdie artikel bespreek word, is die kleiner een, wat slegs twee folios beslaan, die interessantste. Dit vorm deel van 'n vroeer omslag van MS Grey 3c16, 'n vyftiende-eeuse kopie van Guido delle Collone se Historiade structionis Troiae, en hoewel geen datum of herkoms in die fragment genoem word nie, was dit moontlik om vas te stel dat dit 'n twaalfde-eeuse genoteerde missaal was wat waarskynlik aan die Dryburgh Abdy, 'n Premonstratensiese monnikeklooster op die grens van Skotland behoort het. Vroee genoteerde missale waarin die gesange, lesings en gebede soos in hierdie fragment in die korrekte liturgiese volgorde verskyn, is baie skaars. Die groter fragment, MS 48b3, bestaan uit 43 blaaie en is goed bewaar en aantreklik met baie dekoratiewe hoofletters in helder kleure. Dit vorm deel van die sanktorale van 'n baie groot koorboek en is moontlik in die vyftiende eeu in die Bologna-streek van Italie gebruik. 'n Meer presiese datum en herkoms kon egter nie vasgestel word nie.
Keywords: dryburgh

Zyfflich und die Bistumsorganisation in Mittelalter und Neuzeit: das Stift Zyfflich in der Kölner Kirchenprovinz - Stinner, Johannes (Beiträge zur Chronik Zyfflichs, 2012)
Keywords: zyfflich

Zsámbéki premontrei prépostsági templom - Szakács, Béla Zsolt (Magyar muvelodéstörténeti lexikon: középkor és kora újkor, 2012)
Keywords: zsámbék

Kamienne plyty z ostatniej cwierci XII wieku w dawnym kosciele Norbertanek pw. Swietej Trójcy w Strzelnie - Szczęsna, Joanna (Ars omnia vincit. Studia z dziejów sztuki i kultury artystycznej, 2012)
Keywords: strzelno

Anselm von Havelberg, Anticimenon Über die eine Kirche von Abel bis zum letzten Erwählten und von Ost bis West - Thümmel, Hans Georg (Theologische Rundschau, 2012)
Keywords: 👤 anselm of havelberg

Heylissem. Histoire d'une abbaye de l'ordre de Prémontré - Tordoir, Joseph (Cercle d'Histoire, Archéologique et généalogique de Wavre et du Brabant wallon, 2012)
Keywords: heylissem

Bad Schussenried: Das ehemalige Prämonstratenserstift - Tuchen, Birgit (Der nördliche Bodenseeraum. Ausflugsziele zwischen Rhein und Donau., 2012)
Keywords: schussenried

Opatská kaple (kaple sv. Šebestiána) premonstrátského klášterního kostela Panny Marie a sv. Václava ve Znojme-Louce: (poznámky ke stavebnímu a výtvarnému vývoji) - Vácha, Zdenek (Archaeologia historica, 2012)
[Die Abtskapelle (St.-Sebastian-Kapelle) der Prämonstratenserklosterkirche der Jungfrau Maria und des Heiligen Wenzel in Znojmo-Louka: (Anmerkungen zur baulichen und künstlerischen Entwicklung)]
Keywords: louka

Egidius (Gillis) van Leeuw, premonstratenzer kruisprediker, kruisvaarder naar Damietta en abt van Middelburg en Vicoigne († 1236) - Van Moolenbroek, Jaap (Analecta Praemonstratensia, 2012)
Keywords: middelburg; vicoigne

Haus Meer in Meerbusch: Kloster, Schloss und Park - Vogelsang, Rosemarie; Lutum, Reinhard (Rheinischer Verein für Denkmalpflege und Landschaftsschutz, 2012)
Keywords: meer

Premonstratenzers - Vries, Gerben E. de (De middeleeuwse kloostergeschiedenis van de Nederlanden, 2012)
Keywords: 🇳🇱 netherlands (general)

Floreffe: recherches récentes sur les décors peints médiévaux de l'abbaye prémontrée - Wilmet, Aline (Chronique de l'Archéologie wallonne, 2012)
Keywords: floreffe

Les décors peints de l'infirmerie médiévale de l'abbaye de Floreffe - Wilmet, Aline (Annales de la Société archéologique de Namur, 2012)
Keywords: floreffe

Mittelalterliche Kult-Etablierung und neuzeitliche Kult-Imagination. Gertrud von Altenberg, die filia sanctae Elisabeth - Winkel, Harald (Elisabeth und kein Ende ... Zum Nachleben der heiligen Elisabeth von Thüringen: 5. Tagung der Arbeitsgruppe “Marburger Mittelalterzentrum (MMZ)”, Marburg, 1. Juni 2007, 2012)
Num Pages: 348 Pp.
Keywords: altenberg

St. Jakobi in Coesfeld - Wipper, Heinrich (Die Kalebasse, 2012)
Keywords: coesfeld (st. jakobi)

Das Prämonstratenserkloster Veßra - Wölfing, Günther (Jahrbuch des Hennebergisch-Fränkischen Geschichtsvereins, 2012)
Keywords: veßra

Präsentation des Buches "Das Prämonstratenserkloster Veßra: Urkundenregesten 1130-1573" - Wölfing, Günther (Kolloquium zu den neuesten Forschungsergebnissen im Kloster Vessra auf den Gebieten der Archäologie, Bauforschung und Denkmalpflege : Klausur und Kreuzgang : Tagungsband, 2012)
Keywords: veßra

Stavební dějiny premonstrátského kláštera Teplá. I. část - Zahradník, Pavel (Sborník muzea Karlovarského kraje, 2012)
Keywords: teplá

Premonštrátsky kláštor Blahoslavenej Panny Márie v Bíni - Žažová, Henrieta (Studia Historica Tyrnaviensia, 2012)
Keywords: bíňa

Kloster Berentrop bei Neuenrade und seine wechselvolle Geschichte - Kohl, Rolf Dieter (Die Schelle, 2011)
Keywords: berentrop

Le prieuré de Boucquy - Puloc'h, Armelle (Au fil de Jaux: Bulletin de la Municipalité, 2011)
Keywords: boucquy

L'abbaye de Gérigny : vous connaissez ? (Le cercle des collectionneurs de Signy-l'Abbaye, 2011)
Keywords: gérigny

Kloster Aland war der Gottesmutter geweiht: Gründung in der ersten Hälfte des 13. Jahrhunderts (Heimatkunde und Heimatgeschichte, 2011)
Keywords: aland

Die Wirtschaftsgeschichte des Klosters Clarholz, 1, Die Besitzgeschichte - Ardura, Bernard (Analecta Praemonstratensia, 2011)
Keywords: clarholz

Zur Typologie der Evangelienharmonien des Zacharias Chrysopolitanus: vier italienisch illuminierte Handschriften des 12. Jahrhunderts in München - Bauer-Eberhardt, Ulrike (Buchschätze des Mittelalters : Forschungsrückblicke, Forschungsperspektiven : Beiträge zum Kolloquium des Kunsthistorischen Instituts der Christian-Albrechts-Universität zu Kiel, 2011)
Keywords: 👤 zachary of besançon

Liturgische handschriften met muzieknotatie in de premonstratenzer abdijen Grimbergen, Tongerlo, Park en Averbode: wat is voorhanden en welke zijn premonstratenzer handschriften? - Behrendt, Inga (Premonstratenzer gregoriaans in de Nederlanden : liturgische handschriften (13de-16de eeuw), 2011)
Keywords: averbode; grimbergen; park; tongerlo

Gottesgnaden (Calbe): ehem. Prämonstratenserstift, ehem. Hospitalkirche Gottesgnaden - Beier, Stefan (Klosterlandschaft Sachsen-Anhalt, 2011)
Keywords: gottesgnaden

Jerichow: ehem. Prämonstratenserchorherrenstift und Klosterkirche St. Marien und St. Nikolai - Beier, Stefan (Klosterlandschaft Sachsen-Anhalt, 2011)
Keywords: jerichow

Leitzkau: ehem. Prämonstratenserstift, Pfarrkirche St. Peter und ehem. Stiftskirche Sancta Maria in monte - Beier, Stefan (Klosterlandschaft Sachsen-Anhalt, 2011)
Keywords: leitzkau

Le programme sculpté du chevet de Sainte-Marie d'Arthous (thèmes et comparaison dans le monde roman) - Blancher, Carole (Bulletin de la Société de Borda, 2011)
Keywords: arthous

Krisenphänomene und Reformversuche?: das Prämonstratenserkloster Langen zwischen dem 14. und 16. Jahrhundert - Bley, Matthias (Emder Jahrbuch, 2011)
Keywords: langen

Investition in die Zukunft : 875 Jahre Abtei Hamborn - Bockelbrink, Philipp; Euskirchen, Claudia; Kunz, Brigitta (Stadt, 2011)
Keywords: hamborn

Travaux d'environnement à l'église de Laval-Dieu - Carlier, Jean-Maurice (Chez nous, 2011)
Keywords: laval dieu

Převorka Anna versus probošt Šebestián – dva typy řeholníků v Nové Říši na konci 16. století - Černušák, Tomáš (Folia historica Bohemica, 2011)
Publisher: Institute of History, Czech Academy of Sciences
Keywords: nová říše

The Founders and Patrons of the Premonstratensian Houses in Ireland - Clyne, Miriam (The Regular Canons in the Medieval British Isles, 2011)
Keywords: 🇮🇪 ireland (general)

Klášterní Hradisko a Svatý Kopeček. Premonstrátská stopa v panorámatu Olomouce - Dolejší, Kateřina (Památky - tvůrci panoramat našich měst. Dny evropského dědictví 2011, 2011)
Keywords: hradisko

850 Jahre Kloster Hausen - Eberth, Werner (Beiträge zur Geschichte von Hausen und Kleinbrach, 2011)
Keywords: hausen

Custodians of Continuity? The Premonstratensian Abbey at Barlings and the Landscape of Ritual - Everson, Paul; Stocker, David A. (Heritage Trust of Lincolnshire, 2011)
Keywords: barlings

The Witham valley: a landscape with monasteries? - Everson, Paul; Stocker, David A. (Church Archaeology, 2011)
Keywords: barlings; tupholme

L'abbaye de Septfontaines - Febvre, Jean (La Gazette de l'Association Culturelle Andelotienne, 2011)
Keywords: septfontaines en bassigny

Das Kloster Dünnwald: die abseits gelegene Keimzelle des Kölner Stadtteils Dünnwald - Flock, Inge (Rechtsrheinisches Köln, 2011)
Keywords: dünnwald

Die Anfänge des Stifts Varlar und sein Priorat in Deventer - Frese, Werner (Westfälische Zeitschrift, 2011)
Keywords: varlar

Das Sagogn-Wildenberger Kloster Rot an der Rot - Gabathuler, Heinz (Bündner Monatsblatt, 2011)
Keywords: rot an der rot

Lire la pierre comme un marqueur spatial et fonctionnel: l'exemple de l'abbaye de Beauport (Côtes-d'Armor) au XIIIe siècle. - Gallet, Yves (Ex quadris lapidibus: la pierre dans l'art médiéval ; mélanges d'histoire de l'art offerts à Eliane Vergnolle, 2011)
Keywords: beauport

Das Prämonstratenserstift in Jerichow - Ausgangspunkt der Christianisierung der Nordmark - Grubitzsch, Falko (Kulturgeschichten aus Sachsen-Anhalt, 2011)
Keywords: jerichow

Gertrud von Altenberg, Namenspatronin des Biskirchener Gertrudisbrunnens - Grün, Paul (Biskirchener Heimatkalender, 2011)
Keywords: altenberg

Der heilige Norbert: Erzbischof und Ordensgründer - Handgrätinger, Thomas (Norbertus-Verlag, 2011)
Keywords: 👤 norbert of xanten

Records of Shap Abbey, Cumbria - Hawkins, Harry (Monastic Research Bulletin, 2011)
Keywords: shap

Die Beziehungen der Familie von Bülow zum Kloster Rehna im Spiegel ihrer Schenkungen und Stiftungen im 13. Jahrhundert. - Hestermann, Gregor (Jahrbücher des Vereins für mecklenburgische Geschichte und Alterthumskunde, 2011)
Keywords: rehna

875 Jahre Abtei Hamborn (1136 - 2011): Seelsorge mitten unter den Menschen - Horstkötter, Ludger (Duisburger Jahrbuch, 2011)
Keywords: hamborn

Gründung und Entwicklung des Klosters Flaesheim - Husmann, Gregor (Halterner Jahrbuch, 2011)
Keywords: flaesheim

Torre Abbey: locality, community, and society in medieval Devon. - Jenkins, John Christopher (University of Oxford, 2011)
Keywords: torre

Tommarp : kunglig produktionsort och klosterstad - Jönsson, Lars (Institutionen för arkeologi och antikens historia, Lunds universitet, 2011)
ISBN: 9789189578371
Keywords: tommarp

So klingt Versöhnung: Geschichten zur Geschichte der Glocken in der Marienkirche Gelnhausen - Kappel, Hans-Henning (Stiftung Marienkirche Gelnhausen, 2011)
OCLC: 725235925
Keywords: gelnhausen (marienkirche)

Das Ende der Klosterregion: die Aufhebung der Klöster Clarholz und Herzebrock - Klueting, Edeltraud (Jahrbuch für mitteldeutsche Kirchen- und Ordensgeschichte, 2011)
Keywords: clarholz

Soubor terakotových reliéfně zdobených dlaždic z kláštera Panny Marie a sv. Jiří ve Střelné - Kouřil, Pavel (Co můj kostel dnes má, nemůže kníže odníti. Věnováno Petru Sommerovi k životnímu jubileu, 2011)
Keywords: velká střelná

Soubor terakotových reliéfně zdobených dlaždic z kláštera Panny Marie a sv. Jiří ve Střelné - Kouřil, Pavel (Co můj kostel dnes má, nemůže kníže odníti : věnováno Petru Sommerovi k životnímu jubileu, 2011)
Keywords: velka střelná

Ein Register verschollener Quellen zur Geschichte der Abtei Sayn - Krings, Bruno (Jahrbuch für westdeutsche Landesgeschichte, 2011)
Keywords: sayn

Das Havelberger Osterspiel des 15. Jahrhunderts: Rekonstruktion des mittelalterlichen Osterspiels der Prämonstratenser am Havelberger Dom, Uraufführung der rekonstruierten Fassung, Ostersonntag, den 04. April 2010 - Langner, Martin-Maximilian (Elbe-Havel Verlag, 2011)
Pages: 44
Keywords: havelberg

Pachtovereenkomst voor het Hof ten Bremt in Burst - mei 1404 - Liessens, Gerrit; Souffreau, Georges Léon (Mededelingen van de Heemkundige Kring van Erpe-Mere, 2011)
Keywords: hof ten bremt

Salcedo - López de Ocáriz Alzola, José Javier (Euskadi : Euskal Erromanikoaren entziklopedia = País Vasco : Enciclopedia del románico en el País Vasco, 2011)
Keywords: salcedo

Sources et documents: chronique de sigillographie normande - À propos du cartulaire de Mondaye: les dépôts de sceaux de référence dans les établissements religieux normands au XIIIe siècle - Maneuvrier, Christophe; Thébault, Marion (Annales de Normandie, 2011)
Keywords: mondaye

Regesten der Urkunden des Klosters Trostadt - Mötsch, Johannes (Jahrbuch des Hennebergisch-Fränkischen Geschichtsvereins, 2011)
Keywords: trostadt

Propriétés données à l'abbaye de Belval par Herbert de Mouzon, vers 1145 - Motte, Paul (Revue historique ardennaise, 2011)
Keywords: belval

Die Gründung und Frühzeit der Prämonstratenserabtei Wadgassen im Spiegel der Kirchen- und Territorialpolitik Erzbischof Alberos von Trier - Müller, Jörg (Analecta Praemonstratensia, 2011)
Keywords: wadgassen

Die Weltchronik des Propstes Burchard von Ursberg: staufische Reichspolitik in universalhistorischer Perspektive - Oberweis, Michael (Analecta Praemonstratensia, 2011)
Keywords: 👤 burchard of ursberg

K problematike stredovekého portálu kláštorného kostola v Šahách - Oriško, Štefan (Archaeologia historica, 2011)
Keywords: šahy

Die Wirtschaftsgeschichte des Klosters Clarholz. I. Teil: Die Besitzgeschichte - Ossenbrink, Jochen (Analecta Praemonstratensia, 2011)
Keywords: clarholz

La circarie lorraine de l'ordre de Prémontré - Parisse, Michel (Religieux et religieuses en Empire du Xe au XIIe siècle, 2011)
Keywords: 🇫🇷 france (general)

Repairing "that vision by which Christ may be seen": The St Swithun Cycle at Corhampton, and the Depiction of Patronal Saints in English Romanesque Wall Painting - Park, David (Image, Memory and Devotion: Liber Amicorum Paul Crossley, 2011)
Keywords: corhampton

Spirituality of the Premonstratensians : the twelfth and thirteenth centuries - Petit, François (Cistercian Publications, 2011)
Keywords: 📚 premonstratensian (general)

Hof – Stadt – Kloster. Zu Funktions- und Gefühlsräumen mittelalterlicher Frauenklöster in Wien - Schedl, Barbara (Funktionsräume, Wahrnehmungsräume, Gefühlsräume: Mittelalterliche Lebensformen zwischen Kloster und Hof, 2011)
Num Pages: 171 Pp.
Keywords: himmelspforte (austria)

"Slawenmission" östlich der Elbe - Bischof Anselm und der Havelberger Dom - Schier, Luise (Kulturgeschichten aus Sachsen-Anhalt, 2011)
Keywords: havelberg; 👤 anselm of havelberg

Edle von Lindow und "Anwälte Gottes" vom Kloster Leitzkau - Sehl, Helmut (Zerbster Heimatkalender, 2011)
Keywords: leitzkau

Restituer l'abbatiale romane de Mureau (Vosges)? - Sesmat, Pierre (Ex quadris lapidibus: la pierre dans l'art médiéval ; mélanges d'histoire de l'art offerts à Eliane Vergnolle, 2011)
Keywords: mureau

První etapa výzkumu v areálu premonstrátské kanonie v Teplé - Široký, Radek; Nováček, Karel (Památky západních Cech, 2011)
Keywords: teplá

Poněkud hladová péče o památky. Zpráva o klášteře v Doksanech - Solař, Miloš (Dějiny a současnost : kulturně historická revue, 2011)
Keywords: doksany

Eine unglückliche Liebe - und der Aufruhr im Stift "Gottes Gnade" bei Calbe - Steinmetz, Dieter H. (Dirnen, Templer und Dämonen - Geschichten aus der Geschichte der 1075-jährigen Stadt Calbe, 2011)
Place: Calbe/Saale Publisher: Heimatverein Calbe/Saale, 2011, ISBN 3-935971-57-5
Keywords: gottesgnaden

Tihanyi bencés apátsági templom; Türjei premontrei prépostsági templom - Szakács, Béla Zsolt (Magyar muvelodéstörténeti lexikon: középkor és kora újkor, 2011)
Keywords: türje

Medieval canonical collections of the Norbertine Abbey of Weissenau in the Hermitage of St. Petersburg - Szuromi, Szabolcs Anzelm (Analecta Praemonstratensia, 2011)
Keywords: weissenau

Le dépôt lapidaire de l'abbaye Notre-Dame de Beauport : Une invitation à la relecture de cinq siècles d'architecture - Techer, Pascale (Regards sur les depots lapidaires de la France du Nord : actes de la journee d'etudes L'architecture en objets, Paris, Institut national d'histoire de l'art, vendredi 12 decembre 2008, 2011)
Keywords: beauport

Le « premier cartulaire » de l'abbaye de Mondaye - Thébault, Marion (Annales de Normandie, 2011)
Keywords: mondaye

Het archeologische onderzoek van de oude parochiekerk in de abdij van Tongerlo - Vander Ginst, Vanessa; Smeets, Maarten (2011)
Keywords: tongerlo

Klášter Panny Marie a svatého Jiří ve Střelné. Pokus o návrat k jednou již spatřenému - Wihoda, Martin (Co můj kostel dnes má, nemůže kníže odníti. Věnováno Petru Sommerovi k životnímu jubileu, 2011)
Keywords: velka střelná

Klášter Panny Marie a svatého Jiří ve Velké Střelné. Pokus o návrat k jednou již spatřenému - Wihoda, Martin (Co můj kostel dnes má, nemůže kníže odníti. Věnováno Petru Sommerovi k životnímu jubileu, 2011)
Keywords: velká střelná

Les décors peints médiévaux de l'abbatiale Notre-Dame et Saint-Jean de Floreffe - Wilmet, Aline (Bulletin de la Commission Royale des Monuments, Sites et Fouilles, 2011)
Keywords: floreffe

Vom Prämonstratenserkloster Veßra zum Hennebergischen Museum - Witter, Thomas (Mitteldeutsches Jahrbuch für Kultur und Geschichte, 2011)
Keywords: veßra

Johannes Busch und die Klosterbibliothek von St. Wiperti Quedlinburg im 15. Jahrhundert - Wozniak, Thomas (Quedlinburger Annalen, 2011)
Keywords: quedlinburg

Stavební dějiny premonstrátského kláštera Teplá. I. část - Zahradník, Pavel (Sborník muzea Karlovarského kraje, 2011)
Keywords: teplá

Oberberken und Unterberken im Spannungsfeld zwischen dem Kloster Lorch und dem Stift Adelberg - Zollmann, Günther (Heimatblätter. Jahrbuch für Schorndorf und Umgebung, 2011)
Keywords: adelberg; lorsch

Die letzten Mönche von Rüti. Eine Klosteraufhebung mit Nachwirkungen - Niederhäuser, Peter (Heimatspiegel: Illustrierte Beilage im Verlag von Zürcher Oberländer, 2010)
Keywords: rüti

Whithorn Priory. Burials at the tomb of St. Ninian - Faulkner, Neil (Current Archaeology, 2010)
Keywords: whithorn

L’abbaye de Beauport - Chartier-Le Floch, Erwan (ArMen. La Bretagne, Un Monde a Decouvrir, 2010)
Keywords: beauport

Dvojité kláštery v premonstrátském řádu - Zemanová, Hana (Charles University, 2010)
RESUMÉ Tato práce o dvojitých klášterech v premonstrátském řádu popisuje chronologicky vznik těchto klášterů od jejich počátku až do 12. století a to nejen na Východě, ale i na Západě. Dvojité kláštery vznikaly živelně především v době rané církve. Jejich vznik a postupný zánik ovlivňovala nejen náboženská, ale i sociální a politická situace v širším okolí. Nejznámější dvojité kláštery vznikaly ve 12. století v premonstrátském řádu a rychle se šířily z Francie i do sousedních zemí, protože svatý Norbert byl stoupencem takového uskupení. Později ale bylo třeba dát soužití obou pohlaví nějaký řád či pravidla. Bylo tedy rozhodnuto oddělit dvojité kláštery nejen vzdálenostně, ale i právně. V období schizmatu, kdy se generálních kapitul účastnili pouze opati řádu jižně od Rýna, bylo těžké prosazovat oddělení komunit a proto se dvojité kláštery na území dnešního Německa udržely déle než ve Francii. To dokládá i vznik dvojitého kláštera ve Weissenau v roce 1145 a následné přemístění sester do nedalekého Meisenthalu v roce 1156. A tak postupným rušením a přestěhováním konventů sester docházelo současně k rušení dvojitých klášterů a začal se více uplatňovat systém zakládání samostatných ženských klášterů. Dvojité kláštery měly v církevních dějinách svoje místo takové, jaké odpovídalo historické etapě, byly však...
Accepted: 2017-04-20T17:46:30Z Publisher: Univerzita Karlova, Katolická teologická fakulta
Keywords: 📚 premonstratensian (general)

Que relate le cartulaire de l'abbaye de Chaumont-Porcien ? - Luczka, Guillaume (Chez nous, 2010)
Keywords: chaumont-porcien

Chitry-le-Fort - Église paroissiale Saint-Valérien - (canton de Chablis) (Bulletin du centre d’études médiévales d’Auxerre, 2010)
Keywords: chitry

Grabungen an der ehemaligen Propstei St. Peter in Merzig - Adler, Wolfgang (Landesarchäologie Saar, 2005-2009, 2010)
Keywords: merzig

Wäschenbeuren und Kloster Adelberg - Akermann, Manfred (Burgen und Pfalzen der Staufer: ein Ausflugsführer, 2010)
Keywords: adelberg

Anticimenon: on the unity of the faith and the controversies with the Greeks - Anselm of Havelberg (Liturgical Press, 2010)
Keywords: 👤 anselm of havelberg

Anticimenon: über die eine Kirche von Abel bis zum letzten Erwählten und von Ost bis West - Anselm of Havelberg (Aschendorff, 2010)
Keywords: 👤 anselm of havelberg

Les abbayes Saint-Sauveur de l'Étoile (Authorn) et Saint-Georges (Saint-Martin-des-Bois): deux abbayes oubliées de l'ordre de Prémontré en Loir-et-Cher - Audebrand, Fabienne (Actes officiels des 31e et 32e colloques du Centre d'études et de recherches prémontrées : Loir-et-Cher ... 2005 : Mont-Saint-Martin (France), Leffe (Belgique), 2006, 2010)
Keywords: l'étoile

Musik eingebettet in Geschichte. Eine etwas andere Art der Vermittlung mittelalterlicher Handschriften - Behrendt, Inga (Archivnachrichten aus Hessen, 2010)
Keywords: arnstein

Rufillus von Weißenau (um 1200) in seiner Buchmalerwerkstatt - Berschin, Walter (Mittellateinische Studien II, 2010)
Keywords: weissenau

Die Freiherren von Sagogn/Schiedberg als Schiedsleute, Schutzherren und Förderer der Prämonstratenser - Bundi, Martin (Beiheft zum Bündner Monatsblatt, 2010)
Keywords: 🇩🇪 germany (general); 📚 premonstratensian (general)

Norbertijner pastorieën in het oude hertogdom Brabant: Een overzicht van bestaande en verdwenen panden - Cijffers-Rovers, Brenda (Norbertijnse pastorieën in het hertogdom Brabant, 2010)
Keywords: 🇧🇪 belgium (general); 🇳🇱 netherlands (general)

Archaeological Monitoring at Langley Abbey, Norfolk - Clarke, G. (2010)
On the 25th-27th November 2009, OA East carried out an archaeological watching brief at Langley Abbey, Langley Green, Langley, Norfolk, NR14 6DG (TG 3623 0286). The monitoring was carried out during an ongoing development including the repair of a barn formed from a substantial medieval abbey building, and the creation of educational access and interpretative displays. These works include the installation of a soakaway and drainage trenches, the construction of a new stairway and the removal of two concrete pads, a concrete floor and a modern brick wall. Features were also identified at the junction of the northern wall of the gatehouse and the north-western corner of the barn/western range, and these are interpreted as being contemporary with the original use of the Abbey. These comprise a buttress surviving below ground level, and subsequent reinforcement at a later date. The monitoring identified features in the barn/western range that post-date the dissolution of the Abbey including: a porch leading to a door in the eastern wall, a retaining wall blocking a further door in the eastern wall and a heavily truncated internal stair leading leading to a door in the western wall. A brick wall was also identified to the north of the gatehouse.
Num Pages: 15 Publisher: Oxford Archaeological Unit Ltd
Keywords: langley

The rental of Holy Trinity abbey, Lough Cé - Clyne, Miriam (Medieval Lough Cé: History, archaeology and landscape, 2010)
Keywords: lough key

De pastorie van Wezemaal: een gebouw aan het woord - Coenegrachts, Tom; Graauw, Jacqueline de (Norbertijnse pastorieën in het hertogdom Brabant, 2010)
Keywords: wezemaal

The Incunabula of Parc Abbey (Heverlee, Leuven) - Coppens, Christian (De Gulden Passer, 2010)
Keywords: park

Figurae tra littera e spiritus. Il tabernaculum di Mosè e le sue rappresentazioni medievali (da Cosmas Indicopleustes ad Adam di Dryburgh) - De Fraja, Valeria (Pensare per figure. Diagrammi e simboli in Gioacchino da Fiore, 2010)
Keywords: 👤 adam of dryburgh

Archiwum Norbertanek w Imbramowicach - Dębowska, Maria (Archiwa, Biblioteki i Muzea Kościelne, 2010)
Keywords: imbramowice

Die romanische Kirche St. Ägidius in Keferloh und ihre Wandmalereien - Dobler, Gerald (Jahrbuch des Vereins für Christliche Kunst in München, 2010)
Keywords: keferloh

Norbert von Xanten und der Orden der Prämonstratenser: Sammelband zur historischen Vortragsreihe im Norbertjahr 2009-2010 in Magdeburg - Dölken, Clemens (Norbertus-Verl., 2010)
Pages: 196
Keywords: 👤 norbert of xanten; 📚 premonstratensian (general)

La restitution du bâtiment conventuel sud - cellier et réfectoire - de l'abbaye de La Lucerne - Ducoeur, Danièle (Revue de l'Avranchin et du pays de Granville, 2010)
Keywords: la lucerne

Een onbekend handschrift met evangeliepreken uit de tekstgroep Zwolle - Ermens, Daniël (Ons geestelijk erf, 2010)
Keywords: park

Wybrane problemy badawcze zwiazane z romanskim portalem z kosciola sw. Wincentego na Olbinie, obecnie w kosciele sww. Marii Magdaleny we Wroclawiu. Przeglad literatury - Fafara, Aldona (Sródmiejska katedra. Kosciól sw. Marii Magdaleny w dziejach i kulturze Wroclawia, 2010)
Keywords: wrocław

Norbert von Xanten, die Gründung von Prémontré und die Entstehung des Prämonstratenserordens - Felten, Franz J. (Norbert von Xanten und der Orden der Prämonstratenser : Sammelband zur historischen Vortragsreihe im Norbertjahr 2009/2010 in Magdeburg, 2010)
Keywords: prémontré; 👤 norbert of xanten

Die Bibliothek des Prämonstratenserklosters Varlar bei Coesfeld - Frese, Werner (Klösterliche Sammelpraxis in der Frühen Neuzeit, 2010)
Keywords: varlar

Varlar und sein Priorat Deventer - Frese, Werner (Analecta Praemonstratensia, 2010)
Keywords: deventer; varlar

Neue Bruchstücke der Iwein-Handschrift X2 in der Stiftsbibliothek Schlägl - Glaßner, Christine (Zeitschrift für deutsches Altertum und deutsche Literatur, 2010)
Keywords: schlägl

Kurzgefasste Kirchengeschichte von Langenselbold - Haas, Rainer (Traugott Bautz, 2010)
Pages: 88
Keywords: selbold

Norbert von Xanten: der Gründer des Prämonstratenserordens und seine Zeit - Halder, Klemens H. (Tyrolia-Verl., 2010)
Pages: 143
Keywords: 👤 norbert of xanten

Graffiti bei den Nonnen: der spätgotische Umbau der Wenauer Klosterkirche - Heckner, Ulrike (Denkmal-Kultur im Rheinland: Festschrift für Udo Mainzer zum 65. Geburtstag, 2010)
Keywords: wenau

Die Klosterbasilika zu Ilbenstadt - Heß, Pascal (University of Frankfurt, 2010)
Keywords: ilbenstadt

Milevský klášter a jeho význam pro cestovní ruch Milevska - Houžvičková, Miroslava (Vysoká škola ekonomická v Praze, 2010)
The Premonstratensian monastery in Milevsko is the oldest monastery in South Bohemia and it belongs to the most valuable sights of the Czech Romanesque architecture. The aim of the bachelor thesis is to evaluate the importance of the monastery for the tourism of the town, to describe its potential and to provide enough information about this monument. This thesis also tries to analyse the position of this monastery in the town and the whole region and suggests eventual solutions to support the attendance of this monument.
Keywords: milevsko

Das Handschriftenverzeichnis des Prämonstratenserklosters Windberg von 1595 - Kaindl, Annemarie (Klösterliche Sammelpraxis in der Frühen Neuzeit, 2010)
Keywords: windberg

Premontrei prépostságok az esztergomi érsek joghatósága alatt. A királyi egyházak jogállásának kérdéséhez - Kiss, Gergely (Középkortörténeti tanulmányok, 6: A VI. Medievisztikai PhD-konferencia (Szeged, 2009. június 4-5.) előadásai, 2010)
Premonstratensian provosts under the authority of the archbishop of Esztergom. The question of the royal churches' legal status
Num Pages: 338 Pp.
Keywords: 🇭🇺 hungary (general)

Königsfeld, ein untergegangener Hof des Klosters Steinfeld - Konrads, Manfred (Jahrbuch des Kreises Euskirchen, 2010)
Keywords: steinfeld

Uposażenie ziemskie klasztoru Norbertanek fundacji rybnickiej i czarnowąskiej do 1228 roku - Kopka, Monika (Sanctimoniales: Zakony żeńskie w Polsce i Europie Środkowej (do przełom XVIII i XIX wieku), 2010)
Landbesitz des Prämonstratenserinnenklosters der Stiftung von Rybnik und Czarnowąsy (Czarnowanz) bis 1228
Num Pages: 514 Pp.
Keywords: czarnowąsy; rybnik

Quellen zur Geschichte des Stiftes Flaesheim im 13. Jahrhundert: Ergebnisse eines Editionsprojektes am Seminar für Klassische Philologie (Lehrstuhl Latinistik II) der Ruhr-Universität Bochum - Kordes, Matthias (Vestische Zeitschrift, 2010)
Keywords: flaesheim

Die ehemalige Prämonstratenser-Stiftskirche, später Kanonissen-Stiftskirche SS. Maria und Nikolaus in (Essen-) Stoppenberg - Kosch, Clemens (Die romanischen Kirchen von Essen und Werden : Architektur und Liturgie im Hochmittelalter, 2010)
Place: Regensburg Publisher: Schnell & Steiner, 2010, ISBN 978-3-7954-2346-9. - (Grosse Kunstführer)
Keywords: stoppenberg

De verdwenen kloosterkerk van Wittewierum (Groningen). Gebouw en inrichting tussen late middeleeuwen en vroeg-moderne tijd - Kroesen, Justin Ernest Alexander (Jaarboek voor liturgie-onderzoek, 2010)
Keywords: bloemhof

Der Kult des seligen Hroznata bis zum Jahre 1634 - Kubín, Petr (Die Heiligen und ihr Kult im Mittelalter, 2010)
Keywords: 👤 hroznata of bohemia

Ein Wahrzeichen mit Geschichte: der Georgenberg oberhalb von Bad Rodach, einst Ort einer klösterlichen Niederlassung - Kuschbert, Andreas (Heinrichskalender, 2010)
Keywords: georgenberg

K datování první etapy výstavby románského kostela sv. Martina v Bernarticích, okr. Písek - Kyncl, Tomáš; Varhaník, Jiří (Archaeologia historica, 2010)
Unikátně dochované pozůstatky střešních latí románského kostela sv. Martina v Bernarticích jsou současné s výstavbou západního štítu jeho lodi. Dendrochronologická analýza prokázala, že jak dřevo latí, tak dřevo nosníku lešení štítu pochází z jedlí smýcených v zimě 1222/1223.
Keywords: bernartice

Zur Theologie der Prämonstratenser im 12. Jahrhundert - Leinsle, Ulrich G. (Norbert von Xanten und der Orden der Prämonstratenser: Sammelband zur historischen Vortragsreihe im Norbertjahr 2009/2010 in Magdeburg, 2010)
Keywords: 📚 premonstratensian (general)

Le recueil de miracles: un miroir de la société médiévale au XIIe siècle. Étude critique du Liber miraculorum sancti Cornelii de l'abbaye de Ninove - Libert, Brieuc (University of Louvain, 2010)
Keywords: ninove

Cleholta - Clarus Ortus - Clarholz. Das Kloster der Prämonstratenser in der Axtbachniederung - Meier, Johannes (Klöster und Landschaft: das kulturräumliche Erbe der Orden, 2010)
Keywords: clarholz

Zum Bildprogramm des gotischen Gewölbes der ehemaligen Prämonstratenserkirche in Clarholz - Mense, Josef (Jahrbuch für Westfälische Kirchengeschichte, 2010)
Keywords: clarholz

San Pelayo de Cerrato. De la fundación monástica a la Fundación Grupo Siro - Moratinos García, Manuel (Fundación Grupo Siro, 2010)
Keywords: san pelayo de cerrato

Abbaye de Beauport: fondation et essor (XIIe-XVe siècles) - Nabucet, Amélie (Université de Rennes, 2010)
Keywords: beauport

Gospel Salad: Conversion among the Twelfth-Century Premonstratensians - Neel, Carol (Studies in Medieval and Renaissance History, 2010)
Keywords: 📚 premonstratensian (general)

Anthropologische Untersuchung des Kinderskeletts aus Merzig-St. Peter, Grab 21 - Nicklisch, Nicole; Alt, Kurt W. (Landesarchäologie Saar, 2005 - 2009, 2010)
Keywords: merzig

The Mellifluous Bee: The Marian Theology of Adam of Dryburgh - O’Cinnsealaigh, Benedict D. (Authorhouse, 2010)
Keywords: 👤 adam of dryburgh

Dzieje klasztorów norbertańskich w Żukowie - Okroy, Franciszek Ksawery (Wydawnictwo "ROST", 2010)
Keywords: żukowo

Ženské kláštery v pohusitských Čechách – premonstrátky - Pátková, Hana (Sanctimoniales: Zakony żeńskie w Polsce i Europie Środkowej (do przełom XVIII i XIX wieku), 2010)
Frauenklöster in Böhmen in der Zeit nach Hussitenkriegen – Prämonstratenserinnen
Num Pages: 514 Pp.
Keywords: 🇨🇿 czechia (general)

Lehnbedingungen des Klosters Engelport - Pies, Norbert J. (Jahrbuch für den Kreis Cochem-Zell, 2010)
Keywords: engelport

Klöster der Prämonstratenser und Zisterzienser im östlichen Deutschland: Ein Beitrag zur vergleichenden Kulturlandschaftsanalysemittels landeskundlicher Bestandsaufnahme - Porada, Haik Thomas (Klöster und Landschaft: das kulturräumliche Erbe der Orden, 2010)
Keywords: 🇩🇪 germany (general)

Kloster Jerichow - Ramm, Peter (Verlag Janos Stekovics, 2010)
Keywords: jerichow

Überlegungen zu Bautyp und Baumeisterfrage der zerstörten Abteikirche von Wadgassen - Reinert, Manfred; Reinert, Stephan (Kurtrierisches Jahrbuch, 2010)
Keywords: wadgassen

Philip of Harvengt's Life of the Blessed Virgin Oda - Robertson, Lynsey (Journal of Medieval History, 2010)
For every famous author of the twelfth-century renaissance, there are numerous lesser-known writers. Despite being overshadowed by more brilliant scholars or those closer to the centre of important events, their voices add depth to the study of the intellectual and religious history of this period. A founding member of one of the earliest Premonstratensian houses, a highly-educated and prolific author, much in demand as a hagiographer, and a vigorous defender of the clerical order, Philip of Harvengt is one such writer, and a worthy subject for study. This article examines one of his hagiographical works, the Life of the Blessed Virgin Oda, a nun attached to his own house, whom he portrays as a martyr. It analyses the predominant and recurrent concerns and ideals expressed in the Life, particularly the claim to martyrdom, and the means by which this is expressed.
Keywords: 👤 philip of harvengt

Revitalisierung von Kirchenräumen – St. Ägidius in Keferloh und St. Alban bei Peterskirchen - Rohrmann, Hans (Jahrbuch des Vereins für Christliche Kunst in München, 2010)
Keywords: keferloh

St. Salvator : Pfarrkirche, ehemalige Prämonstratenserabteikirche - Rutz, Oswin (Kath. Pfarramt St. Salvator, 2010)
Keywords: griesbach

Los cartularios desde la perspectiva archivística: el “Becerro Mayor” de Santa María la Real de Aguilar de Campoo - Sánchez de Mora, Antonio (Publicaciones del Instituto Tello Téllez de Meneses, 2010)
Keywords: aguilar de campoo

Maximilian I. und die bayerischen Klosterbibliotheken: Unter besonderer Berücksichtigung des Prämonstratenserklosters Windberg - Schmid, Alois (Klösterliche Sammelpraxis in der Frühen Neuzeit, 2010)
Keywords: windberg

Het Vrouwenstift van Keyserbosch te Neer - Schreurs, Petrus (Rondom het Leudal: tijdschrift voor natuur, geschiedenis en milieu, 2010)
Keywords: keizerbosch

Mitglieder der Familie Bruch als Pröpste der Prämonstratenserabtei Wadgassen - Skalecki, Liliane (Neue Erkundungen zur Kultur und Geschichte Wadgassens: Jubiläumsschrift anläßlich der 875sten Wiederkehr der Klostergründung in Wadgassen 1135-2010, 2010)
Keywords: wadgassen

Želiv Reginarda Metského - Sommer, Petr (Za zdmi kláštera. Cisterciáci v českých dějinách, 2010)
Keywords: želiv

Klášter Rosa Coeli - nejstarší šlechtická fundace na Moravě - Studeník, Jan (Charles University, 2010)
Keywords: kounice

Tradycja norbertanska w przedstawieniach Marii z Dzieciatkiem trzymajacym jablko - Szczesna, Joanna (Roczniki humanistyczne, 2010)
Keywords: 📚 premonstratensian (general)

Zur Frühgeschichte des Prämonstratenserstifts Heiligenberg in der Grafschaft Bruchhausen: Ein Annäherungsversuch. - Thalmann, Söhnke (Oldenburger Jahrbuch, 2010)
Keywords: heiligenberg

De Lambertuskerk en Helden: vanaf het jaar 1230 tot heden - Thiesen, Henk M (s.n., 2010)
Section: 335 p. : ill., foto's. ; 24×29 cm.
Keywords: helden

A csornai premontrei monostor a 13-14. században - Vajk, Ádám (Soproni Szemle: Helytörténeti folyóirat, 2010)
The Premonstratensian abbey of Csorna in the 13th-14th centuries
Keywords: csorna

Les avatars des manuscrits médiévaux de l'abbaye de Parc - Van Balberghe, Emile (De Gulden Passer. Tijdschrift voor Boekwetenschap, 2010)
Keywords: park

De datering van de regeerperiodes van de Ninoofse abten tot 1578 - Van De Perre, Dirk (Analecta Praemonstratensia, 2010)
Keywords: ninove

De herberg van de abdij van Ninove te Dendermonde - Van De Perre, Dirk (Gedenkschriften Oudheidskundige Kring der Stad en des Voormaligen Lands van Dendermonde, 2010)
Keywords: ninove

De norbertijnenabdij van Park-Heverlee en haar netwerk van pastorieën - Van Lani, Stefan (Norbertijnse pastorieën in het hertogdom Brabant, 2010)
Keywords: park

Regesten en transcripties van de oorkonden van het Maria Magdalenaklooster te Nijmegen (1250-1652) - Van Synghel, G.A.M. (Koninklijke Nederlandse Akademie van Wetenschappen, 2010)
Keywords: nijmegen

Het klooster van Wittewierum - Wildeman, Jannes A. (Het Wold : een tijdschrift over de geschiedenis van de dorpen Slochteren, Schildwolde, Overschild, Luddeweer, Woudbloem, Froombosch en Kolham, 2010)
Keywords: bloemhof

L’apport de l’archéométrie à l’étude des décors peints de l’abbaye de Floreffe - Wilmet, Aline (Université de Liège, 2010)
Keywords: floreffe

A csornai premontrei prépostság épületének megújulása - Winkler, Gábor (Soproni Szemle: Helytörténeti folyóirat, 2010)
The reconstruction of the Premonstratensian abbey of Csorna
Keywords: csorna

Das Prämonstratenserkloster Vessra: Urkundenregesten 1130 - 1573 : mit einem Verzeichnis der weiteren archivalischen Quellen - Wölfing, Günther (Böhlau Verlag, 2010)
Erstmalig liegt jetzt eine umfassende Quellenedition des bedeutendsten Klosters im ehemals frankischen Suden des Freistaates Thuringen vor. Obwohl das Pramonstratenserkloster Vessra als Hauskloster der Fursten von Henneberg und als ein geistiges Zentrum in Ostfranken eine grosse Ausstrahlung hatte, fehlte bislang eine solche Sammlung. Uber tausend zum grossten Teil unveroffentlichte Urkunden sind in ausfuhrlichen Vollregesten aufbereitet und durch ein Verzeichnis der ubrigen archivalischen Quellen des Klosters erganzt worden. Die Edition erschliesst uber die Geschichte des Klosters hinaus der thuringischen und frankischen Landesgeschichte sowie der Ordens- und Wirtschaftsgeschichte neue Quellen.
Keywords: veßra

Premonštráti v Bzovíku - Žažová, Henrieta (Zlatá kniha Hontu, 2010)
Keywords: bzovík